Impacts of high-altitude aerosol hygroscopicity on cloud microphysics in the North China Plain: A WRF fast-SBM modeling study - Qian Gao; Hui He; Xiang'e Liu; Yan Yang; Rong Yuan; Ping Tian; Kai Bi; Fei Wang; Jiujiang Sheng; Yongqing Wang (Atmospheric Research, 2026)

Correction to: Gsα deficiency in macrophages promotes tumor progression via the MAPK signaling pathway - Wenjiang Yan; Jingjing Yang; Siyu Tan; Tixiao Wang; Rong Xiao; Na Li; Min Chen; Lee S. Weinstein; Lifan He; Chang Ma; Jingsu Zhang; Lifen Gao; et al. (Journal of Molecular Medicine, 2026)

Gsα deficiency in macrophages promotes tumor progression via the MAPK signaling pathway - Wenjiang Yan; Jingjing Yang; Siyu Tan; Tixiao Wang; Rong Xiao; Na Li; Min Chen; Lee S. Weinstein; Lifan He; Chang Ma; Jingsu Zhang; Lifen Gao; et al. (Journal of Molecular Medicine, 2026)

Overexpression, clinical significance and potential mechanisms of protein kinase D1 in hepatocellular carcinoma: multi-omic analyses and pharmacological insights - Zhen-dong Chen; Hui-ping Lu; Yan-ting Zhan; Fei-yan He; Liang-qin Zhu; Yu-long Deng; Xi-ni Wei; Min-ying Yang; Kai Qin; Yu-xing Tang; Ke-jun Wu; Zhi-guang Huang; et al. (Functional & Integrative Genomics, 2026)

Long-term fertilization enhances Bacilli cell size by increasing soil resource availability and shifting its metabolic strategies - Nan Rong; Youzhi Feng; Ruirui Chen; Yuanyuan Bao; Shiying He; Shudong Ding; Xiaoyuan Yan (Agriculture, Ecosystems & Environment, 2026)

Cropping diversification increases microbial network complexity associated with enhanced soil multifunctionality and resistance to global change - Qian Guo; Peng He; Rui Li; Rong Yang; Jianing Wang; Tengfei Ma; Ning Ling; Lina Zheng; Zhaoming Wang (Soil and Tillage Research, 2026)

Reconstruction of the Cretaceous palaeo-plateau in South China: Insights from geochemical thermobarometry and isostasy modelling - Hanqiao Zheng; Junfeng Gong; Rong Yang; Ruohong Jiao; Junqing He; Fengqi Zhang; Hongdan Deng; Jiakang Huang; Zhiquan Yu; Yunlong Wang; Hanlin Chen; Shufeng Yang (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Oral Janus nanomotor covalent conjugation rapeseed protein-derived DPP-IV inhibitory peptide and liraglutide: A self-propelled targeted delivery system for promoting insulin secretion and glucose-lowering - Huimin Dong; Haiyan He; Huizhen Xing; Chengzhi Guo; Zhigao Wang; Rong He (Food Research International, 2026)

AIE-active dual-pore covalent organic framework for colorimetric/fluorescence detection and degradation of perfluorooctanoic acid - Tianyuan Yu; Shuai Liu; Shaoxi He; Guoyi Pu; Xi Zhang; Yanxiong Liu; Wenyu He; Ziyu Bao; Zezhou Zhao; Jiahui Liu; Fei Li; Rong Sheng Li; et al. (Chemical Engineering Journal, 2026)

Influence of the intrinsic properties of nanopipettes on sensing performance - Wenhao Ma; Rong Tian; Shixuan He; Shaoxi Fang; Bohua Yin; Yongjia Wang; Ting Weng; Wanyi Xie; Danqun Huo; Changjun Hou; Deqiang Wang (Chemical Engineering Journal, 2026)

Biochar promotes methane production from anaerobic digestion: Pore structure regulation and quantitative correlation assessment - Ze-Mu Li; Ai-Hua Li; Cong-Cong Tang; Qian Li; Ai-Juan Zhou; Wenzong Liu; Zhi-Ling Li; Zhang-Wei He; Rong Chen (Bioresource Technology, 2026)

Multi-copy expression of classical swine fever virus E2 in a recombinant pseudorabies virus enhances immunogenicity and supports its potential as a PRV-CSFV bivalent vaccine candidate - Xianfei Shang; Hui Zhao; Yufeng He; Zhenxiang Rong; Xiquan Ke; Jinglei Gao; Ke Zhang; Jiyuan Luo; Min Zhang; Huanchun Chen; Xiangmin Li; Ping Qian (Veterinary Microbiology, 2026)

Spearman rank analysis and dynamic contact stress concentration model of Brazilian splitting fracture behavior of coal samples under impact load - Kong Xiangguo; Rong Zhihao; Ma Yankun; Lin Haifei; Xiao Peng; He Di; Ji Pengfei; Zhu Yanhui (Physics and Chemistry of the Earth, Parts A/B/C, 2026)

Molecular insights into the transformation of dissolved organic matter from refinery wastewater in receiving water: Photochemical and photo-microbial effects - Leqi Wang; Lei He; Zhuoyu Li; Haifeng Rong; Yifei Zhu; Zelin Niu; Chunmao Chen; Qinghong Wang (Journal of Environmental Chemical Engineering, 2026)

Arginine-rich hemp seed globulin-tannic acid non-covalent complexation: Structural compaction, enhanced antioxidant/emulsifying properties, and modulated digestibility - Yu Zhang; Xiao-Dong Tian; Zuo-Xing Di; Hai-Bo Jin; Guang-Xiang He; Suo-He Yang; Rong-Yue Zhang; Lei Ma; Xiao-Yan Guo; Peng-Wei Xu (Food Chemistry, 2026)

Reducing the residual oil body content in soy protein isolate (SPI) through pH regulation and studying the changes in physicochemical, flavor profiles, and processing properties - Merga Nagassa; Shudong He; Shuyun Liu; Yulong Deng; Huimei Li; Rong Zhang; Jiazhen Song; Suwei Jiang; Hanju Sun (Food Chemistry, 2026)

Evolutionary agroecology: Passive responses to light competition increase yield in wheat - Yong-He Zhu; Yuan Li; Rong-Rong Wang; Jacob Weiner; Feng-Min Li (Field Crops Research, 2026)

Autogenous dentin graft material promotes bone regeneration involving OPN/CD44-mediated BMSC recruitment - Xin Deng; Jianmin Zhuo; Yanyan Yang; Ziliang Zhou; Jing Li; Rong Rong; Weihong Chen; Jiashen Chen; Siwen Yu; Siyuan Chen; Lu He; Janak Lal Pathak; et al. (Chemical Engineering Journal, 2026)

Construction and application of an antifouling transistor-based cytosensor for detection of CTCs - Rong Zou; Huiling Yan; Lei Wang; Yu Chen; Caiyuan Liao; Bowen Zhang; Gang Chang; Ping Wang; Hanping He (Chemical Engineering Journal, 2026)

Temporal changes of soil erodibility and its driving factors in long-term sugarcane continuous cropping systems - Juan Wei; Tieguang He; Yu Zhu; Lirong Su; Huiping Ou; Yingying Deng; Mengge Yang; Jinlong Chang; Yuliang Liao; Qingbiao Rong; Yuhan Huang (CATENA, 2026)

PepOSX-AI: CPP - an interpretable transformer-based deep learning model for prediction of cell-penetrating peptides - Haowen Chen; Weiwei He; Kaiyan Feng; Rong Xu; Sheng Yin; Lin Zheng; Jing Chen; Mouming Zhao; Jucai Xu; Lijun You (Analytica Chimica Acta, 2026)

Semiconducting polymer-based ratiometric fluorescent nanoprobe for highly accurate imaging of H2S in inflammatory and tumor cells - Chen Han; Xing Wang; Yating He; Rong Wang; Hong-Min Meng; Lin Zhang; Zhaohui Li (Analytica Chimica Acta, 2026)

Microenvironment-regulated Fe single-atom nanozyme with neutral-pH peroxidase-mimicking activity for paper-based multiplexed biomarker detection - Rong Huang; Linping Tian; Dongmei Deng; Xiaoxia Yan; Haibo He; Wei Wang; Liqiang Luo (Analytica Chimica Acta, 2026)

Differential effects of alcohol-derived serum metabolites and direct ethanol exposure on mouse preantral follicle development - Meng-Ting Cao; Yang Shi; Chun Li; Yi-Lin Fan; Zhu-Rong Hu; Le-Ning Dang; Xue-Rui He; Wei-Qiang Luo; Jing-Jing Li; Xing-Rong Yan (Chemico-Biological Interactions, 2026)

Plant litter enhances hexabromocyclododecane removal in riparian zones at high water level: Insights from the coupling of microbial dehalogenation and carbon cycling - Rong Wang; Juan Chen; Li Wang; Han Gao; Qihao Nie; Shunqing Zhang; Qiming He (Water Research, 2026)

Nanoconfinement-enhanced peroxymonosulfate activation by Co single atoms in hollow mesoporous carbon: Roles of active-site chemistry and mesoscale confinement - Hao Luo; Junli Zheng; Jiaxin Liu; Junjun Ma; Rui He; Chuqi Huang; Rong Xie; Qintie Lin (Water Research, 2026)

Dysregulation of xenobiotic metabolism and mitochondrial dysfunction exacerbate acetaminophen-induced hepatotoxicity in human antigen R-deficient male mice - Natalie Eppler; Elizabeth Jones; Forkan Ahamed; Naren Raja; Jephte Y. Akakpo; Margitta Lebofsky; Lily He; Ira Vats; Priyanka Ghosh; Yifan Yu; Kaitlyn Thomas; Colin McCoin; et al. (Toxicology, 2026)

Electrostatically assembled gold nanocluster-enhanced porphyrinic metal-organic framework nanozymes for oxygen-boosted photodynamic therapy of hypoxic tumors - Ao He; Juan Zhou; Jing Zhu; Guojing Hong; Minglan Fan; Yuyan Bao; Rong Li; Manxiao Cheng; Xiang Ran (Journal of Photochemistry and Photobiology B: Biology, 2026)

Human-relevant co-exposure to 6:2 Cl-PFESA and PFHxS impairs sperm motility and blood-testis barrier integrity in male mice: Evaluation of combined effects - Lan Shi; Tianrui Gao; Zhipeng Zhu; Fan Yang; Bing Han; Jia Lv; Lin Tao; Yang Gao; Rong Hua; Huan Wu; Yichao Huang; Xiaojin He (Journal of Hazardous Materials, 2026)

Endoplasmic reticulum stress-mediated glycophagy drives macrophage M1 polarization in silica nanoparticles-induced pulmonary fibrosis - Lei Bao; Zihan Geng; Linpeng Niu; Lili Shi; Liyi He; Yaxian Pang; Cunhui Zhang; Yan Liu; Jiawei Chen; Beibei Shi; Ruiting Wu; Jingyuan Wang; et al. (Journal of Environmental Sciences, 2026)

Engineering bimetallic Cobalt–Iron glycerate Co-Catalysts on bismuth vanadate for improved charge transfer and photoelectrochemical catalytic water oxidation - Tsung-Rong Kuo; He-Jin Li; Kai-Jie Chuang; Chutima Kongvarhodom; Sibidou Yougbaré; Muhammad Saukani; Hung-Ming Chen; Lu-Yin Lin (Fuel, 2026)

Green synchronous fluorescence spectroscopy using non-carcinogenic standard: Rapid determination of carcinogenic polycyclic aromatic hydrocarbons in dairy products - Yi-Han Guo; Jia-Rong He; Jia-Wen Wei; Hong-Jun Liu; Jia-Lin Li; Ping-Ping Wu; Gaofeng Zheng; He-Dong Luo; Na Li; Yao-Qun Li (Food Control, 2026)

Endogenous iron mobilization and redox disruption by tandem nanoreactors for ferroptosis-driven cancer immunotherapy - Lei Qiao; Tong-Yin Xiong; Tian-Hao Yang; Wan-Rong Wang; Xiao-Yan He; Ye-Zi You; Long-Hai Wang (Chemical Engineering Journal, 2026)

RETRACTED ARTICLE: Molecular mechanisms of flower color variation in Impatiens uliginosa: insights from transcriptome sequencing and functional analysis of the IuMYB1 gene in anthocyanin biosynthesis and pigmentation - Baiyang He; Yuteng Xue; Shanman Li; Xue Hu; Xiaoli Lou; Jiwei Wang; Huang Deng; Shunming Zhang; Chao Luo; Yuhong Rong (Physiology and Molecular Biology of Plants, 2026)

Grass Carp Reovirus ( GCRV ): Biology, Immune Responses and Control Strategies - Waqar Younas; Mijuan Shi; Rong Huang; Yaping Wang; Libo He; Hong Yang; Lei Zhang; Yingyin Cheng; Wanting Zhang; Lanjie Liao; Yongming Li; Bin Gui; et al. (Reviews in Aquaculture, 2026)
As the world's population grows, aquaculture is becoming a rapidly growing source of protein. Grass carp ( Ctenopharyngodon idella ) is one of the most important aquacultured species in China and has emerged as a significant commercial fish worldwide. However, grass carp reovirus (GCRV) poses a significant threat to grass carp aquaculture. This review covers GCRV biology, phylogeny, pathogenesis, immune response pathways, therapeutic approaches, and future challenges and directions. A comprehensive phylogenetic analysis describes the structure of GCRV, its entry into cells, its molecular architecture, its replication procedures and its interactions with the host, with a particular focus on the pivotal role of Pattern Recognition Receptors (PRRs). The paper explores how PRRs, such as RLRs (RIG‐I and MDA5) and TLRs (TLR3 and TLR19), are essential for identifying GCRV and initiating robust antiviral responses, particularly the interferon pathway. The paper goes on to explain the complex immune evasion tactics employed by GCRV, emphasizing how viral proteins such as VP41, VP4 and VP56 selectively target and interfere with critical components of PRR signaling cascades, such as MAVS‐TBK1 and MITA/STING, thereby reducing host immunity. Various next‐generation vaccines are being developed, including DNA, subunit, VLP and oral/mucosal platforms. These are supported by Chinese herbal and chemical antivirals. According to CRISPR/Cas9, experimental RNAi, PI4KB and SOCS3a/3b are host genes that can be altered to increase grass carp resistance to GCRV. This research offers significant insights into viral cell invasion and strengthens innate and adaptive immunity, enabling safer, more practical and multilayered control in aquaculture.

Fine mapping and candidate gene analysis of tassel glume closure1 (tgc1) gene in maize (Zea mays L.) - Ziwen Shi; Jinmiao Qin; Sheng Zhang; Yujiao Gao; Qing He; Hongyang Yi; Tingzhao Rong; Moju Cao (Theoretical and Applied Genetics, 2026)

Evaluating the effectiveness of marine ecological red lines: an integrated assessment of ecological outcomes and governance performance - Rong Zeng; Wenhai Lu; Chengliang He; Jie Liu; Yan Xu; Chang Liu; Yangyi Ai; Yan Zheng (Frontiers in Marine Science, 2026)
Marine protected areas worldwide often exhibit uneven conservation outcomes, largely due to differences in governance effectiveness and management implementation. As a large-scale spatial conservation policy, Marine Ecological Red Lines (MERLs) have been widely implemented in China to regulate human activities and safeguard critical marine ecosystems. However, their protection effectiveness remains insufficiently evaluated using quantitative and scalable approaches. In this study, we develop an indicator-based assessment framework grounded in the Pressure–State–Response (PSR) model to evaluate the effectiveness of MERLs. The framework integrates indicators of anthropogenic pressures, ecosystem conditions, and management responses, enabling spatially explicit and temporally comparable assessment. We apply this framework to MERLs in Hainan Province over a five-year period (2020–2024) and conduct systematic comparisons with adjacent non-protected areas. Furthermore, correlation analysis is used to examine the relationships between pressure reduction and ecological state changes, providing preliminary insight into the associations between management actions and ecological outcomes. The results show that MERLs are associated with reduced anthropogenic pressures and improved ecological conditions relative to surrounding areas, although spatial heterogeneity in outcomes persists. The proposed framework provides a structured approach for examining interactions among pressures, ecosystem states, and governance responses, and provides quantitative evidence supporting conservation effectiveness assessment at a provincial scale. The proposed framework may also support adaptive management and policy optimization for MERLs and provide practical reference for the implementation of Other Effective Area-Based Conservation Measures (OECMs).

Partitioned identification of vegetation drivers and their interactions in the Loess Plateau via interpretable XGBoost-SHAP - Yi Ren; Jia Tian; Xuejuan Feng; Guowei Wu; Caifeng He; Wei Bao; Tao Yu; Jiahui Gao; Tao Wang; Jian Wen; Rong Tao (Environment, Development and Sustainability, 2026)

Early and prolonged oral edaravone for neuroprotection in acute ischemic stroke: the ERASE-STROKE randomized controlled phase 3 trial - Yang Xiang; Wang-Sheng Jin; Xin-Chen Zhu; Yan Song; Xiao Chen; Qing-Hua Wang; Hao-Lun Sun; Yang Zhao; Xiao-Rong Yu; Tao Feng; Ai-Hong Guo; Hong-Guo Dai; et al. (Science Bulletin, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Burkholderia cepacia NB-13: Biocontrol efficacy and medium-driven metabolic regulation - Zhou Yin; Xiaoqin Li; He Guan; Dindi Tu; Xingyi Luo; Wancheng Hu; Fanqian Zhou; Menglong Li; Shulin Liu; Hui Li; Rong Song; Kailin Liu; et al. (Pesticide Biochemistry and Physiology, 2026)

Corrigendum to “State-selective engineering in luminescent metal-organic frameworks: Ligand-to-ligand charge transfer activates superior photocatalytic sterilization in Wei River” [J Hazard Mater 500 (2025) 140448] - Liang Qiu; Yajie Zhang; Baiyu Wu; Wenqiong Liu; Yiwen Xie; Jing He; Kerang Huang; Jianlong Wang; Rong Wang (Journal of Hazardous Materials, 2026)

Species-specific bioaccumulation and biotransformation of antibiotics shape differential toxicological effects in a multi-level aquatic community - Bin Wang; Hailing Zhou; Mengting Li; Bingyu Shen; Lidan Zhang; Jiayi Yang; Yushi Fang; You Zi; Jinmei Chen; Yujie He; Rong Ji (Journal of Hazardous Materials, 2026)

Three-stage temperature-ramping stirred-tank bioleaching enhances copper recovery from chalcopyrite by mitigating surface passivation - Rong Nie; Bingyang Tian; Xinlong Yang; He Shang; Wenjuan Li; Jiankang Wen; Hongying Yang (Journal of Cleaner Production, 2026)

Cold plasma processing of Summer Black grape juice: Modulation of bioactive compounds, flavour fingerprint evolution, and XGBoost-based storage time prediction - Huizhen Xing; Shanqun Wang; Jingjing Kan; Qirui Shi; Zhigao Wang; Rong He (Innovative Food Science & Emerging Technologies, 2026)

Hypoallergenic casein peptides derived from strain–enzyme combined hydrolysis attenuate allergic immune responses and modulate gut microbiota in mice - Xiaomei Zhang; Minting Rong; Jinlan Xie; Ting Wang; Zhigui He; Aiying Xu; Xiaomeng Wu; Haizhu Wu (International Dairy Journal, 2026)

Engineering peptide-functionalized fermented milk with enhanced DNA-protective, antioxidant and anti-inflammatory properties via ultrasound-assisted enzymolysis - Jing Hao; Shengqi Zhang; Minquan Wu; Mokhtar Dabbour; Benjamin Kumah Mintah; Chunhua Dai; Rong Zhang; Zhaoli Zhang; Haile Ma; Ronghai He (Food Research International, 2026)

The heterojunction regulated by Au nanoparticles efficient removal of NO through the synergistic effects of SPR and the electron bridge - Youzhou He; Zhiqiang Guo; Yue Li; Xingyan Liu; Kaili Wu; Yuyu Fang; Rong Peng; Min Fu; Bowen Lei (Environmental Research, 2026)

The synthesis of alkaline earth metal-organic framework based on asymmetric triazine hexacarboxylic acid and iodine capture performance - Shao Bin Xu; He Qun Cai; Rong Huo; Ting Zhang; Jing Jin; Yong Heng Xing; Feng Ying Bai (Environmental Research, 2026)

China could simultaneously increase wheat yield and nitrogen use efficiency under the temperature rise of 1 ℃ through optimal crop managements - Kaiyuan Gong; Shuoqiu Ding; Yadong Luo; Yinghua Zhang; Xiao Wang; Fengying Duan; Xia Li; Liangbing Rong; Zhihao He; Hao Feng; Qiang Yu; Wenbin Zhou; et al. (European Journal of Agronomy, 2026)

Na-rich Na3.2V1.9Fe0.1O2(PO4)2F cathode unlocks high energy density and wide-temperature operation in sodium-ion batteries - Qiang Fu; Qin He; Fangxiang Song; Keliang Wang; Jing Li; Xianquan Ao; Rong Li (Chemical Engineering Journal, 2026)

Phosphorus–boron synergistic carbonization/dormancy strategy enables polyurethane foams with aging enhanced fire safety - Shuang Li; Hai-Bo Zhao; Ming-Jun Chen; Lei He; Lin Zhang; Fu-Rong Zeng; Yu-Zhong Wang (Chemical Engineering Journal, 2026)

Biochar–bentonite composite enabling antibiotic removal and greenhouse gas mitigation in waters - Yan Sun; Xiang Jia; Le Dai; Wei Ding; Yongjie Wang; Jin Zhang; Huan He; Nan Rong; Pei Lei (Chemical Engineering Journal, 2026)

Natural pyrite-enhanced co-culture system for simultaneous nitrate and ammonium removal under low C/N conditions: Mechanistic insights and real wastewater application - Kuang-di Xu; Pan He; Xiang-lin Liu; Lei Yu; Si-jia Li; Quan Wang; Rong-ping Chen; Ke Yin; Guang Guo; Wen-Jie Xu; Gong-De Wu (Bioresource Technology, 2026)

Evolving natural yeast to protein-rich micro-grain adaptable for non-sterile low-carbon biomanufacturing - Xinru Wang; Zhaoyu Xu; Zhihui Shi; Weihe Rong; Hailin He; Hongyi Zhou; Lu Liu; Zhijia Liu; Wenjie Sui; Guokun Wang; Yanhe Ma (Bioresource Technology, 2026)

An Indicator System for Evaluating the Powerhouse of Meteorological Science and Technology: Design and Preliminary Application - Chaolin Zhang; Xudong Liang; Min Wen; Jianjun He; Wenjuan Zhang; Chang Liu; Qing Sun; Rong Yu; Xiaolu Yan; Zhu Zhang; Qihua Jin; Aili Shi; et al. (Journal of Meteorological Research, 2026)

Effects of GIAHS conservation on agricultural landscape and ecological sustainability in heritage sites: evidence from the Yuanyang Hani Rice Terraces - Jin-Rong Zhang; Hong-Bo Li; He-Ping Yang; Meng-Na Qi (Environment, Development and Sustainability, 2026)

Study on the anti-inflammatory effects of active ingredients in Vespa velutina auraria Smith - Ming-Rong Li; Xiu-Qin Pang; Chao-He Liu; Wei Zhang; Heng Liu; Hai-Rong Zhao; Zhi-Bin Yang; Yan Wang; Yi-Hao Che; Huai Xiao (Natural Product Research, 2026)

Corrigendum to “Progress in the application of Salmonella vaccines in poultry: A mini review” [Vet. Immunol. Immunopathol. 278(2024), 110855] - Jie Pan; Rong-rong Wei; Ping Xu; Yun-ying Liu; Chen Li; Guo-wei Ding; Juan Fan; Yu-he Li; Jing-yi Yu; Peng Dai (Veterinary Immunology and Immunopathology, 2026)

Sodium alginate bead flotation assisted by cationic cellulose nanofibers for polystyrene microplastic removal - Linjuan Zhang; Hao Wen; Kemin Wei; Xichen Zheng; Jia He; Manli Wang; Peng Wei; Shaoli Fan; Guiwen Rong (Process Safety and Environmental Protection, 2026)

Integrated metabolomic and transcriptomic analyses reveal that pectin metabolism mediates texture divergence in grape berries - Zhi-Meng Gan; Xiao-Yan Ai; Yong Liu; Wei Zhu; Yang Zhang; Hui-Liang Wang; Fu-Rong Wang; Xiao-Dong Hou; Hua-Ping He; Lin-Zhong Gong (Postharvest Biology and Technology, 2026)

Undescribed triterpenoid ellagitannins from Castanopsis calathiformis and their potential antiproliferative and hypoglycemic activity - Ya-feng Wang; Ying-rong Bao; Rui-jie He; Nao Pang; Zhang-bin Liu; Bing-yuan Yang; Gui-qin Li; Yong-lin Huang (Phytochemistry, 2026)

Multilayer microbial framework of aerobic granule microecosystems: Integrating community ecology, genetic networks, and enhancement strategies - Rushuo Yang; Zhe Liu; Yongjun Liu; Yuhang Zhang; Jie Lei; Zhuangzhuang Yang; Haobo He; Jiaxuan Wang; Rong Chen (Bioresource Technology, 2026)

Cloning and functional analysis of MdCRCT1 in the regulation of drought tolerance in apple - Xiao-Wen Li; Ya-Qi Liu; Jing-Yi Su; Xin-Rong Shi; Chang Li; Xue Wang; Qi-Fei Wu; Xuan He; Hong-Jian Cao; Xiao-Fei Wang; Ting-Ting Zhang (Physiology and Molecular Biology of Plants, 2026)

Differential analysis of lipid profiles in natural Calculus Bovis and Bovis Calculus Sativus by UHPLC-MS/MS - Qiang Mao; Huan Zhong; Wan-Li Liang; Jin Dai; Rui-Ting Huang; Yi-Di Wang; Di-Yang Sun; Kai Tang; Long-Fei Xia; Hai-Biao Gong; Yi-Fang Li; Wan-Yang Sun; et al. (Journal of Natural Medicines, 2026)

Contrasting interactions of Cd, Cu, and Zn during uptake and efflux in Daphnia magna - Yun Wu; Rong Yan; Jialin He; Yajing Kou; Chenchen Zuo; Wei Zhang (Ecotoxicology, 2026)

Research on Simulation Optimization of ART Charging Strategies in Automated Container Terminals - Hongqi Huang; Rong Yang; Mengjie He; Nenad Zrnic; Ning Zhao; Xiangwei Liu (Journal of Marine Science and Engineering, 2026)
In automated container terminals, Autonomous Rail-guided Transporters (ARTs) are responsible for horizontal transportation tasks between quay cranes and yard blocks during unloading operations. Their charging strategies directly affect operational continuity, charging resource utilization, and road traffic load. To improve the consistency between the simulation environment and the actual terminal layout, this study constructs a DXF-based directed traffic network based on the CAD/DXF layout of Tianjin Port Second Container Terminal. A coupled discrete-event simulation model integrating ART operations, charging behavior, and traffic dynamics is developed using SimPy. The study further compares several charging strategies, including threshold charging, conventional opportunity charging, safe opportunity charging, interval charging, and Distance-Aware Interval Charging (DAIC). The results indicate that the conventional opportunity charging strategy suffers from battery depletion failures under continuous unloading task flows due to the absence of mandatory low-battery protection. After introducing a safety threshold, the safe opportunity charging strategy effectively eliminates the risk of battery depletion. Considering comprehensive performance indicators, including operational success rate, task completion time, charging travel distance, charging frequency, minimum State of Charge (SOC), and road congestion level, the 40%/70% interval charging strategy demonstrates strong overall robustness, while the 40%/80% interval charging strategy shows advantages in completion time and charging resource utilization. Both strategies can therefore be regarded as key candidate charging schemes for ART operations in Tianjin Port Second Container Terminal.

Deformation and Reconstruction of Coastal Typhoon Wind Fields in Hangzhou Bay - Li Li; Jiayi Guo; Zhiguo He; Tao Feng; Yuezhang Xia; Honghua Zou; Yaping Zha; Rong Zhou; Ye Zhu; Wenjun Zhu (Journal of Marine Science and Engineering, 2026)
Coastal typhoon deformation plays a critical role in determining typhoon tracks, intensity changes, precipitation and related flooding, storm surges, and typhoon waves, and thus is highly associated with coastal disaster patterns. This study proposes a three-level framework for typhoon wind field modeling through the integration of geometric characterization with physical-informed reconstruction. At its core, an elliptical fitting method is developed based on second-order moments to quantify the structural asymmetries. This geometric fitting method is incorporated into the reconstruction method of Holland–Miyazaki, creating a physically consistent model capable of simulating typhoon deformation processes during landfall. Validation through high-resolution Weather Research and Forecasting (WRF) simulations of Typhoon Chan-hom (2015) demonstrates the framework’s effectiveness, capturing elliptical eyewall deformation with aspect ratios exceeding 1.5, primarily driven by coastal topography and surface friction interactions. The method is further validated through Typhoon Mitag (2019), with mean wind component errors below 1 m/s, the average correlation coefficients surpassing 0.9, and wind direction mean absolute errors largely below 10°. This research provides a practical framework for quantifying and characterizing the wind field deformation during typhoon landfall in coastal regions, thereby supporting ther operational forecasting and disaster reduction in vulnerable coastal regions.

Environmental Factors Drive Neurodegenerative Diseases Through Glutamate Excitotoxicity: A Convergent Mechanistic Pathway - Yulu He; Tingting Yi; Meixin Min; Ke Xu; Huan Lin; Rong Xu; Dan Deng; Xiaoping Xiao (Neuroscience Bulletin, 2026)

Isolation, identification, and disease-protective potential of Pseudomonas monsensis DBFF02 against Saprolegnia infection in grass carp - Guofan Zhang; Kunyan Li; Yuyuan Peng; Simei He; Chen Li; Rong Fan; Jiajie Xie; Linger Qian; Xinran Long; Jiayi Wang; Jiatao Yang; Yanmin He; et al. (Aquaculture, 2026)

Cholesteryl ester accumulation as a biomarker for personalized selection of fertility-preserving therapies in endometrioid endometrial carcinoma - Yijiao He; Shenyi Yin; Wenying Zhao; Yanmin Wang; Danhua Shen; Yi Wang; Jing Geng; Xiaobo Zhang; Ying Yu; Juan Li; Yang He; Jiaxin Li; et al. (Science Bulletin, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Ganoderma lucidum spore lipid extract synergizes with chemotherapy to alleviate tumor progression by enhancing macrophage phagocytosis of dying tumor cells - Guan-Di Xiao; Zi-Xuan Li; Yi-Fang Li; Lei Liang; Cheng Yuan; Wen-Dong Xu; Ju-Yan Liu; Yan-Ping Wu; Rong-Rong He (PharmaNutrition, 2026)

A novel phytoformula targeting lipid peroxidation inhibition attenuates UV-induced skin photoaging - Ling-Ping Wu; Wei Chen; Qian-Pei Lin; Shi-Yun Feng; Jin Dai; Qiong-Yi Zhang; Wen-Yi Chen; Hiroshi Kurihara; Xiao-Min Li; Shu-Hua Ouyang; Yi-Fang Li; Rong-Rong He (PharmaNutrition, 2026)

Continental records of the early Cretaceous OAE1a and mechanisms of carbon cycle perturbation driven by climate-weathering coupling in the Yin'e Basin - Qianghao Liu; Rong Liu; Youyou Huang; Tianxin He (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Indole metabolites produced by Lactobacillus acidophilus impedes bisphenol F- aryl hydrocarbon receptor interaction and ameliorates bisphenol F induced depression-like changes - Miaoyang Hu; Ayiguzaili Manglike; Xiaozhu Li; Jin Wei; Xinyu Lou; Jing Liu; Zhiru Tang; Weiping He; Guixiang Ji; Wenjuan Wang; Tengfei Ma; Rong Gao; et al. (Journal of Hazardous Materials, 2026)

Green derivative synchronous fluorescence spectroscopy approach for rapid quantification of Rhodamine B in food samples - Hong-Jun Liu; Jia-Rong He; Yi-Han Guo; Jia-Lin Li; Wei-Peng Cai; Ping-Ping Wu; Yao-Qun Li (Food Control, 2026)

Optimizing biochar selection for soil amendment: Unraveling the feedstock-texture interplay for enhanced crop performance - Rong Zhang; Zizhen Ma; Linhua Jiang; Wenjie Gao; Hongping He; Heng Yu; Tao Yu; Bo Yang; Chengtun Qu (Bioresource Technology, 2026)

AI-decoded enzymatic blueprints navigate the unknown metabolome - Shu-Xin Cao; Xiang Luo; Yu Bai; Hong-Li Tan; Rong-Rong He (Science China Life Sciences, 2026)

Drying-wetting cycles alter the balance between physical fragmentation and leaching during leaf litter decomposition: a laboratory incubation experiment - Le-Lin Yu; Rui-Jing Chai; Qi-Han Tu; An He; Le-Cheng Ai; Rong Mao (Plant and Soil, 2026)

Host switching and successive subculturing drive adaptive responses in Liriomyza sativae - Yang Gao; Wei He; Ming Zhang; Hai-Nuo Hong; Jin Wang; Ying Zhou; Zeng‑Rong Zhu (Journal of Pest Science, 2026)

A joint optimization method for weight estimation and re-identification based on a cattle back semantic disentanglement model - Yuqi Zhang; Longxiang Li; Hui Kang; Shiyuan Liang; Kai Niu; Yue Rong; Zhiqiang He (Computers and Electronics in Agriculture, 2026)

Distribution and transport of trace organic contaminants from land to the coastal sea - Shi-Jie Lv; Ting Pan; Rui Tang; Jun-Rong Liang; Hui He; Lei Mai (Marine Pollution Bulletin, 2026)

Late-spring vertical profiles in atmospheric water vapor stable isotopes reveal westerlies moisture transport across the Himalaya into the Asian Water Towers - Jing Gao; Jingjing Yang; Gebanruo Chen; Yigang Liu; Xiaowei Niu; Aibin Zhao; Yilong Wang; Rong Cai; Zeqing He; Taihua Zhang; Tandong Yao (Science Bulletin, 2026)

A germline-specific vesicular structure licenses mRNA activation during spermiogenesis and is hijacked in gastric cancer - Mingxi Liu; Zerui Wang; Yinuo Li; Qingsong Xie; Zhuang Xiao; Xuezhi He; Guanxiong Wang; Yang Gao; Yini Zhang; Lin Zheng; Xun Xia; Lujie Chen; et al. (Science Bulletin, 2026)

Microcrystalline cellulose modified with ethylenediamine disuccinate via ring-opening grafting reaction: A novel and efficient biosorbent for heavy metal ions - Ziyi Wang; Wenqi Wang; Lang Zhao; Min He; Rong Li (Carbohydrate Polymers, 2026)

Insights to how tubular pore biochar affects anaerobic digestion of waste activated sludge: Performances and mechanisms - Ze-Mu Li; Ai-Hua Li; Qing-Bin Meng; Cong-Cong Tang; Qian Li; Ai-Juan Zhou; Wenzong Liu; Zhi-Ling Li; Zhang-Wei He; Rong Chen (Bioresource Technology, 2026)

The causal relationship between polycystic ovary syndrome and structural changes in brain: a Mendelian randomization study - Han Yang; Wei Xie; Camilo Alberto Pinzon Galvis; Si Huang; Xu He; Si-yi Yu; Qing You; Fan-rong Liang; Zhi-yong Xiao; Ning Li (Brain Imaging and Behavior, 2026)

Grass carp TMEM33 promotes GCRV replication by targeting MAVS for degradation and suppressing host antiviral immune response - Qian Wang; Zichao Peng; Rong Deng; Yongming Li; Zuoyan Zhu; Yaping Wang; Libo He; Jing Lu (Marine Life Science & Technology, 2026)

Bridging cortical intentions: brain–computer interfaces for spinal cord injury recovery - Xuantao Hu; Jiale He; Na Li; Jian Mo; Senyu Yao; Yubao Lu; Mudan Huang; Pan Jiang; Mao Pang; Lei He; Jin Gong; Zifeng Liu; et al. (Science Bulletin, 2026)

Enrichment of organophosphate esters in the surface microlayer of a subtropical urban lake: Phase partitioning dynamics and air-water exchange implications - Mingfu Lin; Tao He; Rong Wang; Lixiang Zhong; Menghuan Zhang; Jun Wang; Yumei Huang (Journal of Hazardous Materials, 2026)

Nickel(II)-induced charge separation modulating in Ni-coordinated covalent organic framework for boosting dual-pathway hydrogen peroxide production - Qinfeng Rong; Junxia Qin; Shuying Li; Zhiling Huang; Sijing He (Journal of Environmental Chemical Engineering, 2026)

The effects of water depth, temperature and seasonal water-column overturning on sediment-derived odorous volatile organic compounds of a ladder-step reservoir, Yiwu, China - Bo Gao; Junyu Ma; Jiahe Wang; Hongbin Zhu; Yangkang Fang; Qinggang Gong; Zhizheng Luo; Yi He; Rong Zhang; Cancan Jiang; Yongzhi Chi; Yanghui Xiong; et al. (Journal of Environmental Chemical Engineering, 2026)

Soil hydrology affected by crushed rock content modulates the alpine ecological restoration: implications from soil reconstruction - Ruixuan Li; Jianfei Wang; Chengjing He; Rong Sun; Qing Zhang; Qinghua Liu; Xueyong Pang (Journal of Environmental Management, 2026)

Stochastic and deterministic processes shape microbiota and flavors of strong-flavor Daqu made from different wheat varieties during fermentation - Kangjie Yu; Rong Yang; Huiling Huang; Shuanghui Wang; Chaojiu He; Liya Huang; Yi Ma; Dejun Han (Food Research International, 2026)

Gelation behavior of egg white protein modulated by polysaccharide charge characteristics: Molecular mechanisms from hydration perspective - Can Wu; Rong He; Xinyu Liu; Qiuyue Hou; Bing Cui; Bin Zhou (Food Chemistry, 2026)

Multi-objective optimization of rice production and environmental sustainability under climate change in the Yangtze River Delta: A DNDC-random forest framework approach - Shuoshuo Liang; Ping He; Qingnan Chu; Wentian He; Ruochen Li; Xinpeng Xu; Rong Jiang; Shuang Liu; Linkui Cao; Zhimin Sha (Field Crops Research, 2026)

Towards sustainable potato production in China: Optimizing nitrogen and water management with 5R strategies - Zhaolong Pan; Rong Jiang; Daijia Fan; Daping Song; Hanyou Xie; Xiya Wang; Wei Zhou; Ping He; Wentian He (European Journal of Agronomy, 2026)

Dynamic responses and failure modes of ultra-high strength alkali-activated concrete slab under impact load - Haiyu He; Lihua Wu; Xudong Zhi; Feng Fan; Gang Ma; Rong Zhang (Engineering Structures, 2026)

Integrative bulk and single-cell transcriptomic analyses reveal nucleus pulposus cell fibrosis as a therapeutic target in intervertebral disc degeneration and identify quercetin as a potential antifibrotic agent - Peilin He; Jun Tao; Guo Li; Ye Mu; Rong Hu; Junming Chen; Wenqi Feng (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Design of sequential strongly convex programming algorithm for reentry trajectory planning - Yutang Li; Di Zhou; Zhen He; Songzhou Li; Siyuan Li; ChaoRan Yan; Rong Huang (Advances in Space Research, 2026)

Lengthening vegetation carbon turnover time across China’s forests - Rong Ge; Xiaoli Ren; Honglin He; Guirui Yu; Li Zhang; Qian Xu; Mengyu Zhang; Shilong Piao; Kailiang Yu; Mathew Williams; Xiaobo Zhu; Shiyong Yu; et al. (Science Bulletin, 2026)

Applying semi-supervised learning algorithms in real-environment solid waste classification - Dong–Ying Lan; Pin–Jing He; Hui–Huang Zou; Rong–Rong Kan; Yi Wang; Fan Lü; Hua Zhang (Resources, Conservation and Recycling, 2026)

Molten NaOH-KOH assisted thermo-chemical detoxification of waste salt containing hazardous organics - Hongping He; Yong Cheng; Linhua Jiang; Youcai Zhao; Dongjie Niu; Xunchang Fei; Rong Zhang; Shijin Dai (Process Safety and Environmental Protection, 2026)

Metabolic depression drives discontinuous gas exchange in diapause pupae of Sericinus montelus (Lepidoptera: Papilionidae): a seasonal adaptation strategy - Quan-Hong Xiao; Rong-Wei Wu; Zhe He; Dao-Hong Zhu (Journal of Insect Physiology, 2026)

A high-performance polymer-modified bentonite liner for sustainable landfills: from systematic optimization to field validation - Wei Yang; Rong Zhou; Yifei He; Xueying Liu; Mengjian Ren; Anna Lushnikova (Journal of Environmental Management, 2026)

Microwave treatment enhances brown rice edible quality: Deciphering moisture content-driven modulation of microstructure, moisture distribution and starch properties - Yang Yu; Jiayu Zhang; Dan Ouyang; Rong He; Kai Huang; Shangyuan Sang; Yanan Liu; Jiali Xing; Ying Wan; Xiaohu Luo (Journal of Cereal Science, 2026)

Monodisperse lutetium-177-labeled poly(lactic acid) microspheres for radioembolization therapy of hepatocellular carcinoma - Qing-Rong Jiang; Ping He; Ling-Yun Guo; Qi-Yi Mo; Xing-Long Zhou; Wei Wang; Zhuang Liu; Rui Xie; Da-Wei Pan; Wen-Jie Zhang; Xiao-Jie Ju; Liang-Yin Chu (Chemical Engineering Journal, 2026)

Building a sandwich heterojunction TiO2/TiN/h-BN to improve artificial photosynthesis toward alcohols - Changwan Zhuang; Chenpu He; Jianhua Wang; Noushad Ullah; Rong Nie; Qiaolan Zhang; Zonglin Yi; Huanwang Jing (Chemical Engineering Journal, 2026)

Counteracting the Trojan horse effect: Dual-light-driven biochar/LaFeO3/TiO2 for synchronous ARGs-inactivation and phosphorus-adsorption - Bei Yang; Peifang Wang; Hao Liu; Lisha Wang; Shiying He; ShaoPeng Rong; Zhenkun Ma; Yueqin Cheng; Yanfang Feng; Lihong Xue (Chemical Engineering Journal, 2026)

The emerging role of fatty acids as key bioactive components of Ganoderma lucidum spore oil in alleviating tumor progression - Qi-Jun Chen; Zi-Xuan Li; Guo-Cai Wang; Ting Xie; Guan-Di Xiao; Hui Xu; Jing Li; Xiang Luo; Yi-Fang Li; Lei Liang; Ju-Yan Liu; Yan-Ping Wu; et al. (Journal of Natural Medicines, 2026)

Advances in natural biomacromolecule-based Janus materials: preparation, applications and future prospects in food science - Ying Xu; Xuan Tao; Liubin Li; Yao Chen; Rong He; Xingrong Ju; Zhigao Wang (Critical Reviews in Food Science and Nutrition, 2026)

Integrated sensing and communication for lettuce water-status monitoring - Ning Yang; Rong Du; Ni Yu; Wanting He; Zhenzhong Wang; Xiao Du; Si Chen (Computers and Electronics in Agriculture, 2026)

Natural functional sweet-tasting molecules from food-medicine plants: an updated review of their sources and classifications, sensory evaluation, mechanism of sweet taste transduction and safety - Rong Li; Kangmeng Sun; Jiayi Liang; Xinyu Luan; Xinyuan Sun; Peigen Xiao; Chunnian He (Trends in Food Science & Technology, 2026)

Physical properties as the key bridge from structure-activity relationship to AI-guided rational design of food-derived bioactive peptides: A systematic review - Huizhen Xing; Huimin Dong; Chengzhi Guo; Zhigao Wang; Rong He (Trends in Food Science & Technology, 2026)

Mechanisms of failure and permeability evolution in gas-bearing strata under tunnel-induced stress paths - Jiafeng Tan; Deyi Jiang; Rong Liu; Yi He; Jinyang Fan; Jianyu Liang; Cheng Qian; Hanlin He; Hong Zheng (Transportation Geotechnics, 2026)

Reinforcement learning assisted sparse population coevolutionary algorithm for multi-component spectral feature selection - Panpan Zhang; Yilan He; Jing Rong; Ye Tian; Yajie Zhang; Shangshang Yang; Xingyi Zhang (Swarm and Evolutionary Computation, 2026)

A fast powerful X-ray transient from possible tidal disruption of a white dwarf - Dongyue Li; Wenda Zhang; Jun Yang; Jin-Hong Chen; Weimin Yuan; Huaqing Cheng; Fan Xu; Xinwen Shu; Rong-Feng Shen; Ning Jiang; Jiazheng Zhu; Chang Zhou; et al. (Science Bulletin, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Sulfur-doped TiO₂ with enhanced photocatalytic CO₂ reduction performance toward CO - Die He; Hui Ping Zhao; Hua Peng Guo; Rong Chen; Qiong Liu (Journal of Environmental Chemical Engineering, 2026)

Exploring different modification methods of biochar for Se(IV) removal from water: Synergistic effect of adsorption and reduction - Yu-Ying Wang; Juan Yu; Rong-Ting Jiao; Li-Li He; Yao Su; Yun-Long Wang; Hui Lin; Yan Shi; Hao-Hao Lyu (Journal of Contaminant Hydrology, 2026)

Rice bran protein-based self-propelled nanomotors for targeted delivery of dihydroquercetin: A food-grade nano-system for anti-atherosclerosis - Huizhen Xing; Huimin Dong; Chengzhi Guo; Yucheng Zou; Zhigao Wang; Xiaohu Luo; Rong He (Food Research International, 2026)

Deciphering the relationship between post-fire ground deformation and debris flow activity influenced by lithological heterogeneity: Insights from a comparative analysis in southwestern China - Yonghao Zhou; Xueqiang Gong; Xiewen Hu; Kun He; Jiangkun Rong; Ruichen Zhou (Engineering Geology, 2026)

Ion−dipole−induced high stability of acidic DESs for efficient extractive and oxidative desulfurization - Dongao Zhu; Jie Yin; Siyi Han; Rong Zhang; Chunyan Dai; Jing He; Hongping Li; Wenshuai Zhu; Huaming Li; Wei Jiang (Chemical Engineering Journal, 2026)

Mechanoluminescent Janus architecture for stimulus-responsive photodynamic therapy - Rong-Kai Du; Xu-Lin He; Qing-Qing Jin; Hong Liang; Tai-Zhong Xiao; Lei Zhong; Jun-Cheng Zhang; Tian-Ying Sun; Lei Zhou; Ming-Mei Wu (Chemical Engineering Journal, 2026)

Robust copper/mesoporous silica catalyst for efficient furfural hydrogenation to furfuryl alcohol - Xin-Yu Xiao; Jie Zhang; Rong Wang; Qi Wang; Hai-Song Li; Jing-He Yang (Biomass and Bioenergy, 2026)

Unveiling the genetic architecture of stripe rust resistance in wheat: a region-specific GWAS in Xinjiang, China - Feifei Zhang; Rong Wang; Wenjuan Jiao; Wanlong He; Yuzhe Zhang; Na Sun; Bin Bai; Kemei Li; Yukun Cheng; Hongwei Geng (Theoretical and Applied Genetics, 2026)

Effect of long-term cultivation on ground arthropod diversity and network stability in desert agricultural ecosystems - Yongzhen Wang; Yilin Feng; Jialong Ren; Zhibin He; Jiliang Liu; Wenzhi Zhao; Rong Yang (Plant and Soil, 2026)

Plant-soil feedback driven by root-associated fungal communities accelerates the secondary succession of bare saline-alkaline grassland patches - Xiaona Zheng; Yuhong Yin; Dan Yang; Jingjuan Bi; Wenlong He; Siya Li; Xiao Liang; Jigui Chen; Rong Wang; Zhiying Guo; Xing Li; Tao Zhang; et al. (Plant and Soil, 2026)

5-Methoxyflavone inhibits the proliferation of lung adenocarcinoma cells through PI3K/AKT/GSK3β/β-catenin/Cyclin D1 signaling and attenuates chemoresistance and PD-L1 expression - Yan Zhao; Yiwen Cui; Rong Li; Mingyong Li; Zhiwei He; Yingying Hu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

A weighted EEG-fNIRS integration model enhances cortical representation of inter-muscular coordination - Xinqi He; Rong Song (Medical & Biological Engineering & Computing, 2026)

Effects of Straw Returning on Physicochemical Properties and Microbial Characteristics of Agricultural Soil - Tantan Zhang; Shiqiang Ge; Rong Gan; Siyuan He; Fuyuan Duan; Lin Li (Current Microbiology, 2026)

Preparation and application of the transistor based on D-A isoindigo copolymer/GR blend for the detection of circular tumor cell - Caiyuan Liao; Fayu Wang; Long Fang; Rong Zou; Yaping Wang; Gang Chang; Hanping He (Analytica Chimica Acta, 2026)

Juvenile-Onset Cerebrotendinous Xanthomatosis with Novel Compound Heterozygous CYP27A1 Mutations: Case Series and Literature Review - Kefang Du; Chunrong Wang; Linlin Wan; Zhao Chen; Hongyu Yuan; Qian Jiang; Xiao Dong; Daji Chen; Riwei Ouyang; Xiafei Long; Xiaokang Wu; Xinying Xiao; et al. (The Cerebellum, 2026)

CRODNet: Cascaded learning network for contactless top-view cattle rotated object detection - Hui Kang; Yuqi Zhang; Longxiang Li; Chunyang Li; Sen Wang; Kai Niu; Yue Rong; Zhiqiang He (Computers and Electronics in Agriculture, 2026)

Widespread incongruence in the phylogenomics of the ancient land plant lineage, Selaginellaceae (lycophytes) - Jing Zhao; Hong Yu; Carl J. Rothfels; Jian-Jun Yang; Shao-Li Fang; Zhao-Rong He; Li-Bing Zhang; Xin-Mao Zhou (Molecular Phylogenetics and Evolution, 2026)

Efficient low-temperature NO reduction via constructing Cu+ −O−Co3+ sites to enhance lattice oxygen release and CO adsorption - He Wang; Ye Zhu; Wei Wang; Xiaoqing Dang; Yufei Zhang; Dandan Zhu; Rong Li; Dongjie Yan; Qian Ma; Jiaxin Qu; Jiaquan Zhang; Yu Huang (Journal of Hazardous Materials, 2026)

Cerium isotopic compositions of deep-sea sediments: implications for geochemical behavior of rare earth elements in the pelagic seafloor - Ganglan Zhang; Jianghao Bai; Mingyu Zhao; Pengcong Wang; Yangtao Zhu; Jun Cao; Hao Wu; Rong Xu; Gaowen He; Gangjian Wei; Yinan Deng (Geochimica et Cosmochimica Acta, 2026)

Recrystallization and orientation competition via hot extrusion in n-type Bi2Te3 alloys for advanced power generator - Tao Xiong; Hailong He; Ge Tian; Yi Wu; Youqun Li; Chunping Niu; Feng Jiang; Chenhao Ren; Mingzhe Rong (Chemical Engineering Journal, 2026)

Performance stability and recovery strategy of pre-denitrification coupled partial nitritation/anammox-hydroxyapatite processes for enhanced organic matter, nitrogen and phosphorus removal from swine manure digestate - Yunzhi Qian; Shilong He; Fuqiang Chen; Junhao Shen; Chao Rong; Yan Guo; Yu Qin; Yu-You Li (Bioresource Technology, 2026)

Screening of Fecal Bacteroides Strains and Discovery of Bacteroides eggerthii S13-F8 with Protective Effects Against Chemotherapy-Induced Diarrhea - Yi Zhao; Zhengqun Dai; Yanmei Lang; Rui Li; Hongyu Zheng; Jiajia Mi; Xiu He; Jin Liu; Rong Xiang; Xueran Mei; Yang Liu; Yantang Wang; et al. (Probiotics and Antimicrobial Proteins, 2026)

miR‑16‑5p Protects RGCs Against Retinal Ischemia–Reperfusion Injury by Modulating Astrocyte-Mediated Neuroinflammation Through the Wip1/NF-κB Signaling Axis - Wen Hu; Wenjing He; Guangyi Huang; Yuchen Zhou; Yue Li; Shuya Tao; Daizai Lei; Fen Tang; Ningning Tang; Li Jiang; Qiangqiang Lan; Hui Huang; et al. (Molecular Neurobiology, 2026)

Effects of green manure mulching on the trophic structure of soil fauna in desert agricultural ecosystems of northwestern China - Yongzhen Wang; Zhibin He; Jiliang Liu; Yilin Feng; Jialong Ren; Wenzhi Zhao; Rong Yang (Applied Soil Ecology, 2026)

Cu–N4 active site sensing platform for point-of-care colorimetric detection of environmental organophosphorus pesticide - Rong Huang; Zhong Dong; Wanyi Zhang; Zhenggang Xue; Dongmei Deng; Wei Wang; Yuanyuan Li; Haibo He; Liqiang Luo (Analytica Chimica Acta, 2026)

Regulatory mechanisms of total phosphorus on N2O concentrations: A case study of Dongting lake - Jie Liang; Yi Li; Weixiang Li; Ziqian Zhu; Xiang Gao; Ran Du; Lan Lu; Jing He; Chaozhong Tan; Rong Wu; Jikai Liao (Water Research, 2025)

State-selective engineering in luminescent metal-organic frameworks: Ligand-to-ligand charge transfer activates superior photocatalytic sterilization in Wei River - Liang Qiu; Yajie Zhang; Baiyu Wu; Wenqiong Liu; Yiwen Xie; Jing He; Kerang Huang; Jianlong Wang; Rong Wang (Journal of Hazardous Materials, 2025)

Acoustic emission-based damage assessment and failure mechanism analysis on CFST columns with different joint configurations under compression-bending loads - Enchao Rong; Junfu He; Liqiang Tang; Kaizhong Xie; Yanjun Chang (Engineering Structures, 2025)

A comprehensive interpretation of thermochronological data in the Hengduan Mountains with tectonic implications - Junqing He; Rong Yang; Sean D. Willett; Maria Giuditta Fellin; Yunpeng Wu; Katrina Gelwick; Xuhua Shi; Colin Maden (Earth-Science Reviews, 2025)

Emerging trends in anticoagulation therapy: a bibliometric analysis of DOACs and endogenous coagulation pathway inhibitors - Zhe Zhu; Rong Huang; Hongli He; Rong Zhao; Xirui Li; Fangyan He; Dan Luo (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Biocontrol Effects and Potential Defence Mechanism of Bacillus velezensis JS6-1 Against Fusarium solani-Induced Postharvest Rots in Muskmelon - Yafang He; Jiayi Wei; Fushuang Chen; Ning Wang; Yajie Han; Zifei Wu; Xingwen Wang; Faqiang Zhan; Yingwu Shi; Rong Yang; Huifang Bao (Current Microbiology, 2025)

Investigation of the Shallow Structure of the Hami Basin Northern Margin Fault Using Comprehensive Geophysical Methods - Guang-hong Ju; Xiao-dong He; Rong-ying Zheng; Yan-ling Liu; Jun-qi Duan; Jun Shen; Zhi-tao Gao (Applied Geophysics, 2025)

Concentration-dependent visual SO2 detection from trace to pure in a zirconium MOF - Guang-Rui Si; Xiang-Jing Kong; Lin-Hua Xie; You-Tuo Zhang; Tao He; Jian-Rong Li (Science Bulletin, 2025)

Biosynthetic rule-guided theoretical chemical space mapping strategy for enhanced analysis of plant metabolomes: application to the geographical profiling of goji berry - Wan-Yang Sun; Zhi-Hui Luo; Jie-Qi Cai; Qian Guo; Guo-Tao Chen; Guo-Dong Chen; Dan Hu; Hai-Guang Gong; Xue Li; Wei Bi; Ying Wang; Kwok-Fai So; et al. (Science Bulletin, 2025)

Fracture evolution from micropore changes to macro failure of coal samples with static-dynamic loads based on dislocation and energy theory - Yuchu Cai; Shugang Li; Xiangguo Kong; Zhihao Rong; Di He (Physics and Chemistry of the Earth, Parts A/B/C, 2025)

Morphology and nutrient content of bamboo rhizomes: Responses to enclosure succession in a Phyllostachys edulis forest in Wuyi Mountains, China - Xing Cai; Rui Cheng; Zhenhua Chen; Jiannan Lin; Min Wu; Jiaying Liu; Jihong Xiao; Yuchen Lin; Lingyan Chen; Yirong Zhang; Jundong Rong; Tianyou He; et al. (Forest Ecology and Management, 2025)

Sustainable bipolar membranes with three-dimensional flower-like spherical MgAl-layered double hydroxides doped quaternized chitosan for accelerated water dissociation and durability - Ming Li; Jinyun Xu; Hongze Li; Xiaoqing Wang; Shijie Shang; Xiaoyan Wang; Sijia He; Yanyan Ji; Li Yang; Rong Kuang; Chenxin Hu; Wenju Zhu; et al. (Desalination, 2025)

Electric field-induced gradient polyanionic hydrogel electrolytes with zinc-ion selective transport for stable zinc-ion batteries - Dan Rong; Shujun Zou; Yan Wu; Sijing He; Qinfeng Rong (Chemical Engineering Journal, 2025)

Electrochemical and photoelectrochemical CO2 reduction to hydrocarbons by a copper-based molecular catalyst - Zhibing Wen; Rong Zhang; Yong Zhu; Hua Gao; Ran Zhao; Zhi Chen; Siyao Wang; Shuanglin He; Ya-Qiong Zhang; Rong-Zhen Liao; Fei Li (Chemical Engineering Journal, 2025)

Novel insights to the synergistic effects of magnetic biochar in anaerobic digestion while treating synthetic organic wastewater for biomethane recovery - Zhang-Wei He; Yuan-Long Jia; Cong-Cong Tang; Ai-Juan Zhou; Wenzong Liu; Yong-Xiang Ren; Aijie Wang; Rong Chen (Chemical Engineering Journal, 2025)

A fungal polysaccharide from Trametes orientalis: Structural elucidation and multifaceted antitumor mechanisms via metastasis, angiogenesis, and immunomodulation - Wenrui He; Haojing Jiang; Mingming Rong; Xinxing Li; Jing Xu; Yuanqiang Guo (Carbohydrate Polymers, 2025)

Establishment of regeneration and CRISPR/Cas9-mediated genetic transformation systems in Impatiens walleriana - Huang Deng; Yulu Wu; Shanman Li; Baiyang He; Yuteng Xue; Shunming Zhang; Xue Hu; Yu Zhou; Jiwei Wang; Yuhang Wang; Songtao He; Yuhong Rong; et al. (Plant Cell, Tissue and Organ Culture (PCTOC), 2025)

Exploring the dual role of anti-nutritional factors in soybeans: a comprehensive analysis of health risks and benefits - Dakai Di; Shudong He; Rong Zhang; Kuan Gao; Min Qiu; Xingjiang Li; Hanju Sun; Sophia Xue; John Shi (Critical Reviews in Food Science and Nutrition, 2025)

Simulating the multiple effects of a diatom bloom on metal bioaccumulation in clams - Weiyi He; Fengjie Liu; Minwei Xie; Rong Chen; Qiao-Guo Tan (Marine Pollution Bulletin, 2025)

Crop diversification improves productivity and soil health by regulating fungal diversity - Rui Li; Zhibin He; Peng He; Rong Yang; Dengke Ma; Yuan Li; Yangzhou Xiang; Weihao Sun; Xi Zhu; Zhixin Zhang (Soil and Tillage Research, 2025)

Navigating the lunar frontier: one hundred landing sites at the south pole for future mission challenges - Yongjiu Feng; Pengshuo Li; Haoteng Li; Yan Liu; Mengrong Xi; Rong Wang; Shurui Chen; Panli Tang; Yuze Cao; Qian Huang; Qionghua You; Shijie Liu; et al. (Science Bulletin, 2025)

Selective flotation separation of smithsonite and calcite using sodium dodecyl phosphonate as a collector: Flotation performance and adsorption characteristics - Zehang Guo; Haiyang He; Peilun Shen; Rong Peng; Haiyun Xie; Dianwen Liu (Minerals Engineering, 2025)

Haloxylon ammodendron plantations: enhancing multi-trophic arthropod diversity and soil multifunctionality in arid deserts - Jialong Ren; Yongzhen Wang; Xiaogan Zhou; Wenzhi Zhao; Zhibin He; Rong Yang; Weidong Xin; Wei Ren; Chengchen Pan; Jiliang Liu (Journal of Environmental Management, 2025)

Hydrogen-rich reduction coupled with wet leaching for the conversion of spent SCR catalysts into carbide solid solutions - Rong Mu; Zepeng Lv; Shaolong Li; Jilin He; Jianxun Song (Journal of Environmental Chemical Engineering, 2025)

Enhancing ethanol tolerance and metabolic activity of Saccharomyces cerevisiae during Rice fermentation by fixed-frequency ultrasound - Jing Hao; Mengyuan Yang; Mokhtar Dabbour; Benjamin Kumah Mintah; Chunhua Dai; Rong Zhang; Zhaoli Zhang; Haile Ma; Ronghai He (Food Research International, 2025)

Multi-objective optimization of food, energy, and carbon for vertical agrivoltaic system on building façades - Yijun Lu; Chun Liang Tan; Yang He; Filip Biljecki; Stephen En Rong Tay; Siu-Kit Lau (Energy and Buildings, 2025)

GO-enhanced polyurethane phase change materials with triple dynamic bonds: Oxime-urethane, coordination and hydrogen bonds - Rong Huang; Fu Zhao; Yongsheng Li; Zhuoni Jiang; Fangfang He; Kai Zhang; Zhengguo Chen; Guansong He; Wenbin Yang (Chemical Engineering Journal, 2025)

FT-ICR MS and viral metagenomics reveal distinct mechanisms of lysogenic and lytic phage-driven DOM transformations in wastewater at formula-levels - Qi Wang; Jieqi Tian; Rong Zhang; Pengcheng Yan; Yali Niu; Guodong Zhang; Qiuling Ma; Jian Zhou; Ruigang Wang; He Guo; Tiecheng Wang (Chemical Engineering Journal, 2025)

Applications and challenges of modified algal biochar in environmental remediation - Yan Sun; Chunxiao Hao; Yongjie Wang; Huan Zhong; Song Zhou; Han Meng; Huan He; Pei Lei; Nan Rong (Chemical Engineering Journal, 2025)

Impact of Ca supplement to the single-stage partial nitritation/anammox-hydroxyapatite process in treating swine manure digestate: deterioration mechanism and recovery strategy - Yunzhi Qian; Shilong He; Chao Rong; Yan Guo; Fuqiang Chen; Junhao Shen; Yu Qin; Yu-You Li (Chemical Engineering Journal, 2025)

Geniposide protects against cerebral ischemic injury by targeting SOX2/RIPK1 axis - Xiaogang He; Yi Zhang; Chunyang Xu; Rong Zhang; Ya Li (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Prediction of Lithofacies and Three-Dimensional Geological Modeling Based on CNN-LSTM Spatiotemporal Networks - Qianghao Liu; Rong Liu; Tianxin He; Haoran Zhang (Mathematical Geosciences, 2025)

Computational insights and activity evaluation of novel SHP-2 inhibitors for targeting type 2 diabetes mellitus - Rong Liu; Liang Zou; Maoqi Wang; Yueyue He; Mao Shu (Molecular Diversity, 2025)

Radionuclide tracers reveal seasonal dynamics of particle-associated pollutants in the Jiulong Jiang Estuary, a subtropical tidal estuary - Dekun Huang; Jieran Zhang; Rong He; Fule Zhang; Qiangqiang Zhong; Li Bin; Tao Yu (Marine Pollution Bulletin, 2025)

Biofilm community structure and loading effect of netted cages for offshore aquaculture in the Western Yellow Sea - Ming-Shan Sun; Chun-Wei Bi; Liu-Yi Huang; Rong-Ping Liu; Xin-Xing You; Shu-Yue He (Biosystems Engineering, 2025)

Ten eudesmane sesquiterpenoids from Dobinea delavayi and their antimalarial and lipid-lowering activities - Wei Chen; Li-Tian Dong; Pei-Mi He; Wei-Juan Zu; Yi-Ling Yang; Rong Liu; Bei Jiang; Chao-Jiang Xiao (Phytochemistry, 2025)

Inhalation exposure to cationic nanoplastic induces ferroptosis in the lung by perturbing core circadian transcription factors Bmal1 - Yanliang Wu; Yongrong Yao; Chunyang Wu; Rong He; Zeqian Huang; Chaofeng Zhang (Journal of Hazardous Materials, 2025)

Microbial electrotrophs-driven molecular transformations of dissolved organic matter in paddy soil - Rong Tang; Xiaoshan Luo; Wenjie He; Xixi Cai; Lingyan Huang; Lihua Zhou; Yong Yuan (Journal of Environmental Management, 2025)

Electron beam irradiation inhibits high-moisture rice quality deterioration during storage - Dongmin Li; Jiali Xing; Pei Wang; Li Wang; Yuwei Zhang; Rong He; Dan Ouyang; Ying Wan; Xiaohu Luo (Journal of Cereal Science, 2025)

Effects of the interior conductivity on Mercury's field-aligned currents - Z. Shi; S. Fatemi; Z.J. Rong; F. He; Y. Wei (Icarus, 2025)

Hydro-mechanical and homogenization behaviour of GMZ bentonite pellets/block assemblies upon hydration - Zhang-Rong Liu; Wei-Min Ye; He-Hua Zhu; Yong-Gui Chen; Qiong Wang (Geomechanics for Energy and the Environment, 2025)

Hydrothermal carbonate chimney event from yin’ e basin: Mineralogy, geochemistry, and mode of evolution - Tianxin He; Rong Liu; Qianghao Liu; Hongliang Dang; Xu Wang (Geochemistry, 2025)

Radionuclides and heavy metals in surface sediments of the Bering and Chukchi Seas: distribution, source identification, and risk assessment - Jing Lin; Qiangqiang Zhong; Rong He; Fule Zhang; Hao Wang; Liang Wang; Dekun Huang; Tao Yu (Continental Shelf Research, 2025)

Unraveling the effect of sorbitol on Cu-based catalysts for the continuous hydrogenation of CO2-derived ethylene carbonate to methanol and ethylene glycol - Tong-Yang Song; Ji-Zheng Zhang; Jun He; Xian-Lang Chen; Xin-Yuan Huang; Ai-Ping Jia; Xiaohong Li; Rong-Rong Li; Ji-Qing Lu (Chemical Engineering Journal, 2025)

Study on the field-scale bacterial growth dynamics and ecological effects of microbial dust suppression - Haoran Wang; Yi He; Rong Liu; Jie Chen; Yongjiang Wen; Kunyu Yan; Yong Cao (Chemical Engineering Journal, 2025)

A Co(III)-dipyrazolate framework for atmospheric CO2 photoreduction - Yingjie Wang; Xiang-Jing Kong; Guang-Rui Si; Tao He; Da-Yu Chen; Jian-Yu Zhang; Na Xing; A-Wu Zhou; Jian-Rong Li (Chemical Engineering Journal, 2025)

Unraveling the diversity of bile acid modifications by integrative mass spectrometry approaches - Nan Xing; Yu-Fei Wang; Xue Ding; Hong-Li Tan; Yi-Fang Li; Guo-Xiang Sun; Rong-Rong He; Wan-Yang Sun (Science China Life Sciences, 2025)

Quorum-sensing Inhibitory Activity of Xanthones from Hypericum Curvisepalum N. Robson Against Chromobacterium Violaceum - Hong Zeng; Qiu-Ying He; Sheng-Qiang Yang; Xiao-Lian Wei; Jia-Zi Luo; Jing-Kai Zhou; Rong-Bing Fu; Li-Ping Teng; Zhong-Bo Zhou (Current Microbiology, 2025)

Front margin tectonic deformation characteristics of the Xu–Su arc tectonic belt and its tectonic implications - Rong-ying Zheng; Yun-sheng Yao; Jun Shen; Hao-yuan He; Chun-shan Guo; Xiao-hui Yu; Xun-ye Dai; Lu-wei Li; Xuan-kai Jiao; Zhong-yuan Yu; Zhi-tao Gao (Applied Geophysics, 2025)

Extending the Mutational Spectrum of SYNE1 Ataxia in Chinese Patients - Xin Huang; Zhao Chen; Qian Jiang; Panyan Liu; Yiqing Gong; Lijing Lei; Jia Chen; Chunrong Wang; Linlin Wan; Lang He; Linliu Peng; Rong Qiu; et al. (The Cerebellum, 2025)

Corrigendum to “Bioinformatics identification of shared signaling pathways and core targets linking Benzo[a]pyrene exposure to HCC progression” [Toxicology 514 (2025) 154129] - Yong-Le Li; Rong He; Meng Tang; Jing-Yi Lan; Guo-Yang Liu; Li-He Jiang (Toxicology, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Isolation of pentasaccharide resin glycosides from the whole plants of Ipomoea biflora and their cytotoxic activities - Jin-Ping Gu; Tian-Zi Qi; Dong-Rong Zhu; Xu-Jia He; Su-Peng Guo; Xin Lan; Hong Gu; Jia-Lie Luo; Min Yang; Yu-Cheng Gu; Wen-Li Wang; Guang-Tong Chen; et al. (Phytochemistry, 2025)

Bridging the knowledge gap: From poly(butylene adipate-co-terephthalatebutylene) degradation to CO2-generating mineralization under the synergistic effect of bacteria and fungi - Yue Wang; Qi Liu; Chang-Hong Xie; Ruo-Tong Zhao; Qiu-Xiang Tang; Dong-Fei Han; Yi-Ning Xia; Ji-Xiao Cui; Chang-Rong Yan; Wen-Qing He (Journal of Hazardous Materials, 2025)

Elimination of antibiotic resistance genes and adaptive response of Firmicutes during chicken manure composting - Wei-Li Jia; Ben Wang; Lu-Kai Qiao; Fang-Zhou Gao; Wang-Rong Liu; Liang-Ying He; Guang-Guo Ying (Journal of Hazardous Materials, 2025)

High spatio-temporal resolution CO2 emission estimation model for Chinese crude oil maritime transportation - Zhaojin Yan; Guanghao Yang; Rong He; Kai Shi (Journal of Cleaner Production, 2025)

A novel multi-dimensional viscoelastic mitigation device: Shake table tests and numerical assessment of precast concrete sandwich wall panel structure - Jia-Xuan He; Zhao-Dong Xu; Zhong-Wei Hu; Lian-Yu Zhang; Qiang-Qiang Li; Yao-Rong Dong; Gabriele Milani (Engineering Structures, 2025)

Electroacupuncture may alleviate diabetic neuropathic pain by inhibiting the microglia P2X4R and neuroinflammation - Si-ying Qu; Han-zhi Wang; Qun-qi Hu; Yi-qi Ma; Yu-rong Kang; Li-qian Ma; Xiang Li; Lu-hang Chen; Bo-yu Liu; Xiao-mei Shao; Bo-yi Liu; Jun-ying Du; et al. (Purinergic Signalling, 2025)

The application of nutrients in enhancing drought tolerance of secretohalophyte Atriplex canescens in the desert regions of Northwest China - Jian-jun Kang; Wen-zhi Zhao; Zhi-bin He; Bing Liu; Rong Yang; Hai Zhou; Dong-Mei Zhang (Plant and Soil, 2025)

Discovery of novel potential 11β-HSD1 inhibitors through combining deep learning, molecular modeling, and bio-evaluation - Xiaodie Chen; Liang Zou; Lu Zhang; Jiali Li; Rong Liu; Yueyue He; Mao Shu; Kuilong Huang (Molecular Diversity, 2025)

Polymeric immunoglobulin receptor (pIgR) in cancer progression: a critical role and potential therapeutic target - Shaoju Qian; Yeqing He; Ruixue Li; Panpan Sun; Xingyi Zhang; Lin Pan; Zhishan Xu; Zhiwei Feng; Rong Lian; Lili Yu (Apoptosis, 2025)

ZDHHC13 Reduces the Risk of Ischemic Stroke by Regulating Metabolites - Zhen Wei; Chunshu Rong; Wei He; Xu Wang; Dexi Zhao (Journal of Molecular Neuroscience, 2025)

The prognostic significance of histopathological growth patterns in liver metastases undergoing surgery: a systematic review and meta-analysis - Xiang-Yu Wang; Bo Zhang; Yin-Chen Gu; Mei Yang; Bao-Rui Tao; Rong-Quan Sun; Yi-Tong Li; Zhen-Mei Chen; Sen-Feng Ying; Chen-He Yi; Yan Geng; Rui Zhang; et al. (Clinical & Experimental Metastasis, 2025)

Direct recovery of high-purity uranium from fluoride-containing nuclear wastewater via extraction materials with ensemble Lewis sites and a tandem electrochemical device - Guo Li; Yan Liu; Chi Jiao; Zhengyu Jiang; Juan Zhang; Tao Chen; Tao Lin; Rong He; Wenkun Zhu; Xiangke Wang (Water Research, 2025)

Degradation of biodegradable plastic films in soil: microplastics formation and soil microbial community dynamics - Yue Wang; Run-Hao Bai; Qi Liu; Qiu-Xiang Tang; Chang-Hong Xie; Aurore Richel; Christophe Len; Ji-Xiao Cui; Chang-Rong Yan; Wen-Qing He (Journal of Hazardous Materials, 2025)

Constructing asymmetric D′-A-D" imine covalent organic frameworks to optimize exciton effect and enhance photocatalytic reduction of U(VI) - Yang-Xing He; Xiao-Juan Chen; Rui Zhang; Hao-Xuan He; Cheng-Peng Niu; Cheng-Rong Zhang; Zhi-Hai Peng; Yuan-Jun Cai; Zhen-Wen Zhang; Ru-Ping Liang; Jian-Ding Qiu (Journal of Hazardous Materials, 2025)

Significant insights of CaO2 promoting heavy metal complexes removal during a plasma process - Meiqian Lu; Rong Li; Zichen Wang; Yue Liu; Guodong Zhang; Qiuling Ma; Jian Zhou; He Guo; Tiecheng Wang (Journal of Environmental Management, 2025)

Screening novel anti-inflammatory peptides inhibiting the NLRP3 inflammasome from UHPLC-MS/MS-characterized peptide profiles of cocoa tea protein hydrolysates - Hai-Biao Gong; Chang-Yu Yan; Hui-Er Ye; Shuo-Yan Tan; Shi-Sheng Chen; Jian-Wen Ye; Wan-Yang Sun; Hong-Li Tan; Xiang Luo; Jie Niu; Kun Li; Jing-Hao Wang; et al. (Food Research International, 2025)

Insights from structural characterization for understanding isolation and impact of roasting on allergenic potential of sesame Oleosins - Dakai Di; Rong Zhang; Huimei Li; Min Qiu; Suwei Jiang; Shuizhong Luo; Hanju Sun; Shudong He (Food Chemistry, 2025)

A soil–water retention model with differentiated adsorptive and capillary regimes - Zhang-Rong Liu; Wei-Min Ye; Yu-Jun Cui; He-Hua Zhu; Yong-Gui Chen; Qiong Wang (Computers and Geotechnics, 2025)

Machine learning-driven molecular generation for accelerated screening of high-performance flame retardants in epoxy resin composites - Zhongwei Chen; Chunlei He; Kai Wang; Feng Rong; Long Xiang; Ziwei Zuo; Changliang Wang; Xinyuan Yang; Yong Guo; Juncheng Jiang; Yuan Yu (Chemical Engineering Journal, 2025)

Characteristics of loess landslides under the effects of faults and rivers and their correlations with geological and surficial evolutionary processes - Qi-qi Liu; Wan-li Xie; Hui Yang; Ming Yan; Rong-sen Zhu; Ke Mu; Yi-lun Chang; Shengjie Di; Xiaoliang He; Xiaomin Liu; Ying Zhang (Bulletin of Engineering Geology and the Environment, 2025)

Multi-stage risk assessment and evacuation strategy for promoting urban resilience in the face of bioaerosol leakage under various meteorological information - Zhijian Liu; Yuchen He; Chenxing Hu; Rui Rong; Zhijian Dong; Chenglin Ye; Li Chen (Urban Climate, 2025)

Recent advances in fluorescent aptamer-based sensors for food safety analysis - Ranran Hou; Liuqin He; Xin Ji; Xiaoxiao Rong; Yulong Yin; Xing Li; Yunxuan Weng; Xiaoying Zhao (Trends in Food Science & Technology, 2025)

Bioinformatics identification of shared signaling pathways and core targets linking Benzo[a]pyrene exposure to HCC progression - Yong-Le Li; Rong He; Meng Tang; Jing-Yi Lan; Guo-Yang Liu; Li-He Jiang (Toxicology, 2025)

Size-dependent internalization of polystyrene microplastics as a key factor in macrophages and systemic toxicity - Wei-Qiang Luo; Meng-Ting Cao; Chen-Xuan Sun; Jun-Jian Wang; Meng-Xi Gao; Xue-Rui He; Le-Ning Dang; Yang-Yang Geng; Bing-Yao Li; Jing Li; Zhi-Cheng Shi; Xing-Rong Yan (Journal of Hazardous Materials, 2025)

Methanogenic response of paddy soils exposed to zinc oxide nanoparticles and sulfurized products - Minghao He; Rong Tang; Fengyi Guan; Weijie Peng; Jinrong Lu; Keyi Li; Lihua Zhou; Yujie Wang; Yong Yuan (Journal of Hazardous Materials, 2025)

Assessment of fate of respiratory droplets and effectiveness of different air cleaners during outpatient consultation - Haiyang Liu; Zhijian Liu; Guangpeng Yao; Zhijian Dong; Chuan Jiang; Jingwei Liu; Rui Rong; Junzhou He; Chenxing Hu; Shiyue Li; Zhenyu Liang (Journal of Hazardous Materials, 2025)

Adsorption behavior and mechanism of cadmium, copper, and lead on polylactic acid microplastics exposed to ultraviolet light - Fang Feng; Shutao Wang; Xue He; Xinghua Wang; Jia Huang; Guiming Liu; Sashuang Rong; Shiming Su; Hongyuan yan; Bing Han; Wei Liu (Journal of Environmental Chemical Engineering, 2025)

Bismuth tungstate/graphite carbon nitride composites for efficient photocatalytic reduction of U(VI): Synthesis, performance, and mechanism - Yu-Jia Xiao; Shi Chen; Ping Li; Dong Zhang; Jing-Jing Wang; Hui Dong; Yan-Rong He (Journal of Environmental Chemical Engineering, 2025)

Modulation of surface properties and emulsifying properties of gliadin particles by alkyl gallates: Effects of pH and alkyl chain length - Can Wu; Ziqing Zhao; Rong He; Xinyu Liu; Bing Cui; Yuying Hu; Bin Zhou (Food Research International, 2025)

A novel tin dioxide field effect transistor with PMMAA functionalized organic passivation layer for the detection of the cortisol in saliva - Caiyuan Liao; Rong Zou; Qixin Zhou; Huan-Yu Liu; Song-Mei Liu; Long Fang; Gang Chang; Hanping He (Chemical Engineering Journal, 2025)

Glymphatic Impairment Associated with Neurocognitive Dysfunction in Moyamoya Disease - Chaofan Zeng; Yuanren Zhai; Peicong Ge; Chenglong Liu; Xiaofan Yu; Wei Liu; Junsheng Li; Qiheng He; Xingju Liu; Xun Ye; Qian Zhang; Rong Wang; et al. (Translational Stroke Research, 2025)

Effect of high in-situ asymmetric stress on the brittle failure of the boundary of an underground powerhouse - Ben-Guo He; Shi-Chen Qiu; Xia-Ting Feng; En-Rong Liu; Tao Chen; Shencun Yan (Bulletin of Engineering Geology and the Environment, 2025)

Addressing accuracy challenges in machine learning for debris flow susceptibility: Insights from the Yalong River basin - Zaiyang Ming; Jianqiang Zhang; Haiqing He; Lili Zhang; Rong Chen; Yang Jia (Journal of Mountain Science, 2025)

Integrating straw return and tillage practices to enhance soil organic carbon sequestration in wheat–maize rotation systems in the North China Plain - Hua Han; Daijia Fan; Shuxia Liu; Rong Jiang; Daping Song; Guoyuan Zou; Ping He; Minyu Wang; Wentian He (Agriculture, Ecosystems & Environment, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Recruitment of copiotrophic and autotrophic bacteria by hyperaccumulators enhances nutrient cycling to reclaim degraded soils at abandoned rare earth elements mining sites - Yong-He Han; Xi-Wen Cui; Hai-Yan Wang; Xiao-Bin Lai; Ying Zhu; Jia-Bing Li; Rong-Rong Xie; Yong Zhang; Hong Zhang; Zhibiao Chen (Journal of Hazardous Materials, 2025)

Effect of egg white on the structure and properties of starch in wheat noodles - Jinyi Xu; Shangyuan Sang; Jinye Zhang; Jiali Xing; Rong He; Fuxing Xu; Guanghui Fang; Dan Ouyang; Ying Wan; Xiaohu Luo (Journal of Cereal Science, 2025)

Pyroptosis was suppressed by 20-hydroxyecdysone through Lin28b-mediated let-7d in vascular endothelial cells - Danli Chen; Jianjun Yang; Lingxuan Ren; Zihan Zheng; Zhen Jin; Jiazheng Wen; Jianyu He; Rongcheng Ding; Jianjiang Wang; Rong Lin; Qiang Song (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

SIRT5: a potential target for discovering bioactive natural products - Yuwei Xie; Nali Cai; Xiaohua Liu; Liangliang He; Yiming Ma; Changyu Yan; Juan Liang; Shu-Hua Ouyang; Ao Luo; Yingzhi He; Jun Lu; Dang Ao; et al. (Journal of Natural Medicines, 2025)
Silent information regulator 5 (SIRT5) is the fifth member of the sirtuin family, which is mainly expressed in mitochondrial matrix. SIRT5 plays a key role in metabolism and antioxidant responses, and is an important regulator for maintaining intracellular homeostasis. Given its involvement in multiple cellular processes, dysregulation of SIRT5 activity is associated with a variety of diseases. This review explores the structural characteristics of SIRT5 that influence its substrate specificity, highlights recent research advances, and summarizes its four key enzymatic activities along with their corresponding substrates in disease contexts. We also discuss the natural products that modulate SIRT5 activity and identify potential targets of SIRT5 through virtual docking, which may provide new therapeutic avenues. Although the mechanism of SIRT5 in diseases needs to be further elucidated and deglutathionylation activities are still at an early stage, targeting SIRT5 and its substrates holds significant promise for the development of novel therapeutics. Graphical abstract

Physical contraction strategy for large-scale fabrication of reduced graphene oxide-coated solid phase microextraction fibers - Linlin Wei; Jianyun Sun; Xingguo Wang; Ting Qi; Aiying Song; Rong Liu; Xinghe He (Analytica Chimica Acta, 2025)

Temporal Dynamics of Genetic Diversity in Protected and Unprotected Wild Rice ( Oryza rufipogon ) Populations: Implications for Conservation - Zhi‐Zhou He; Wen‐Wen Shao; Olivier Honnay; Hui Liao; Hao Chen; Jing Liu; Shan‐Shan Dong; Ding Li; Guo‐Zhen Fan; Yao Zhao; Jun Rong; Yan Liu; et al. (Molecular Ecology, 2025)
Genetic diversity is vital for population survival, yet there is a paucity of studies focusing on the effectiveness of establishing protected areas for maintaining the population genetic diversity of threatened plant species. To evaluate the effectiveness of in situ conservation measures, we used simple sequence repeats (SSR) and single nucleotide polymorphisms (SNP) markers to monitor temporal dynamics in genetic diversity of the threatened wild rice Oryza rufipogon in both protected and unprotected populations in China between 2001 and 2020. Unprotected populations tended to have decreased census population sizes ( Nc ) compared to protected populations, although they both showed a reduction in effective population size ( Ne ). While allele diversity and expected heterozygosity remained stable, several populations, especially those without protection, exhibited a significant decrease in observed heterozygosity ( Ho ) and an increase in inbreeding ( F IS ). The level of genetic differentiation between populations did not change over time, but the number of private alleles increased and Ne varied in several populations, indicating the effects of genetic drift. Indicators for temporal trends in Ho , F IS , and Ne revealed that both protected and unprotected populations are facing warnings of declining genetic diversity, although some protected populations remain resilient, reflecting the genetic lag behind Nc change. Overall, these findings highlight the effectiveness of in situ conservation efforts in maintaining population size and genetic diversity, yet we also show the necessity of lasting population dynamics monitoring, using different genetic indicators.

Establishment of different artificial infection method models for grass carp reovirus - Hanyue Wang; Yongming Li; Qian Wang; Bin Gui; Lanjie Liao; Zuoyan Zhu; Yaping Wang; Rong Huang; Libo He (Aquaculture, 2025)

Melittin: A promising therapeutic agent for rheumatoid arthritis treatment - Rong Huang; Xiying He; Qingxin Meng; Guangyu Yan; Kun Dong; Yakai Tian (Toxicon, 2025)

Effects of triclosan on microalgal-bacterial symbiosis system operating in stable phase: Performances and mechanisms - Qiang Chao; Tian-Yang Wang; Cong-Cong Tang; Rong Wang; Zhang-Wei He; Zhi-Hua Li; Yu Tian (Journal of Water Process Engineering, 2025)

Steam-activated biochar for efficient removal of sulfamethoxazole from water: Activation temperature-mediated differences - Shaowen Rong; Yuge He; Liangmeng Ni; Qi Gao; Xin Feng; Shushu Liu; Yanhang Zhong; Yuguo Li; Zhijia Liu (Journal of Water Process Engineering, 2025)

LibRPA: A software package for low-scaling first-principles calculations of random phase approximation electron correlation energy based on numerical atomic orbitals - Rong Shi; Min-Ye Zhang; Peize Lin; Lixin He; Xinguo Ren (Computer Physics Communications, 2025)

Synergistic enhancement of flame retardancy, mechanical properties, dimensional stability, and mold resistance in bamboo via silica mineralization and hydrophobic treatment - Lu He; Gege Bao; Xi Yu; Xiaofeng Zhang; Xiaobei Jin; Zixuan Yu; Rong Zhang; Daochun Qin (Chemical Engineering Journal, 2025)

The diverse sleep structure of mid-day nap in college students - Qin Xiao; Xueqi Sun; Guoxin Zeng; Xin Luo; Qian Jiang; Rong Ren; Xiangdong Tang; Chao He; Zhian Hu; Fenlan Luo; Jie Yan (Sleep and Biological Rhythms, 2025)

Cation Channel TMEM63A Autonomously Facilitates Oligodendrocyte Differentiation at an Early Stage - Yue-Ying Wang; Dan Wu; Yongkun Zhan; Fei Li; Yan-Yu Zang; Xiao-Yu Teng; Linlin Zhang; Gui-Fang Duan; He Wang; Rong Xu; Guiquan Chen; Yun Xu; et al. (Neuroscience Bulletin, 2025)
Accurate timing of myelination is crucial for the proper functioning of the central nervous system. Here, we identified a de novo heterozygous mutation in TMEM63A (c.1894G>A; p. Ala632Thr) in a 7-year-old boy exhibiting hypomyelination. A Ca 2+ influx assay suggested that this is a loss-of-function mutation. To explore how TMEM63A deficiency causes hypomyelination, we generated Tmem63a knockout mice. Genetic deletion of TMEM63A resulted in hypomyelination at postnatal day 14 (P14) arising from impaired differentiation of oligodendrocyte precursor cells (OPCs). Notably, the myelin dysplasia was transient, returning to normal levels by P28. Primary cultures of Tmem63a −/− OPCs presented delayed differentiation. Lentivirus-based expression of TMEM63A but not TMEM63A_A632T rescued the differentiation of Tmem63a −/− OPCs in vitro and myelination in Tmem63a −/− mice. These data thus support the conclusion that the mutation in TMEM63A is the pathogenesis of the hypomyelination in the patient. Our study further demonstrated that TMEM63A-mediated Ca 2+ influx plays critical roles in the early development of myelin and oligodendrocyte differentiation.

A Global Synthesis of How Plants Respond to Climate Warming From Traits to Fitness - Pengyan Jia; Rong Zhang; Bernhard Schmid; Han Wang; Jin‐Sheng He; Jiaxi Liu; Sijie Liu; Sipeng Jian; Yanhao Feng (Ecology Letters, 2025)
Despite intensive research, our understanding of how plants respond to warming by coordinating their full arsenal of traits to adjust fitness is lacking. To fill this gap, we applied a trait‐based framework with three clusters (two functional clusters: “carbon‐fixation rate” and “carbon‐fixation area”; a third cluster: “total carbon fixation”) to a global dataset compiled from 572 studies of warming experiments with 677 species and a comprehensive list of traits and fitness components. The pairwise correlation analysis complemented with SEM and PCA showed that plants increased biomass (the core variable in the third cluster) under warming by coordinating satellite traits in two functional clusters to adjust their core traits, net photosynthesis rate and total leaf area, respectively. In particular, the trait coordination was characterised by the maintenance of net photosynthesis rate and the increase of total leaf area, which was robust across ecological contexts although warming responses of the variables per se displayed context‐dependences. Moreover, the trade‐offs between biomass and reproduction (itself bearing mass vs. number trade‐offs) in their warming responses scaled the coordination to enhance fitness except in the contexts where reproduction was reduced. These findings could help explain and predict plant form and function in a warming world.

Efficient uranium(VI) recovery from fluorinated wastewater via deferiprone ligand complexation - Juanlong Li; Yezi Hu; Zewen Shen; Huihui Jin; Rong He; Wenkun Zhu; Guixia Zhao; Zhuoyu Ji; Bin Ma; Xiangke Wang (Water Research, 2025)

Cytochrome P450 CYP6EM1 confers resistance to thiamethoxam in the whitefly Bemisia tabaci (Hemiptera: Aleyrodidae) via detoxification metabolism - Mingjiao Huang; Peipan Gong; Cheng Yin; Jing Yang; Shaonan Liu; Buli Fu; Xuegao Wei; Jinjin Liang; Hu Xue; Chao He; Tianhua Du; Chao Wang; et al. (Pesticide Biochemistry and Physiology, 2025)

Diagnosis method for AUV propeller entanglement based on stylistic diversity and physics-guided priors - Wenfeng Zhao; Ze Yu; Shenghui Rong; Bo He (Ocean Engineering, 2025)

Phylogenomics of Paragymnopteris (Cheilanthoideae, Pteridaceae): Insights from plastome, mitochondrial, and nuclear datasets - Jing Zhao; Zhen-Long Liang; Shao-Li Fang; Rong-Juan Li; Chuan-Jie Huang; Li-Bing Zhang; Tanner Robison; Zhang-Ming Zhu; Wen-Jing Cai; Hong Yu; Zhao-Rong He; Xin-Mao Zhou (Molecular Phylogenetics and Evolution, 2025)

Toxic aldehydes in fried foods: Formation, analysis, and reduction strategies - Xing-yang Guo; Liang-yu Cheng; Chao Chang; Xiao-ming Jiang; Pan Gao; Wu Zhong; Chuan-rong Hu; Dong-ping He; Jiao-jiao Yin (Food Control, 2025)

Trade-offs between agronomic and environmental benefits: A comparison of inhibitors with controlled release fertilizers in global maize systems - Minyu Wang; Ping He; Daijia Fan; Rong Jiang; Guoyuan Zou; Daping Song; Libo Zhang; Yu Zhang; Wentian He (Field Crops Research, 2025)

Enhancing non-intrusive load monitoring through transfer learning with transformer models - Jing Rong; Cong Wang; Qiuzhan Zhou; Yunxue He; Huinan Wu (Energy and Buildings, 2025)

Epigenetic nanoplatform for synergistic immune activation and immunogenicity restoration enhancing cancer radio-immunotherapy - Zhenhu He; Xiaopei Peng; Jiong Li; Yaning Zhu; Xuan Zhang; Junhong Duan; Jing Ni; Mengtian Ma; Juan Wang; Zhenguo Liu; Bin Feng; Wenbin Zeng; et al. (Chemical Engineering Journal, 2025)

DNA aptamer-crosslinked hydrogel sensor: Design, mechanism and application for food safety analysis - Xinning Wang; Liuqin He; Xiaoxiao Rong; Ling Liu; Yulong Yin; Xiaoying Zhao; Yunxuan Weng (Trends in Food Science & Technology, 2025)

Effects of microclimatic conditions and urban building configurations on aerodynamic characteristics and health risks of bioaerosols: Insights from idealized urban models - Zhijian Dong; Zhijian Liu; Chenxing Hu; Chenglin Ye; Yongjun Jin; Haiyang Liu; Rui Rong; Yuchen He; Li Chen; Chuanchen Li; Yaolong Shi; Yufeng Su (Sustainable Cities and Society, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Spatiotemporal pattern of the East Asian monsoon hydroclimate during the 8.2 ka event inferred from a new speleothem multi-proxy record from SE China - Xiaomei Zhang; Haiwei Zhang; Rui Zhang; Jian Wang; Miaomiao Wang; Zeyuan Liang; Mei He; Rong Wei; Hai Cheng (Quaternary Science Reviews, 2025)

A plant growth-promoting bacterium supports cadmium detoxification of rice by inducing phenylpropanoid and flavonoid biosynthesis - Yingjie Wu; Haiyang Zhao; Meijuan Xiao; Huimin Liu; Hua He; Lu Peng; Qi Tao; Xiaoyan Tang; Yanyan Zhang; Rong Huang; Bing Li; Changquan Wang (Journal of Hazardous Materials, 2025)

Severity and risk to inhalation of pathogen-laden aerosol in large public spaces: Insights from fangcang shelter hospitals under multi-location release - Chuan Jiang; Zhijian Liu; Yongxin Wang; Guangpeng Yao; Junzhou He; Shiyue Li; Rui Rong; Zhenyu Liang; Jingwei Liu (Journal of Hazardous Materials, 2025)

Lipid peroxidation inhibition by icaritin and its glycosides as a strategy to combat iron overload-induced osteoporosis in zebrafish - Chang-Yu Yan; Xiao-Yuan Gu; Shuo-Yan Tan; Ao-Yu Mei; Jiang-Hao Mao; Yi Dai; Jie Niu; Wei-Xi Li; Hiroshi Kurihara; Yi-Fang Li; Rong-Rong He (Food Research International, 2025)

Revisiting bipolar membrane electrodialysis for the production of monoprotic organic acids with different p K a and Mw - Rong Zhou; Zhiguo Dong; Xixi Ma; Lili Xue; Jinxin Liu; Jinfeng He; Weiwei Li; Li Sun; Chuanrun Li; Haiyang Yan (Chemical Engineering Journal, 2025)

The Role of the Intestinal Flora and Its Derivatives in Neurocognitive Disorders: A Narrative Review from Surgical Perspective - Jian Huang; Tian-Shou Qin; Yun Bo; Yu-Jin Li; Rong-Sheng Liu; Yang Yu; Xiao-Dong Li; Jin-Can He; Ai-Xin Ma; Da-Peng Tao; Wen-Jun Ren; Jun Peng (Molecular Neurobiology, 2025)
Perioperative neurocognitive dysfunction is a significant concern for population health, impacting postoperative recovery and increasing the financial burden on patients. With an increasing number of surgical procedures being performed, the prevention and management of perioperative neurocognitive dysfunction have garnered significant attention. While factors such as age, lifestyle, genetics, and education are known to influence the development of cognitive dysfunction, recent research has highlighted the role of the gut microbiota in neurological health. An increased abundance of pro-inflammatory gut microbiota can trigger and worsen neuroinflammation, neuronal cell damage, and impaired cellular autophagy. Moreover, the inflammation-promoting gut microbiota can disrupt immune function, impair neuroautophagy, and affect the production and circulation of extracellular vesicles and neurotransmitters. These factors collectively play a role in the onset and advancement of cognitive impairment. This narrative review delves into the molecular mechanisms through which gut microbiota and their derivatives contribute to cognitive impairment, focusing on the impact of anesthesia surgery, changes in gut microbial populations, and perioperative cognitive impairment associations. The study suggests that alterations in the abundance of various bacterial species and their metabolites pre- and post-surgery may be linked to postoperative cognitive impairment. Furthermore, the potential of probiotics or prebiotics in addressing cognitive impairment is discussed, offering a promising avenue for investigating the treatment of perioperative neurocognitive disorders.

LINC01224 promotes the Warburg effect in gastric cancer by activating the miR-486-5p/PI3K axis - Yuling Bin; Minji Liu; Rong He; Pingfei Tang; Weiming Qu; Dajun Wu; Lin Tan; Qian Wang; Peng Jiang; Hongsai Hu (In Vitro Cellular & Developmental Biology - Animal, 2025)

Melatonin inhibits ferroptosis through the ATF3/GPX4 signaling pathway to relieve myocardial ischemia–reperfusion injury in rats - Minjie He; Yongheng Yang; Xing He; Rong Lei; Hong Liu; Mei Yang (In Vitro Cellular & Developmental Biology - Animal, 2025)

First data on aquaculture of the narrow-barred Spanish mackerel (Scomberomorus commerson) in ponds - Pei-Sheng Chiu; Yeong-Torng Chu; Yen-Hung Lee; Jia-Shin He; Li-Chi Cheng; Ting-Jeng Chang; Jinn-Rong Hseu; Jinn-Shing Weng; Feng-Cheng Wu (Aquaculture International, 2025)

Susceptibility and risk to inhalation of pathogen-laden aerosol in large public spaces: Evidence from Fangcang Shelter Hospitals under multiple ventilation rates - Chuan Jiang; Zhijian Liu; Yongxin Wang; Guangpeng Yao; Junzhou He; Shiyue Li; Rui Rong; Zhenyu Liang; Jiaqi Chu; Jingwei Liu (Sustainable Cities and Society, 2025)

Structurally diversified sesquiterpenoids from Chloranthus henryi and their neuroprotective activities on H2O2 damaged PC12 cells - Meng-Li He; Lian-Lian Xu; Yang Liu; Yan-Ping Gao; Yong-Ming Luo; Rong-Cai Yue; Fang-You Chen (Phytochemistry, 2025)

Preparation and performance evaluation of an efficient microbial dust suppressant for dust control in disturbed areas of blast piles in open-pit coal mines - Jie Chen; Haoran Wang; Yi He; Rong Liu; Chuanhui Zeng; Kunyu Yan; Junpeng Zhu (Journal of Environmental Management, 2025)

Effect of electron beam irradiation on edible quality maintenance of high moisture rice grains - Dongmin Li; Ying Wan; Jinye Zhang; Yuwei Zhang; Rong He; Sangyuan Sang; Jiali Xing; Xiaohu Luo (Journal of Cereal Science, 2025)

The mango bacterial black spot altered the endophyte community structure and diversity - Meng-Jiao Li; Ji-Han Li; Wen-Lin Li; Yuan He; Yu-Bo Ma; Xin-Yu Li; Yan Wang; Cai-Xia Li; Xin-Rong Ma (International Journal of Food Microbiology, 2025)

Effect of Maillard reaction on the allergenicity of crude extract of Mactra quadrangularis - Fa-Jie Li; Xin-Rong He; Dong-Xiao Li; Yang Yang; Shuai Kang; Qing-Mei Liu; Lian-Zhong Luo; Gui-Xia Chen; Guang-Ming Liu (Food Research International, 2025)

Lignocellulosic biowaste hydrothermal humification: Is there a method for predicting humic acid? - Yuchao Shao; Jianchao Wang; Zhiqiang Dong; Yujie Wang; Wenjing He; Weizhong Huo; Rong Ye; Yanqing Liu; Kexue Liu; Jialin Xue; Wenjing Lu; Tianxue Yang (Chemical Engineering Journal, 2025)

Box-shaped necklace-like Fe3O4/MoS2-CNFs composite nanofibers with confinement effect enhancing sodium storage performance - Huayu Wu; Mohan Yue; Lin He; Miao Zhang; Yimin Huang; Chang Sun; Yu Liu; Jindi Wang; Rongguan Lv; Rong Xing (Chemical Engineering Journal, 2025)

Characterization of Gut Microbiota in Rats and Rhesus Monkeys After Methamphetamine Self-administration - Li He; Jia-hui Zhou; Huan Li; Wen-lei Zhang; Tie-qiao Liu; Hai-feng Jiang; Rong-wei Zhai; Xiao-jie Zhang (Molecular Neurobiology, 2025)

Exosomal miR-146a-5p derived from bone marrow mesenchymal stromal cells regulate Th1/Th2 balance and alleviates immune thrombocytopenia in pregnancy - Yanyan Rong; Wei Lu; Xianbao Huang; Dexiang Ji; Dehong Tang; Ruibin Huang; Wenhua Zhou; Guoan Chen; Yue He (Human Cell, 2024)

Relationship Between Whole Blood Iron Levels and Lipid Profile Parameters in the General Population: Findings from Routine Physical Examination Report - Rou-Jun Pan; Zhi Luo; Yu-Shun You; Jun-Dong Wang; Ya-Qi Chen; Rong-Rong Zhou; Shu-Zi-Qi Chen; Lin-Min Wang; Jun-Xiang Zhao; Hua-Qin Su; Cai-Li Wang; Li-Fen Zhang; et al. (Biological Trace Element Research, 2024)

Effect of long-term temperature-controlled rearing on growth traits and sexual maturity of common carp (Cyprinus carpio) - Yongming Li; Kuangxin Chen; Bin Gui; Cheng Yang; Libo He; Lanjie Liao; Zuoyan Zhu; Yaping Wang; Rong Huang (Aquaculture, 2024)

Progress in the application of Salmonella vaccines in poultry: A mini review - Jie Pan; Rong-rong Wei; Ping Xu; Yun-ying Liu; Chen Li; Guo-wei Ding; Juan Fan; Yu-he Li; Jing-yi Yu; Peng Dai (Veterinary Immunology and Immunopathology, 2024)

Partial organic substitution increases soil quality and crop yields but promotes global warming potential in a wheat-maize rotation system in China - Gong Wu; Hai-meng Huang; Bei-bei Jia; Lei-lei Hu; Chong-sheng Luan; Qi Wu; Xiao-yu Wang; Xiao-xiao Li; Zhao Che; Zhao-rong Dong; He Song (Soil and Tillage Research, 2024)

Global techno-economic analysis of MBR for hospital wastewater treatment - Junqing He; Zhenxing Zhang; Fangnan Cui; Xue Tan; Xiang Zheng; Rong Cheng (Science of The Total Environment, 2024)

Invisible hazards: Exploring neonicotinoid contamination and its environmental risks in urban parks across China - Yongfeng Deng; Ruqin Shen; Xue Zhang; Yang Li; Xingguo Chen; Rong-Rong He; Hao Tian; Shuqin Tang; Xiang Luo; Jing Li; Wan-Yang Sun; Hongli Tan (Science of The Total Environment, 2024)

Mechanism of β-MnO2 particle for the peroxymonosulfate activation under electric field: the promoting effect of carbamazepine on Mn(III) and reactive oxygen species production - Shaochun Yuan; Shuquan He; Qingyu Wu; Tuo Wang; Mengyu Li; Rong Liu; Yao Chen; Chuanliang Zhao; Fei Liu; Zhen Liu (Process Safety and Environmental Protection, 2024)

Phylogenomic analyses of the pantropical Platycerium Desv. (Platycerioideae) reveal their complex evolution and historical biogeography - Jing Zhao; Chuan-Jie Huang; Li-Ju Jiang; Zhao-Rong He; Shuai Yang; Zhang-Ming Zhu; Liang Zhang; Hong Yu; Xin-Mao Zhou; Jia-Guan Wang (Molecular Phylogenetics and Evolution, 2024)

Deciphering the evolution and biogeography of ant-ferns Lecanopteris s.s - Li-Ju Jiang; Jing Zhao; Jia-Guan Wang; Sven Landrein; Ji-Pu Shi; Chuan-Jie Huang; Miao Luo; Xin-Mao Zhou; Hong-Bin Niu; Zhao-Rong He (Molecular Phylogenetics and Evolution, 2024)

Evaluation of fluid mobility and factors influencing the deep tight sandstone of the third member of the Shahejie formation in the Jiyang depression, Bohai Bay Basin - Yuchao Wang; Dongxia Chen; Lanxi Rong; Jialing Chen; Fuwei Wang; Shijie He; Yuqi Wang; Zijie Yang; Wenzhi Lei (Marine and Petroleum Geology, 2024)

Effect of zero-valent iron and magnetite on mitigating sulfate and lincomycin stress in anaerobic digestion: microbial succession and antibiotic resistant genes removal - Jing Xie; Jiaxin Zhu; Bolin Min; Rong He; Wenbiao Wang; Li Xie (Journal of Water Process Engineering, 2024)

Experimental study of interception effect by submerged dam on microplastics - Jianhao Jiang; Lulu He; Junping Liu; Xu Liu; Junbao Huang; Li Rong (Journal of Hazardous Materials, 2024)

Research advances in technologies and mechanisms to regulate vinegar flavor - Zhankai Zhang; Zhi-hong Zhang; Ronghai He; Guozhong Zhao; Yongjian Yu; Rong Zhang; Xianli Gao (Food Chemistry, 2024)

Soy protein isolate ameliorate gel properties by regulating the non-covalent interaction between epigallocatechin-3-gallate and myofibrillar protein - Ying Li; Yijun Zhang; Gongchen He; Ziyan Qiao; Rong Yang; Xi Zhou; Lin Chen; Xianchao Feng (Food Chemistry, 2024)

Multifunctional property of N,N-bis (carboxymethyl) glutamic acid modified biomass material: adsorption and degradation removals of cationic dyes in wastewater - Min He; Lang Zhao; Hongbin Hu; Lu Yao; Yinghuai Guo; Chunjiang Hou; Shaokun Gao; Rong Li (Environmental Research, 2024)

Impact of freeze-thaw cycles on the remobilization behaviors of microplastics in natural soils - Lichun Hsieh; Haifeng Rong; Lei He; Jia Guo; Meng Li; Meiping Tong (Environmental Pollution, 2024)

Thyroid hormones and oxidative stress moderated the association between urinary phthalate metabolites and cardiovascular risk factors - Rong He; Hua Bi; Jia He; Yangxu Luo; Xiaotong Li; Qin Li; Rende Huang; Lei Tan (Environmental Pollution, 2024)

Electrodialysis with ultrafiltration membrane for efficient isolation of oxymatrine from simulated eluent of traditional Chinese medicine - Zhiguo Dong; Rong Zhou; Zengqiang Wei; Yiwei Dong; Li Sun; Xixi Ma; Wenlong Liu; Qiuhua Li; Jinfeng He; Chuanrun Li; Haiyang Yan (Desalination, 2024)

Lattice-Engineering modulated band structure facilitates enhanced stability of high-voltage LiCoO2 at 4.6 V - Zhi Zhang; Guang-Xin Wu; Zhou-Liang Tan; He-Zhang Chen; Zhen Yu; Zhen-Rong Yu; Xiao-Bing Huang; Wen-Jie Yang; Ying-De Huang (Chemical Engineering Journal, 2024)

MOF for encapsulating ionic liquids serves as an electrocatalyst to decrease the ignition delay time of electrically controlled solid propellants - Baiquan Chen; Cailing Zhang; Zhenguo Pang; Xugang Rong; Yanli Guo; Wei He (Chemical Engineering Journal, 2024)

Volatile organic compounds in typical coal chemical industrial park in China and their environmental and health impacts - Jieting Zhou; Min Gao; Hongmei Xu; Ruiqing Cai; Rong Feng; Kun He; Jian Sun; Steven Sai Hang Ho; Zhenxing Shen (Atmospheric Environment, 2024)

Correction: Developing Estimation Equations for the Cerchar Abrasivity Index of Rocks Applicable to TBM Tunnels - Lei She; Yan-long Li; She-rong Zhang; Chao Wang; Sun-wen He; Yu-jie Wang; Ming-ming He; Sheng-le Wang (Rock Mechanics and Rock Engineering, 2024)

Novel targets and their functions in the prognosis of uterine corpus endometrial cancer patients - Xin Sui; Penghui Feng; Jie Guo; Xingtong Chen; Rong Chen; Yanmin Zhang; Falin He; Feng Deng (Journal of Applied Genetics, 2024)

Single-cell transcriptome analysis of the mouse lungs during the injury and recovery periods after lipopolysaccharide administration - Hou-Ping Wang; Jian He; Jian-Rong He; Dan-Dan Li; He Huang; Bing Chen (Inflammation Research, 2024)

Amplification of warming-wetting in high mountains and associated mechanisms during the 21st century in Xinjiang, Central Asia - Rong Chen; Keqin Duan; Peihong Shi; Wei Shang; Junhua Yang; Jinping He; Yali Meng; Mingyu Dou; Liang Li (Climatic Change, 2024)

The effect of Desulfovibrio caledoniensis and Pseudomonas aeruginosa on the corrosion behaviour of 70Cu-30Ni alloy - Li-Jun He; Zheng-Hui Qiu; Shao-Xia Ma; Rong-Chang Zeng; Cun-Guo Lin (Biofouling, 2024)

Changes in secondary sexual characteristics of female red swamp crayfish (Procambarus clarkii) and relationship to ovarian development: Implications for intensive breeding of seedlings - Lirong Qin; Jinhui He; Kuan Rong; Chao Guo; Jiashou Liu; Tanglin Zhang; Wei Li (Aquaculture, 2024)

Unraveling phytoremediation mechanisms of the common reed (Phragmites australis) suspension cells towards ciprofloxacin: Xenobiotic transformation and metabolic reprogramming - Bin Wang; Hang Xu; Yu Liu; Kaiping Zhou; Xinyu Li; Deyang Kong; Jinmei Chen; Yujie He; Rong Ji (Water Research, 2024)

PM2.5 constituents associated with mortality and kidney failure in childhood-onset lupus nephritis: A 19-year cohort study - Guohua He; Yaqi Wang; Cheng Cheng; Jianhui Guo; Zhilang Lin; Ziyun Liang; Bei Jin; Liyuan Tao; Liping Rong; Lizhi Chen; Tianxin Lin; Yining Hua; et al. (Science of The Total Environment, 2024)

Degradation characteristics and effect mechanisms of estrogens during aerobic composting of chicken manure based on the orthogonal test - Ziwei Liang; Junhao Wu; De-Chun He; Yan Li; Yan-Qiu Liang; Jia-Wu Hu; Meng-Yao Zou; Jian-Feng Ning; Wang-Rong Liu (Journal of Environmental Management, 2024)

Rhodamine and related substances in food: Recent updates on pretreatment and analysis methods - Rong-zhu Du; Yuan Zhang; Yu Bian; Chun-yu Yang; Xue-song Feng; Zhen-wei He (Food Chemistry, 2024)

Perfluorooctane sulfonate (PFOS) and benzo[a]pyrene (BaP) synergistically induce neurotoxicity in C6 rat glioma cells via the activation of neurotransmitter and Cyp1a1-mediated steroid hormone synthesis pathways - Yu-Shun Lu; Ju Chen; Xiao-Rong He; Shang-Lin Yang; Bing-Jie Ma; Jiang Yu; Jing Qiu; Yong-Zhong Qian; Yan-Yang Xu (Food and Chemical Toxicology, 2024)

Genomic analysis of hypoxia-tolerant population of the Chinese mitten crab (Eriocheir sinensis) - Feng-yuan Yan; Yuan-feng Xu; Wen-rong Feng; Qing-hong He; Guo-an Hua; Wen-jing Li; Pao Xu; Jun Zhou; Yong-kai Tang (Fish & Shellfish Immunology, 2024)

Solar regulation based on thermofluorescence and thermochromism for self-adaption of temperature - Qing Tian; Rong Tang; Zhuoyue Gu; Jingya Hou; Liu Yang; Sailing He (Energy and Buildings, 2024)

Robust polymer electrolytes with fast ion-transport nanochannels constructed by carbon dots for long lifespan Li metal batteries - Jia-Wen Ni; Xi-Rong Zhang; Tian-Bing Song; Zun-Hui Huang; Qian-Li Ma; Tian-Le He; Huan-Ming Xiong (Chemical Engineering Journal, 2024)

Weakly solvated electrolyte enables the robust solid electrolyte interface on SiOx anodes for lithium-ion battery - Zuojie Xu; Rong Huang; Pengfei Huang; Chaowei He; Shenwen Liu; Haonan Zheng; Wenlong Song; Lu Shi; Weiwei Gao; Dan Li; Hui Huang; Hangjun Ying; et al. (Chemical Engineering Journal, 2024)

Tuning local charge polarization of covalent organic frameworks for enhanced photocatalytic uranium (VI) reduction - Xiao-Xing Wang; Cheng-Rong Zhang; Rui-Xiang Bi; Zhi-Hai Peng; Hao-Xuan He; Rui Zhang; An-Min Song; Jia-Xin Qi; Xiao-Juan Chen; Xin Liu; Yuan-Jun Cai; Ru-Ping Liang; et al. (Chemical Engineering Journal, 2024)

Ceftriaxone Removal with Sulfonic-phosphoric Acid Resin Based on Cation Adsorption Characteristic - Changlian Zheng; Min He; Bingqian Jia; Bin Chen; Rong Li (Water, Air, & Soil Pollution, 2024)

Optimizing shrimp nutrition and health: ginseng saponins as functional additives in low-fishmeal diets on Litopenaeus vannamei - Sihan Lin; Rong Yao; Xin Cui; Yucai Guo; Denghui Hu; Bin Zhou; Zhaobin Zhou; Xuanshu He; Zhihong Liao; Beiping Tan; Jin Niu (Frontiers in Marine Science, 2024)
The research investigated the nutritional physiology effect of ginseng saponins on Litopenaeus vannamei ( L. vannamei ) under low-fishmeal diets. In total, five experimental groups were arranged, with 21% fishmeal (high-fishmeal) serving as the positive control (PC), 11% fishmeal (low-fishmeal) serving as the negative control (NC), and 11% fishmeal serving as the addition in all three other groups. Similarly, ginseng saponins (GSP, purity of 2%) were added in the order of 0.1%, 0.3%, and 0.5% (GSP0.1, GSP0.3, and GSP0.5), with an 8-week growth cycle. Both GSP0.1 and GSP0.3 showed significantly higher growth performance (final body weight, FBW; weight gain rate, WGR; specific growth rate, SGR) than the NC group, but significantly lower growth performance than the PC group ( P <0.05). However, it was found that there was no significant difference in the body composition of the whole shrimp between the experimental groups. Compared to the PC group, the GSP0.3 group exhibited significantly elevated levels of antioxidant enzymes, total antioxidant capacities (T-AOC), superoxide dismutase (SOD), and glutathione peroxidase (GSH-Px) ( P <0.05). Additionally, significant differences were observed between the PC and GSP0.3 groups regarding the expression levels of sod , cat , and gsh-px (P<0.05). And there was a better morphological organization of shrimp hepatopancreas in the GSP0.3 group than in all other groups. In comparison with the PC group, there was no significant difference in shrimp survival rates after ammonia nitrogen stress with ginseng saponins added ( P >0.05). Whereas, in terms of the relative expression levels of the corresponding genes, in shrimp of the GSP0.3 group, the relative expression of antioxidant-related genes sod , cat , and gsh-px were significantly higher than that of the PC group ( P <0.05). Caspase3 and p53 , along with bcl-2 and bax , were found to be significantly more expressed in shrimp of the GSP0.3 group than in all other groups ( P <0.05). These findings imply that in addition to improving growth performance, adding ginseng saponins at a concentration of 11% fishmeal could improve the antioxidant capacity of L. vannamei as well as its resistance to stress. Therefore, ginseng saponins can be utilized as a functional additive to increase L. vannamei growth performance, enhance antioxidant capacity, and reduce stress in low-fishmeal diets, 0.3% of ginseng saponins is optimal.

Effects of weather parameters on the population dynamics of Megalurothrips usitatus in cowpea fields in Sanya, China - Yunchuan He; Jiamei Geng; Yang Gao; Qiulin Chen; Ying Zhou; Zeng-Rong Zhu (International Journal of Tropical Insect Science, 2024)

Interactions between microbial communities and polymers in hydraulic fracturing water cycle: A review - Cheng Zhong; Rong Chen; Yuhe He; Deyi Hou; Fu Chen (Science of The Total Environment, 2024)

Structurally diverse diterpenoids from the leaves of Croton mangelong and their anti-diabetic activity - Zhi-Yong Jiang; Qi Niu; Hao-Xin Wang; Hao-Nan Xu; Hong-Xi Xie; Lin Chen; Rong Chen; Hong-Lei Zhang; Lu Gao; Ai-Xue Zuo; Hong-Ping He (Phytochemistry, 2024)

Dicranopteris pedata improves soil quality by enhancing nutrient deposition, decreasing metal concentration, and boosting microbial diversity on abandoned rare earth elements mining sites - Xi-Wen Cui; Zhen-An Xu; Xian Chen; Zhi-Biao Chen; Jia-Bing Li; Rong-Rong Xie; Hong Zhang; Yong Zhang; Yong-He Han (Journal of Environmental Chemical Engineering, 2024)

Accelerated cartilage regeneration through immunomodulation and enhanced chondrogenesis by an extracellular matrix hydrogel encapsulating Kartogenin - Kai Huang; Qing-Yi Zhang; Jie Tan; Rong Nie; Zi-Yuan Feng; Yuan Liu; Ning Sheng; He-Xi Li; Yue-Qi Zhang; Bin Shen; Hui-Qi Xie (Chemical Engineering Journal, 2024)

Developing Estimation Equations for the Cerchar Abrasivity Index of Rocks Applicable to TBM Tunnels - Lei She; Yan-long Li; She-rong Zhang; Chao Wang; Sun-wen He; Yu-jie Wang; Ming-ming He; Sheng-le Wang (Rock Mechanics and Rock Engineering, 2024)

Short-term effects of ambient nitrogen dioxide on medical emergency calls for epileptic seizures: A time-series study - Yijie Wang; Fei Wang; Rong He; Yiming Wang; Yumin Liu; Xiaoqing Jin (International Journal of Biometeorology, 2024)

Bamboo vinegar regulates the phytoremediation efficiency of Perilla frutescens (L.) Britt. by reducing membrane lipid damage and increasing cadmium retention - Zhenguo Li; Xingyu Hao; Tianlian He; Ying Chen; Mingwei Yang; Cheng Rong; Chengzhen Gu; Qingtie Xiao; Ruiyu Lin; Xinyu Zheng (Journal of Hazardous Materials, 2024)

Epinephelus coioides Sec3 promotes Singapore grouper iridovirus infection by negatively regulates immune response - Yu-Rong Lei; Jia-Yang He; Xue-Mei Fu; Cui-Fen Huang; Yun-Xiang Lin; Li-Ling Dai; Zi-An Chen; Ze-Peng Zhang; Fu-Min Liu; Qi-Wei Qin; Hong-Yan Sun (Fish & Shellfish Immunology, 2024)

Gypsum ridges as conduits for deep methane emission in an evaporite basin– Insights into the origin of atmospheric methane on Mars - Yiliang Li; Zikang Li; Xiaorong Qin; Binlong Ye; Ziyu Niu; Anouk Ehreiser; Wenhua Zhang; Yang Pan; Liping Qin; Rong Shu; Jianxi Zhu; Yigang Xu; et al. (Earth and Planetary Science Letters, 2024)

The response of Martian photoelectron boundary to the 2018 global dust storm - Yuqi Wang; Jun Cui; Yong Wei; Zhaopeng Wu; Kai Fan; Zhaojin Rong; Fei He; Yutian Cao; Jiawei Gao (Science China Earth Sciences, 2024)

Assessment of the hormesis effect and toxic damage of short-term low-dose aflatoxin B1 in grass carp (Ctenopharyngodon idellus) - Jin-long Li; Jia-rong Guo; Pei Wang; Jun-zhi Zhang; Zhi-gang He; Jin-long Wang; Yi Hu (Frontiers in Marine Science, 2024)
The present study was conducted to evaluate the hormesis and toxicity of short-term low-dose aflatoxin B1 in grass carp ( Ctenopharyngodon idellus ). Triplicate isonitrogenous and isocaloric aflatoxin B1 diets—CD (control, 0 ug/kg), D1 (20 ug/kg), and D2 (500 ug/kg)—were prepared and fed to grass carp with an initial mean body weight of (15.2 ± 0.1) g for 56 days. The results showed that the weight gain rate and specific growth rate of grass carp fed diet D2 were significantly higher, and the feed coefficient and crude fat content of the whole body were significantly lower ( P < 0.05) compared with those fed diet CD. Serum superoxide dismutase content of grass carp fed D1 diet increased significantly ( P < 0.05) with an increasing dose of aflatoxin B1, but when the dose reached 500 ug/kg (D2), serum superoxide dismutase, complement C3, and immunoglobulin M of grass carp decreased significantly ( P < 0.05), while malondialdehyde increased significantly ( P < 0.05). After short-term feeding of aflatoxin B1-containing diets (D1 and D2), liver body index, visceral body index, serum total cholesterol, triglyceride, and urea nitrogen content of grass carp increased significantly ( P < 0.05), total bile acid secretion decreased significantly ( P < 0.05), and structural damages such as increase in vacuoles, organizational structure loosening, and nucleus translocation were observed in the liver. Meanwhile, liver function indexes such as serum alanine aminotransferase, aspartate aminotransferase, and alkaline phosphatase increased significantly with the increase of aflatoxin B1 dose ( P < 0.05). In addition, the height of intestinal villi, crypt depth, villus–crypt ratio, and tubular cell number, as well as the content of trypsin and lipase activities in the intestine of grass carp in the D2 group, were significantly higher than those in the CD group ( P < 0.05). In conclusion, after a short-term intake of low doses of aflatoxin B1 (≤500 ug/kg), the toxicological damage of aflatoxin B1 was pronounced, although it produced a certain degree of hormesis on the growth performance and intestinal structure and function of grass carp. At a dose of 20 ug/kg, the non-specific immune system and liver structure and function of grass carp showed obvious toxic damage.

Microbial etch: A novel construction method of functionalized biochar for enhanced uranium extraction in radioactive wastewater - Yazhou Wang; Xudong Wu; Xiyang Liu; Chengkun Cai; Chenghu Liang; Lichun Dai; Xinsheng He; Rong He; Huanhuan Liu; Wenkun Zhu (Chemosphere, 2024)

Sustainable design of photo-Fenton-like oxidation process in actual livestock wastewater through the highly dispersed FeCl3 anchoring on a g-C3N4 substrate - Yanfang Feng; Yunyi Liang; Chenman Ding; Yue Jiang; Hongmei Jin; Shaopeng Rong; Jun Wu; Shiying He; Changlei Xia; Lihong Xue (Water Research, 2024)

Evolution and disappearance of the paleo-West Pacific Anomaly: Implications to the future of South Atlantic Anomaly - Yaochen Yue; Jiawei Gao; Fei He; Yong Wei; Shuhui Cai; Huapei Wang; Yuqi Wang; Zhaojin Rong; Zhonghua Yao; Wei Lin; Yongxin Pan (Physics of the Earth and Planetary Interiors, 2024)

Facile construction of plasmonic Ag/Nb2O5 films and their photocatalytic activity against organic dye and nanoplastics - Te Hu; Liang Hao; Qian Zhao; Rong Jia; Sujun Guan; Yiqiang He; Yun Lu (Journal of Water Process Engineering, 2024)

Spatial distribution of bioaerosols and evaluation of four ventilation method on controlling their diffusion in a typical enhanced biosafety level 2 laboratory - Zhijian Liu; Yongxin Wang; Chuan Jiang; Junzhou He; Rui Rong; Shiyue Li; Zhenyu Liang (Journal of Hazardous Materials, 2024)

Impact of the thermo-alkaline pretreatment on the anaerobic digestion of poly(butylene adipate-co-terephthalate) (PBAT) and poly(lactic acid) (PLA) blended plastics - Rong Nie; Wei Peng; Fan Lü; Hua Zhang; Xiangyu Lu; Pinjing He (Journal of Hazardous Materials, 2024)

Bibliometric study of the application of the chicken embryo chorioallantoic membrane model in cancer research: the top 100 most cited articles - Chang Song; Dan-Dan Xiong; Rong-Quan He; Xiang-Zhi Yong; Zhi-Guang Huang; Yi-Wu Dang; Gang Chen; Yu-Yan Pang; Chun-Yan Zhao; Ning Qu; Dan-Ming Wei (Journal of Comparative Pathology, 2024)

Seasonal dynamics of the microbiota and nutritional composition in bee bread from Apis cerana and Apis mellifera colonies - Jia-Li Li; Wan-Li Li; Jun Zhang; Yan-tao Pang; Jian Xiong; Ping Wu; Bang-rong Wei; Xi-Jie Li; Qi Huang; Qi-He Tang; Chong-Hui Zhao; Qian Wang; et al. (Food Research International, 2024)

Organic substitution regime with optimized irrigation improves potato water and nitrogen use efficiency by regulating soil chemical properties rather than microflora structure - Xiya Wang; Binggeng Yang; Lingling Jiang; Shicheng Zhao; Mengjiao Liu; Xinpeng Xu; Rong Jiang; Jun Zhang; Yu Duan; Ping He; Wei Zhou (Field Crops Research, 2024)

Silica's silent threat: Contributing to skin fibrosis in systemic sclerosis by targeting the HDAC4/Smad2/3 pathway - Bingsi Tang; Yaqian Shi; Zhuotong Zeng; Xinglan He; Jiangfan Yu; Ke Chai; Jiani Liu; Licong Liu; Yi Zhan; Xiangning Qiu; Rui Tang; Yangfan Xiao; et al. (Environmental Pollution, 2024)

Suitable habitat evaluation and ecological security pattern optimization for the ecological restoration of Giant Panda habitat based on nonstationary factors and MCR model - Hui He; Xiangke Yu; Hui Yu; Zhigang Ma; Yong Luo; Tao Liu; Ziwei Rong; Jinhong Xu; Dianpeng Chen; Pengshang Li; Fuxin Yuan; Yongtao Zhao (Ecological Modelling, 2024)

Enhanced Fenton performance of wet-mechanochemically synthesized FeS2/Biochar: The multiple synergistic effect derived from mutual element doping - Zunqing Wen; Xiaoguo Shi; Yawei Gu; Ke Ma; Xiaozhe Song; Ao He; Chen Wang; Nianbo Zhang; Huiying Sui; Chongqing Xu; Rong Xue (Chemical Engineering Journal, 2024)

Polydatin: a potential NAFLD therapeutic drug that regulates mitochondrial autophagy through SIRT3-FOXO3-BNIP3 and PINK1-PRKN mechanisms - a network pharmacology and experimental investigation - Jing He; Yi-cai Qian; Ying-chuan Yin; Jing-rui Kang; Tian-rong Pan (Chemico-Biological Interactions, 2024)

Biochar modulates intracellular electron transfer for nitrate reduction in denitrifying anaerobic methane oxidizing archaea - Pan-Long Lv; Chuan Jia; Chi-Hang Wei; He-Ping Zhao; Rong Chen (Bioresource Technology, 2024)

Interfacial exchange of airflow and bacteria-carrying particles induced by door opening and foot traffic in an operating room - Haiyang Liu; Zhijian Liu; Junzhou He; Chenxing Hu; Rui Rong (Building and Environment, 2024)

Adenylate kinase phosphate energy shuttle underlies energetic communication in flagellar axonemes - Huan Wu; Yanman Zhang; Yuqian Li; Shuya Sun; Jintao Zhang; Qingsong Xie; Yue Dong; Shushu Zhou; Xuan Sha; Kuokuo Li; Jinyi Chen; Xin Zhang; et al. (Science China Life Sciences, 2024)

Prediction of solar activities: Sunspot numbers and solar magnetic synoptic maps - Rui Zhuo; Jiansen He; Die Duan; Rong Lin; Ziqi Wu; Limei Yan; Yong Wei (Science China Earth Sciences, 2024)

Investigation of New Integrated Drought Monitoring Model Taking into Account the Effects of Climate Anomalies - Lei Zhou; Wenliang Wang; Congcong He; Siyu Wang; Yalan Li; Rong Tian; Cheng Du (Journal of the Indian Society of Remote Sensing, 2024)

Mass cytometry revealed the circulating immune cell landscape across different Suzuki stages of Moyamoya disease - Chenglong Liu; Peicong Ge; Bojian Zhang; Liujia Chan; Yuheng Pang; Chuming Tao; Junsheng Li; Qiheng He; Wei Liu; Siqi Mou; Zhiyao Zheng; Zhikang Zhao; et al. (Immunologic Research, 2024)
Moyamoya disease (MMD) is a cerebrovascular disorder marked by progressive arterial narrowing, categorized into six stages known as Suzuki stages based on angiographic features. Growing evidence indicates a pivotal role of systemic immune and inflammatory responses in the initiation and advancement of MMD. This study employs high-dimensional mass cytometry to reveal the immunophenotypic characteristics of peripheral blood immune cells (PBMCs) at various Suzuki stages, offering insights into the progression of MMD. PBMC samples from eight patients with early-stage MMD (Suzuki stages II and III) and eight patients with later-stage MMD (Suzuki stages IV, V, and VI) were analyzed using high-dimensional mass cytometry to evaluate the frequency and phenotype of immune cell subtypes. We identified 15 cell clusters and found that the immunological features of early-stage MMD and later-stage MMD are composed of cluster variations. In this study, we confirmed that, compared to later-stage MMD, the early-stage MMD group exhibits an increase in non-classical monocytes. As the Suzuki stage level increases, the proportions of plasmacytoid DCs and monocyte-derived DCs decrease. Furthermore, T cells, monocytes, DCs, and PMN-MDSCs in the early-stage MMD group show activation of the canonical NF-κB signaling pathway. We summarized and compared the similarities and differences between early-stage MMD patients and later-stage MMD patients. There is a potential role of circulating immune dysfunction and inflammatory responses in the onset and development of MMD.

Phonological awareness and RAN contribute to Chinese reading and arithmetic for different reasons - Xiujie Yang; Jon R. Star; Xiangyi Zhu; Rong Wang; Yan Zhang; Jiajin Tong; Zhonghui He (Cognitive Processing, 2024)

PANI/GO and Sm co-modified Ti/PbO2 dimensionally stable anode for highly efficient amoxicillin degradation: Performance assessment, impact parameters and degradation mechanism - Zeyi Wang; Luyao Zhang; Rong Su; Lu Yang; Feng Xiao; Lichuan Chen; Ping He; Dingming Yang; Yali Zeng; Yun Zhou; Ying Wan; Bin Tang (Journal of Environmental Management, 2024)

A deep learning network for improving predictions of maximum and minimum temperatures over complex terrain - Lin Xu; Li Zhou; He Chen; Rong-Hui Cai; Yue Zhou (Theoretical and Applied Climatology, 2024)

Functional comparison of Rab3aa and Rab3ab in grass carp (Ctenopharyngodon idella) immune response and GCRV replication - Lifei Luo; Lv Xiong; Cheng Yang; Libo He; Lanjie Liao; Yongming Li; Zuoyan Zhu; Yaping Wang; Rong Huang (Aquaculture, 2024)

Co-exposure of polystyrene nanoplastics and copper induces development toxicity and intestinal mitochondrial dysfunction in vivo and in vitro - Jinyu Rong; Chenwei Yuan; Xiang Yin; Xiaohan Wu; Fei He; Yixin Wang; Kelvin Sze-Yin Leung; Sijie Lin (Science of The Total Environment, 2024)

Effects of arsenic on the transport and attachment of microplastics in porous media - Jia Guo; Haifeng Rong; Lei He; Cuibai Chen; Baogang Zhang; Meiping Tong (Journal of Hazardous Materials, 2024)

Biomineralization-inspired porous calcium carbonate microspheres as a controlled release system of herbicides/pesticides - Yaoxun Zeng; Xinyi Li; Fangzheng Chen; Huiling Ye; Keyi Rong; Zhili Ran; Binhong Liu; Zhenxing Pan; Xiuxian Xie; Junze Tang; Xujie Liu; Yan He (Journal of Environmental Chemical Engineering, 2024)

High mineralization efficiency of chlorobenzene oxidation using a metal-interaction strengthening MnCoOx catalyst derived from ZIF-67 - Shuangshuang Fu; Dongjie Yan; Dan Tao; Ning Yang; Kaixian Liu; Yifan Rong; Lu Li; Chi He (Fuel, 2024)

Determination of marker residues of quinoxaline-1,4-di-N-oxides and its prototype identification by liquid chromatography tandem mass spectrometry - Lu Li; Rong Liu; Longyun Liu; Zeyu Guo; Tong Zhou; Yuxi Yang; Huiping Yang; Limin He (Food Chemistry, 2024)

Pleurotus eryngii root waste and soybean meal co-fermented protein improved the growth, immunity, liver and intestinal health of largemouth bass (Micropterus salmoides) - Jian-Ming Xu; Wen-Rong Gao; Ping Liang; Guo-He Cai; Hong-Ling Yang; Jian-Bin Lin; Yun-Zhang Sun (Fish & Shellfish Immunology, 2024)

Prospective findings from the Dongfeng-Tongji cohort: Exposure to various metals, the expression of microRNA-4286, and the incidence of acute coronary syndrome - Miaoyan Shen; Xuedan Xu; Wending Li; Xi Wang; Rong Peng; Xuezhen Liu; Qiuhong Wang; Xiaomin You; Pinpin Long; Hao Wang; Rundong Niu; Yu Yin; et al. (Environmental Research, 2024)

A nonlinear elastic-strain hardening model for frozen improved sandy soil under uniaxial compression loading condition - Bo Liu; Yanqing He; Yanhui Han; Guoxuan Wang; Rong Gao; Dongyang Li (Cold Regions Science and Technology, 2024)

Enhanced anaerobic digestion performance and sludge filterability by membrane microaeration for anaerobic membrane bioreactor application - Chun-Hai Wei; Zheng-Wei Wang; Jian-Hua Dai; Kang Xiao; Hua-Rong Yu; Fang-Shu Qu; Hong-Wei Rong; Jun-Guo He; Huu Hao Ngo (Bioresource Technology, 2024)

Chemical constituents from Albatrellus confluence and their chemotaxonomic significance - Qing-Fang Wang; Jing-Rong Ou-Yang; Ting-Ting Guo; Ming-Ming Li; Hong-Ping He (Biochemical Systematics and Ecology, 2024)

Differentiation of bone marrow mesenchymal stem cells into Leydig-like cells with testicular extract liquid in vitro - Rong Hua; Fang-Fang Liang; Fang-Qiang Gong; Hua Huang; Yi-Chen Xu; Min He; Yan-Hua Fang; Ya-Shu Wei; Wei-Wei Zhou; Arshad Mehmood; Yi Mo; Zhong Lin (In Vitro Cellular & Developmental Biology - Animal, 2024)

A Novel FD3 Framework for Carbon Emissions Prediction - Houtian He; Tongyan Liu; Qianqian Li; Jiaru Yang; Rong-Long Wang; Shangce Gao (Environmental Modeling & Assessment, 2024)

The potential use of Zymomonas mobilis for the food industry - Lu Liu; Jian-Ting Li; Sheng-Hao Li; Lin-Pei Liu; Bo Wu; Yan-Wei Wang; Shi-hui Yang; Cheng-Han Chen; Fu-Rong Tan; Ming-Xiong He (Critical Reviews in Food Science and Nutrition, 2024)

Fate of sulfamethoxazole in wetland sediment under controlled redox conditions - Yujie He; Longxue Jiang; Xuan Wu; Wenhui Zhang; Yao Zong; Jiacheng Wang; Jinmei Chen; Jun Shan; Deyang Kong; Rong Ji (Water Research, 2024)

Modeling the long-range transmission of airborne bioaerosol releases in a high-density urban environment - Zhijian Dong; Zhijian Liu; Chenxing Hu; Yongjun Jin; Chenglin Ye; Yuchen He; Rui Rong (Urban Climate, 2024)

Risk assessment of exposure to 12 kinds of mycotoxins through consumption of Pericarpium Citri Reticulatae collected from Three Gorges Reservoir area of China - Wenting Wang; Yuan Yuan; Yingjie Ma; Rong Wu; Shixin He; Lingzhi He (Toxicon, 2024)

Global impact of enhanced-efficiency fertilizers on vegetable productivity and reactive nitrogen losses - Zhaolong Pan; Ping He; Daijia Fan; Rong Jiang; Daping Song; Lei Song; Wei Zhou; Wentian He (Science of The Total Environment, 2024)

Northward shift of Indian summer monsoon and intensifying winter westerlies cause stronger precipitation seasonality over Pamirs and its downstream basins in the 21st century - Jinping He; Keqin Duan; Shuangshuang Li; Wei Shang; Qiong Wang; Rong Chen; Yali Meng (Science of The Total Environment, 2024)

Recycling drinking water treatment sludge in construction and building materials: A review - Zhi-hai He; Bin Wang; Jin-yan Shi; Hui Rong; Hong-yu Tao; Ahmed Salah Jamal; Xu-dong Han (Science of The Total Environment, 2024)

Upcycling textile sludge into magnesium oxychloride cement: Physical properties, microstructure, and leaching behavior - Zhi-hai He; Ya-qian Ni; Jin-yan Shi; Hui Rong; Hong-yu Tao; Ahmed Salah Jamal (Science of The Total Environment, 2024)

Glutathione S-transferase directly metabolizes imidacloprid in the whitefly, Bemisia tabaci - Rong Zhang; Jing Yang; Jinyu Hu; Fengbo Yang; Jinjin Liang; Hu Xue; Xuegao Wei; Buli Fu; Mingjiao Huang; He Du; Chao Wang; Qi Su; et al. (Pesticide Biochemistry and Physiology, 2024)

Biodegradation of phenolic pollutants and bioaugmentation strategies: A review of current knowledge and future perspectives - Jiacheng Wang; Lidan Zhang; Yujie He; Rong Ji (Journal of Hazardous Materials, 2024)

Spartina alterniflora invasion altered phosphorus retention and microbial phosphate solubilization of the Minjiang estuary wetland in southeastern China - Yan-Zhen Lin; Qi-Qi Chen; Yi-Fan Qiu; Rong-Rong Xie; Hong Zhang; Yong Zhang; Jia-Bing Li; Yong-He Han (Journal of Environmental Management, 2024)

Large-scale production of graphene encapsulated silicon nanospheres as flexible anodes for lithium ion batteries - Yanlin Zhang; Dafang He; Junhong Lu; Jie Huang; Haoyang Jiang; Junfeng Rong; Guolin Hou; Haiqun Chen (Chemical Engineering Journal, 2024)

Surface water resource attenuation attribution and patterns in Hai River Basin - Qingming Wang; Yong Zhao; Hao Wang; Jiaqi Zhai; Yue Zhang; Fan He; Rong Liu; Mengyang Ma (Science China Earth Sciences, 2024)

Investigation of pathogen-laden aerosol aerodynamics and ventilation rates on their long-range transmission: A study on the Fangcang shelter hospital - Chuan Jiang; Zhijian Liu; Yongxin Wang; Guangpeng Yao; Shiyue Li; Rui Rong; Zhenyu Liang; Haiyang Liu; Jingwei Liu; Tongliang Wan; Junzhou He (Journal of Cleaner Production, 2024)

Oxygen vacancy mediation of BiOX (X=Cl, Br) towards enhanced photocatalytic CO2 reduction activity - Qiong Liu; Chengbo Bai; Die He; Xueting Wu; Yiping Wu; Rong Chen (Journal of Environmental Chemical Engineering, 2024)

Synchronous fluorescence spectra-based machine learning algorithm with quick and easy accessibility for simultaneous quantification of polycyclic aromatic hydrocarbons in edible oils - Jia-Wen Wei; Jia-Rong He; Shi-Yi Chen; Yi-Han Guo; Xuan-Zhu Huo; Nuan Zheng; Shuo-Hui Cao; Yao-Qun Li (Food Control, 2024)

Transport and release behaviors of PFOA in saturated and unsaturated porous media with biochar amendment - Haifeng Rong; Lei He; Meiping Tong (Environmental Pollution, 2024)

A green and eco-friendly method to enhance Bamboo flame resistance via calcium alginate assisted in-situ mineralization of hydroxyapatite - Lu He; Gege Bao; Xi Yu; Xiaofeng Zhang; Xiaobei Jin; Zixuan Yu; Ying He; Rong Zhang; Daochun Qin (Chemical Engineering Journal, 2024)

A human-specific insertion promotes cell proliferation and migration by enhancing TBC1D8B expression - Hui Zhao; Lin-Lin Liu; Jian Sun; Lian Jin; Hai-Bing Xie; Jian-Bo Li; Hui Xu; Dong-Dong Wu; Xiao-Lin Zhuang; Min-Sheng Peng; Ya-Jun Guo; Wei-Zhu Qian; et al. (Science China Life Sciences, 2024)

Impacts of land use and climate change on runoff in the Shaying River Basin based on SWAT model - Jie Tao; Yang Cao; Rong Gan; Qiting Zuo; Qingli Zhao; Yinxing He (Limnology, 2024)

Inflammatory cell death PANoptosis is induced by the anti-cancer curaxin CBL0137 via eliciting the assembly of ZBP1-associated PANoptosome - Ya-Ping Li; Zhi-Ya Zhou; Liang Yan; Yi-Ping You; Hua-Yu Ke; Tao Yuan; Hai-Yan Yang; Rong Xu; Li-Hui Xu; Dong-Yun Ouyang; Qing-Bing Zha; Xian-Hui He (Inflammation Research, 2024)

Dietary creatine promotes creatine reserves, protein deposition, and myofiber hyperplasia in muscle of juvenile largemouth bass (Micropterus salmoides) - Haodong Yu; Ya He; Mu Qin; Li Wang; Keming Rong; Xuezhen Zhang (Aquaculture, 2024)

Response of soil microbial properties in the life cycle of potatoes to organic substitution regimes in North China - Xiya Wang; Shicheng Zhao; Xinpeng Xu; Mengjiao Liu; Rong Jiang; Jun Zhang; Yu Duan; Ping He; Wei Zhou (Soil and Tillage Research, 2024)

Adaptation mechanisms of leaf vein traits to drought in grassland plants - Xiaochun Wang; Shuang Chen; Xue Yang; Rong Zhu; Miao Liu; Ruili Wang; Nianpeng He (Science of The Total Environment, 2024)

Underlying the inhibition mechanisms of sulfate and lincomycin on long-term anaerobic digestion: Microbial response and antibiotic resistance genes distribution - Li Xie; Jiaxin Zhu; Jing Xie; Jun Xu; Rong He; Wenbiao Wang (Science of The Total Environment, 2024)

Efficient perchlorate reduction in microaerobic environment facilitated by partner methane oxidizers - Pan-Long Lv; Chuan Jia; Chi-Hang Wei; He-Ping Zhao; Rong Chen (Journal of Hazardous Materials, 2024)

Different crystalline manganese dioxide and biochar co-conditioning aerobic composting: Reduced ammonia volatilization and improved organic fertilizer quality - Weijiang He; Shaopeng Rong; Jixiang Wang; Yingjie Zhao; Yunyi Liang; Junxia Huang; Lin Meng; Yanfang Feng; Lihong Xue (Journal of Hazardous Materials, 2024)

The effect of lactic acid bacteria fermentation on physicochemical properties of starch from fermented proso millet flour - Tongze Zhang; Siqi Hong; Jia-Rong Zhang; Pin-He Liu; Siyi Li; Zixian Wen; Jianwei Xiao; Guirong Zhang; Olivier Habimana; Nagendra P. Shah; Zhongquan Sui; Harold Corke (Food Chemistry, 2024)

Partial organic substitution for synthetic fertilizer improves soil fertility and crop yields while mitigating N2O emissions in wheat-maize rotation system - Gong Wu; Shuo Yang; Chong-sheng Luan; Qi Wu; Lei-li Lin; Xiao-xiao Li; Zhao Che; De-bao Zhou; Zhao-rong Dong; He Song (European Journal of Agronomy, 2024)

Controlling airborne pathogen within Fangcang shelter hospitals: Aerodynamic analysis of bioaerosols released from various locations through experiment and simulation - Chuan Jiang; Zhijian Liu; Xia Xiao; Haiyang Liu; Junzhou He; Rui Rong; Jingwei Liu; Zhenzhe Huang; Yongxin Wang (Building and Environment, 2024)

Damming-associated landscape change benefits a wind-dispersed pioneer plant species - Hang Ji; Yong-Rong He; Hong-Yue Li; Ling Lu; Jia-Hui Li; Jie Zou; Rong Wang; Jun-Yin Deng; Xiao-Yong Chen (New Forests, 2024)

Pelagibacterium flavum sp. nov., Isolated from Soil Sample - Xue-Mei Chen; Zu-Zhen Yang; Si-Rong He; Lian-Shuang Xiong; Qing Yuan; Shu-Ya Zuo; Cheng-Lin Jiang; Yi Jiang (Current Microbiology, 2024)

Biodegradability of PBAT/PLA coated paper and bioplastic bags under anaerobic digestion - Wei Peng; Rong Nie; Fan Lü; Hua Zhang; Pinjing He (Waste Management, 2024)

An empirical method for estimating TBM penetration rate using tunnelling specific energy - Lei She; Cheng-cheng Hu; Yan-long Li; She-rong Zhang; Chao Wang; Yu-jie Wang; Ming-ming He; Shi-min Li; Sheng-le Wang (Tunnelling and Underground Space Technology, 2024)

Uranium speciation and distribution on the surface of Shewanella putrefaciens in the presence of inorganic phosphate and zero-valent iron under anaerobic conditions - Guo-Xiu Xuan; Guo-Hao Zhang; Wen-Cai Cheng; Chun-Yan Ma; Qing-Rong Li; En-Tong Liu; Wen-Ge He; Fa-Qin Dong; Xiao-An Li; Zheng-Guo Chen; Xiao-Qin Nie (Science of The Total Environment, 2024)

Developing a highly efficient, environmentally friendly and cost-effective copper sulfide semiconductor sponge for nuclear wastewater treatment under one sun - Wencai Bai; Mengjiao Liu; Kaifu Yu; Xin Cao; Jie Lian; Zhibin Zhao; Yong Xiang; Baoliang Xu; Tao Chen; Rong He; Nan Sun; Wenkun Zhu (Journal of Environmental Chemical Engineering, 2024)

Introducing local-molecule trap in a cost-effective metal–organic framework for C2H2/CO2 separation - Xue-Qian Wu; Tao He; Peng-Dan Zhang; Jiamei Yu; Jian-Rong Li (Chemical Engineering Journal, 2024)

Rational construction of MOF-on-MOF heterojunction with an array of flexible two-dimensional microsheets for efficient CO2 photoreduction - Bing He; Ying-Jie Wang; Xuefeng Bai; He Bian; Yabo Xie; Rui Li; Jian-Rong Li (Chemical Engineering Journal, 2024)

Biochar’s role to achieve multi-pathway nitrogen removal in anammox systems: Insights from electron donation and selective microbial enrichment - Jingwei Fu; Qian Li; Mawuli Dzakpasu; Yifei He; Pengyu Zhou; Rong Chen; Yu-You Li (Chemical Engineering Journal, 2024)

Modelling adaptation measures to improve maize production and reduce soil N2O emissions under climate change in Northeast China - Daijia Fan; Daping Song; Rong Jiang; Ping He; Yaoyao Shi; Zhaolong Pan; Guoyuan Zou; Wentian He (Atmospheric Environment, 2024)

Ferroptosis: underlying mechanisms and involvement in neurodegenerative diseases - Yi Wang; HongJing Li; QianXiong He; Rong Zou; JinRui Cai; Lin Zhang (Apoptosis, 2024)

Lipid characteristics of lung tissue in silicosis rat model were studied based on lipid metabolomics - Hailan He; Rong Qi; Jie Cui; Mingming Liu; Bo Guan; Yufan Zhou; Yingshu Zhang; Xiaohui Hao; Hongli Wang; Heliang Liu (Toxicology Letters, 2024)

Occurrence, multiphase partitioning, drivers, and ecological risks of current-use herbicides in a river basin dominated by rice–vegetable rotations in tropical China - Huadong Tan; Qiao Xing; Ling Mo; Chunyuan Wu; Xiaoying Zhang; Xiaoyu He; Yuefu Liang; Rong Hao (Science of The Total Environment, 2024)

Enhancing the removal of chlorinated hydrocarbons from groundwater using a new BL5 microorganism with functional CS@ZVI materials - Zhiguo Chen; Wenqing Cao; Yan Li; Jingpeng Song; Yiyun Liu; Juncheng Liu; Rong Zhang; Rongxin Su; He Bai (Journal of Water Process Engineering, 2024)

Ecosystem health evaluation of urban rivers based on multitrophic aquatic organisms - Zhen Cui; Wenting Fan; Cheng Chen; Kangle Mo; Qiuwen Chen; Qiang Zhang; Rong He (Journal of Environmental Management, 2024)

Untargeted metabolomics analysis of non-volatile metabolites and dynamic changes of antioxidant capacity in Douchi with edible mushroom by-products - Pei-Xiu Rong; Xiao-Qin He; Mutamed Ayyash; Yi Liu; Ding-Tao Wu; Fang Geng; Hua-Bin Li; Siew Bee Ng; Hong-Yan Liu; Ren-You Gan (Food Chemistry, 2024)

Effects of phytase/ethanol treatment on aroma characteristics of rapeseed protein isolates - Yao Chen; Xuan Tao; Shengqing Hu; Rong He; Xingrong Ju; Zhigao Wang; Rotimi E. Aluko (Food Chemistry, 2024)

A pleiotropic SIS-based hydrogel with immunomodulation via NLRP3 inflammasome inhibition for diabetic bone regeneration - Ning Sheng; Fei Xing; Qing-Yi Zhang; Jie Tan; Rong Nie; Kai Huang; He-Xi Li; Yan-Lin Jiang; Bo Tan; Zhou Xiang; Hui-Qi Xie (Chemical Engineering Journal, 2024)

Microbial stratification protects denitrifying anaerobic methane oxidation archaea and bacteria from external oxygen shock in membrane biofilm reactor - Pan-Long Lv; Chuan Jia; Xu Guo; He-Ping Zhao; Rong Chen (Bioresource Technology, 2024)

A co-located QTL for seven spike architecture-related traits shows promising breeding use potential in common wheat (Triticum aestivum L.) - Jieguang Zhou; Qian Liu; Rong Tian; Huangxin Chen; Jian Wang; Yaoyao Yang; Conghao Zhao; Yanlin Liu; Huaping Tang; Mei Deng; Qiang Xu; Qiantao Jiang; et al. (Theoretical and Applied Genetics, 2024)

Genome dosage alteration caused by chromosome pyramiding and shuffling effects on karyotypic heterogeneity, reproductive diversity, and phenotypic variation in Zea–Tripsacum allopolyploids - Yingzheng Li; Xu Yan; Mingjun Cheng; Zizhou Wu; Qiyuan Zhang; Saifei Duan; Yong Zhou; Huaxiong Li; Shipeng Yang; Yulin Cheng; Wansong Li; Lulu Xu; et al. (Theoretical and Applied Genetics, 2024)

The benefit of omeprazole exposure on all-cause mortality and length of ICU/hospital stay might vary with age in critically ill pediatric patients: A cohort study - Fang-Fang Jiang; Yu Guo; Zheng Zhang; Sun-Jun Yin; Yu-Xin Fan; Yan-Hua Huang; Ya-Jia Li; Li-Rong Chen; Kai Qian; Gong-Hao He (European Journal of Clinical Pharmacology, 2024)

Soil pH differently affects N2O emissions from soils amended with chemical fertilizer and manure by modifying nitrification and denitrification in wheat-maize rotation system - Gong Wu; Fei Liang; Qi Wu; Xiao-Gang Feng; Wen-ding Shang; Hua-wei Li; Xiao-xiao Li; Zhao Che; Zhao-rong Dong; He Song (Biology and Fertility of Soils, 2024)

Degradation of polycyclic aromatic hydrocarbons in aquatic environments by a symbiotic system consisting of algae and bacteria: green and sustainable technology - Mengying Wang; Wenqing Zhang; Tao He; Lingyun Rong; Qi Yang (Archives of Microbiology, 2024)

Effect comparisons of different conditioners and microbial agents on the degradation of estrogens during dairy manure composting - Yan Li; Dong Zeng; Xiao-Lu Jiang; De-Chun He; Jia-Wu Hu; Zi-Wei Liang; Jia-Cheng Wang; Wang-Rong Liu (Chemosphere, 2023)

Advances, challenges, and prospects in microalgal-bacterial symbiosis system treating heavy metal wastewater - Xing-Rui Zhou; Rong Wang; Cong-Cong Tang; Cristiano Varrone; Zhang-Wei He; Zhi-Hua Li; Xiaochang C. Wang (Chemosphere, 2023)

B4C/Ce co-modified Ti/PbO2 dimensionally stable anode: Facile one-step electrodeposition preparation and highly efficient electrocatalytic degradation of tetracycline - Zeyi Wang; Rong Su; Maojie Zhao; Luyao Zhang; Lu Yang; Feng Xiao; Weishan Tang; Lichuan Chen; Ping He; Dingming Yang (Chemosphere, 2023)

A novel active packaging film containing citronella oil: Preparation, characterization, antimicrobial activity and application in grape preservation - Weijie Zhao; Changcheng Li; Weijia Ma; Ruiwen He; Yan Rong; Shovra Sarker; Qi Liu; Fang Tian (Food Packaging and Shelf Life, 2023)

Vertical heterojunction photodetector with self-powered broadband response and high performance - Yajie Han; Shujie Jiao; Jiangcheng Jing; Lei Chen; Zehao Shi; Ping Rong; Dongbo Wang; Shiyong Gao; Wen He; JinZhong Wang (Chemical Engineering Journal, 2023)

Tree species mixture effect on extracellular enzyme kinetics varies with enzyme type and soil depth in subtropical plantations - Xue-Li Jiang; Rong Mao; Zhong-Liang Li; Fu-Sheng Chen; Bin Xu; Jin He; Yu-Xin Huang; Xiang-Min Fang (Plant and Soil, 2023)

Improving Blood Monocyte Energy Metabolism Enhances Its Ability to Phagocytose Amyloid-β and Prevents Alzheimer’s Disease-Type Pathology and Cognitive Deficits - Zhi-Hao Liu; Yu-Di Bai; Zhong-Yuan Yu; Hui-Yun Li; Jie Liu; Cheng-Rong Tan; Gui-Hua Zeng; Yun-Feng Tu; Pu-Yang Sun; Yu-Juan Jia; Jin-Cai He; Yan-Jiang Wang; et al. (Neuroscience Bulletin, 2023)

Screening of small molecule compounds targeting hnRNPA2 protein - Yuan-Rong Zheng; Chao-Jie Wang; Ling Yang; Yu-Jun Zhang; Mei-Juan Fang; He Chang; Kai-Qiang Guo; Song-Lin Shi (Medicinal Chemistry Research, 2023)

Effects of Different Conditioners on Humus Composition and Humic Acid Structural Characteristics in Black Soil Under the Combined Application of Pig Manure and Straw - Shuang Zheng; Jing-Gui Wu; Jin-Rong Li; Juan Hu; Li He (Journal of Soil Science and Plant Nutrition, 2023)

Endophytic Bacillus sp. R1 and Its Roles in Assisting Phytoremediation and Alleviating the Toxicity of Aluminum Combined Phenanthrene Contaminations in Brassica napus - Li-rong Fang; Xue-cheng Yang; Chun-ya Wu; Kai Sun; Mallavarapu Megharaj; Wei He (Current Microbiology, 2023)

Triptolide induces PANoptosis in macrophages and causes organ injury in mice - Hong-Rui Zhang; Ya-Ping Li; Zi-Jian Shi; Qi-Qi Liang; Si-Yuan Chen; Yi-Ping You; Tao Yuan; Rong Xu; Li-Hui Xu; Dong-Yun Ouyang; Qing-Bing Zha; Xian-Hui He (Apoptosis, 2023)

Research progress of main synthetic catalysts used in biomass pyrolysis - Hongwei Rong; Penghong He; Yuxin Luo; Haizhen Cai; Mahmood Laghari; Dabin Guo; Yan Ren; Baihui Cui (Process Safety and Environmental Protection, 2023)

Over-expression of UDP-glycosyltransferase UGT353G2 confers resistance to neonicotinoids in whitefly (Bemisia tabaci) - Tian-hua Du; Cheng Yin; Lian-you Gui; Jin-jin Liang; Shao-nan Liu; Bu-li Fu; Chao He; Jing Yang; Xue-gao Wei; Pei-pan Gong; Ming-jiao Huang; Hu Xue; et al. (Pesticide Biochemistry and Physiology, 2023)

Selective galena depression mechanism of tea polyphenol in chalcopyrite flotation - Haiyang He; Jianjun Fang; Zhilian Qiu; Dianwen Liu; Haiyun Xie; Peilun Shen; Rong Peng; Liguo Peng; Shuang Qin; Shiqin Dong (Minerals Engineering, 2023)

Characteristics of landscape and erosion in the Eastern Pamir and their implications for regional fault connections - Yunpeng Wu; Rong Yang; Junqing He; Hanlin Chen; Xiubin Lin; Xuhua Shi; Kaixuan An; Chunyang Li; Shibao Gao; Yaguang Chen (Geomorphology, 2023)

Reducing airborne transmission of SARS-CoV-2 by an upper-room ultraviolet germicidal irradiation system in a hospital isolation environment - Haiyang Liu; Zhijian Liu; Junzhou He; Chenxing Hu; Rui Rong; Hao Han; Lingyun Wang; Desheng Wang (Environmental Research, 2023)

Revealing mechanisms of triclosan on the removal and distribution of nitrogen and phosphorus in microalgal-bacterial symbiosis system - Sheng-Long Chen; Tian-Yang Wang; Cong-Cong Tang; Rong Wang; Zhang-Wei He; Zhi-Hua Li; Yu Tian; Xiaochang C. Wang (Environmental Pollution, 2023)

Membrane fabrication and configuration design development of photothermal membrane distillation (PMD) - Guo-Rong Xu; Min Wang; Ke Xu; He-Li Zhao; Qian Liu (Desalination, 2023)

Efficient capture of iodine by charge-induced effect of nitrogen-rich ionic liquids - Shi-Jie Guo; Guo-Hao Zhang; Qiu-Hong Zhu; Chao Yu; Jia-Ying Liu; Xiao-Lan Yang; Song Qin; Nan-Rong Zhao; Ling He; Guo-Hong Tao (Chemical Engineering Journal, 2023)

Application of Induced Pluripotent Stem Cells in Malignant Solid Tumors - Rong He; Zhijie Weng; Yunkun Liu; Bingzhi Li; Wenxuan Wang; Wanrong Meng; Bo Li; Longjiang Li (Stem Cell Reviews and Reports, 2023)
In the past decade, induced pluripotent stem cells (iPSCs) technology has significantly progressed in studying malignant solid tumors. This technically feasible reprogramming techniques can reawaken sequestered dormant regions that regulate the fate of differentiated cells. Despite the evolving therapeutic modalities for malignant solid tumors, treatment outcomes have not been satisfactory. Recently, scientists attempted to apply induced pluripotent stem cell technology to cancer research, from modeling to treatment. Induced pluripotent stem cells derived from somatic cells, cancer cell lines, primary tumors, and individuals with an inherited propensity to develop cancer have shown great potential in cancer modeling, cell therapy, immunotherapy, and understanding tumor progression. This review summarizes the evolution of induced pluripotent stem cells technology and its applications in malignant solid tumor. Additionally, we discuss potential obstacles to induced pluripotent stem cell technology. Graphical Abstract

Failure Modes of Jointed Granite Subjected to Weak Dynamic Disturbance Under True-Triaxial Compression - Ben-Guo He; Lei Wang; Xia-Ting Feng; Rong-Li Zhen (Rock Mechanics and Rock Engineering, 2023)

Linear relationship between CH4 fluxes and atmospheric CO2 concentration levels controlled by rice biomass and soil methanogenic communities - Yuanyuan Wang; Zhenghua Hu; Shuqi He; Qiang Jing; Lidong Shen; Chao Liu; Zhurong Wu; Wei Huang; Guihua Lu; Rui Cao; Kezhi Zheng; Ning Dong; et al. (Nutrient Cycling in Agroecosystems, 2023)

Hydrogeochemical characterization and precursor anomalies of hot springs in the North Tianshan orogen - Zhihua Ding; Xiaocheng Zhou; Chengguo Wang; Jingchao Li; Miao He; Jiao Tian; Kayimu Saimaiernaji; Chengying Zhu; Wei Yan; Rong Ma; Xinyong Li; Na Li; et al. (Applied Geochemistry, 2023)

G-quadruplex based biosensors for the detection of food contaminants - Rong Du; Xiebingqing Yang; Ping Jin; Yahui Guo; Yuliang Cheng; Hang Yu; Yunfei Xie; He Qian; Weirong Yao (Critical Reviews in Food Science and Nutrition, 2023)

Surface acidic sites strengthened core-shell HC@MnO2 for enhanced gaseous ammonia adsorption - Weijiang He; Jingling Lu; Nan Zhang; Yu Zhou; Danni Ding; Yanfang Feng; Shaopeng Rong (Chemosphere, 2023)

The impact of crop residue return on the food–carbon–water–energy nexus in a rice–wheat rotation system under climate warming - Li-Yao Zhou; Yong-he Zhu; Zheng-Rong Kan; Feng-Min Li; Feng Zhang (Science of The Total Environment, 2023)

A novel semi-empirical model for crop leaf area index retrieval using SAR co- and cross-polarizations - Rong Wang; Jing M. Chen; Liming He; Jane Liu; Jiali Shang; Jiangui Liu; Taifeng Dong (Remote Sensing of Environment, 2023)

Lack of the CCT domain changes the ability of mango MiCOL14A to resist salt and drought stress in Arabidopsis - Shu-Quan Chen; Cong Luo; Yuan Liu; Rong-Zhen Liang; Xing Huang; Ting-Ting Lu; Yi-Hang Guo; Ruo-Yan Li; Chu-Ting Huang; Zhuo Wang; Xin-Hua He (Plant Science, 2023)

Parallel river channel routing computation based on a straightforward domain decomposition of river networks - Yong-He Liu; Zong-Liang Yang; Pei-Rong Lin (Journal of Hydrology, 2023)

In-situ constructing amidoxime groups on metal-free g-C3N4 to enhance chemisorption, light absorption, and carrier separation for efficient photo-assisted uranium(VI) extraction - Kaifu Yu; Yi Li; Xin Cao; Ruixiang Wang; Li Zhou; Linzhen Wu; Ningning He; Jia Lei; Dengjiang Fu; Tao Chen; Rong He; Wenkun Zhu (Journal of Hazardous Materials, 2023)

Activation of ozone by CoFe-LDO-BC heterogeneous catalyst for efficient mineralization of methylene blue: The role of oxygen vacancies and acidic sites - Nianbo Zhang; Baoyong Zhang; Ao He; Hao Sun; Chen Wang; Zunqing Wen; Guihuan Yan; Yunqian Ma; Rong Xue (Journal of Environmental Chemical Engineering, 2023)

Identification of umami peptides from Wuding chicken by Nano-HPLC-MS/MS and insights into the umami taste mechanisms - Rong Jia; Ying He; Guozhou Liao; Zijiang Yang; Dahai Gu; Yuehong Pu; Ming Huang; Guiying Wang (Food Research International, 2023)

Study on the hypolipidemic activity of rapeseed protein-derived peptides - Feiyu Yang; Jiaqiang Huang; Haiyan He; Xingrong Ju; Ying Ji; Feng Deng; Zhigao Wang; Rong He (Food Chemistry, 2023)

Regulating dynamic equilibrium of active hydrogen for super-efficient nitrate electroreduction to ammonia - Yang Gao; Rong Wang; Yudong Li; Enshan Han; Maosen Song; Ziyi Yang; Feng Guo; Yanzhen He; Xiaohui Yang (Chemical Engineering Journal, 2023)

Insights into roles of triclosan in microalgal–bacterial symbiosis system treating wastewater - Cong-Cong Tang; Tian-Yang Wang; Rong Wang; Cristiano Varrone; Zixuan Gan; Zhang-Wei He; Zhi-Hua Li; Xiaochang C. Wang (Bioresource Technology, 2023)

Sensitive temperature changes on the Tibetan Plateau in response to global warming - Yali Meng; Keqin Duan; Peihong Shi; Wei Shang; Shuangshuang Li; Ying Cheng; Li Xing; Rong Chen; Jinping He (Atmospheric Research, 2023)

In vitro adventitious regeneration and plantlet transplantation of Atractylodes chinensis (DC.) Koidz., a valuable medicinal plant - Wenhao Jia; Junbo Rong; Mengyang Zhang; Wenyue Peng; Xutong He; Xiujuan Lei; Yingping Wang (Plant Cell, Tissue and Organ Culture (PCTOC), 2023)

Citrus medica var. Sarcodactylus (Siebold ex Hoola van Nooten) Swingle: an insight into its botany, traditional uses, phytochemistry, and pharmacological properties - Qin-Ge Ma; Jie Chen; Li-Hua Chen; Guang Wu; Mei-Ning Zhu; Neng-Xin He; Qin-Yuan Wang; Zhi-Pei Sang; Cai-Qing Zhu; Yong-Zhong Wu; Rong-Rui Wei (Phytochemistry Reviews, 2023)

Genetic parameter estimates for estrus duration and urinary hormone levels in captive female giant pandas - He Huang; Shiyi Chen; Yongyou Feng; Zongjin Ye; Rong Hou; Yuliang Liu; Li Luo; Xiangming Huang; Kongju Wu; James Ayala; Kailai Cai; Jingchao Lan (Mammalian Biology, 2023)

Bacillus amyloliquefaciens Induces Resistance in Tobacco Against Powdery Mildew Pathogen Erysiphe cichoracearum - Rong Jiao; Ayesha Ahmed; Pengfei He; Shahzad Munir; Yixin Wu; Junwei Wang; Pengbo He; Ge Wang; Huanwen Yang; Jing Zhao; Canhua Lu; Yongzhan Cai; et al. (Journal of Plant Growth Regulation, 2023)

Pyroptosis: the potential eye of the storm in adult-onset Still’s disease - Xinglan He; Ruixuan You; Yaqian Shi; Zhuotong Zeng; Bingsi Tang; Jiangfan Yu; Yangfan Xiao; Rong Xiao (Inflammopharmacology, 2023)

Which molecular marker is better? Comparative analyses of COI and ITS2 in molecular identification of Trichogramma (Hymenoptera: Trichogrammatidae) - Ao-Kai Wang; Fang-Yi Li; De-Sen Wang; Yu-Rong He; Yuan-Xi Li; Zhi-Chao Yan (BioControl, 2023)

Effects of nano-silicon dioxide on minerals, antioxidant enzymes, and growth in bitter gourd seedlings under cadmium stress - Hongyan Sun; Bo Zhang; Zhijiang Rong; Songjie He; Yifan Gao; Jia Yu; Qingmei Zhang (Acta Physiologiae Plantarum, 2023)

Fabrication and optimization of passive flexible ammonia sensor for aquatic supply chain monitoring based on adaptive parameter adjustment artificial neural network (APA-ANN) - Jinchao Xu; Boyu Mu; Luwei Zhang; Rong Chai; Yanfu He; Xiaoshuan Zhang (Computers and Electronics in Agriculture, 2023)

P24-42: A new generation of fully human anti-CTLA-4 heavy chain-only, Porustobart, shows superior safety in nonclinical study and clinical trials - J. Rong; L. Ding; F. Chen; J. Zhao; Y. He; Y. Rong; V. Chen (Toxicology Letters, 2023)

Serum levels of IL-6/IL-10/GLDH may be early recognition markers of anti-tuberculosis drugs (ATB) -induced liver injury - Huai-Rong Xiang; Yun Li; Xuan Cheng; Bei He; Hua-Min Li; Qi-Zhi Zhang; Bin Wang; Wen-Xing Peng (Toxicology and Applied Pharmacology, 2023)

Transcriptomics reveals key regulatory pathways and genes associated with skin diseases induced by face paint usage - Bin Wang; Zhaohao Zheng; Ling Chen; Wenhui Zhang; Yujie He; Bing Wu; Rong Ji (Science of The Total Environment, 2023)

Freeze-thaw treatment of bacteria significantly affects bacterial transport behaviors in both saturated and unsaturated porous media: Deep investigation the roles of flagella and extracellular polymeric substances - Lei He; Jianmei Qin; Jia Guo; Shuai Wang; Haifeng Rong; Meiping Tong (Science of The Total Environment, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

Understanding key genetic make-up of different coat colour in Bayinbuluke sheep through a comparative transcriptome profiling analysis - Lihua Zhang; Long Liang; Xuemei Zhang; Wen Rong Li; Haiying Li; Sangang He (Small Ruminant Research, 2023)

A GC/C/IRMS-based method for position-specific carbon isotopic analysis of saturated long chain fatty acids - Yu Zhao; Ran Ma; Yaoting Qi; Rong He; Zhenyu Zhu; Bo Wang; Ying Wang; Qiulin Yan; Maxime Julien; Youping Zhou (Organic Geochemistry, 2023)

The early Late Triassic Yumen mafic rocks in the eastern Tethyan Himalaya: A record of the progressive opening of the Yarlung Zangbo Neo-Tethyan Ocean - Wei-Liang Liu; Zhong-Xi Xia; Yun Zhong; Chris Yakymchuk; Zhou-Rong Cai; He Xiao; Xing Liao; Chi Yan; Ru-Xin Ding; Jin-Nan Liu (Lithos, 2023)

Black phosphorus quantum dots induced ferroptosis in lung cell via increasing lipid peroxidation and iron accumulation - Liangding Dou; Rong Liu; Zhaojizhe Wang; Zhi Huang; Lei Wang; Mo Lin; Xin Hou; Jinwen Zhang; Tantan Cheng; Qi He; Dai Wang; Dongbei Guo; et al. (Food and Chemical Toxicology, 2023)

Multiomics reveals new biomarkers and mechanistic insights into the combined toxicity effects of 2,2′,4,4′,5,5′-hexachlorobiphenyl and atrazine exposures in MCF-7 cells - Yu-Shun Lu; Xing Wen; Ju Chen; Xiao-Rong He; Jiang Yu; Jing Qiu; Yong-Zhong Qian; Yan-Yang Xu (Environmental Pollution, 2023)

Zn anode surface engineering for stable zinc-ion batteries: Carbon dots incorporated mesoporous TiO2 as a coating layer - Tian-Bing Song; Qian-Li Ma; Xi-Rong Zhang; Jia-Wen Ni; Tian-Le He; Huan-Ming Xiong (Chemical Engineering Journal, 2023)

Progress and perspective in enrichment and separation of radionuclide uranium by biomass functional materials - Jia Lei; Huanhuan Liu; Li Zhou; Yazhou Wang; Kaifu Yu; Hui Zhu; Bo Wang; Mengxuan Zang; Jian Zhou; Rong He; Wenkun Zhu (Chemical Engineering Journal, 2023)

Identification and evaluation of a novel PARP1 inhibitor for the treatment of triple-negative breast cancer - Rong Gong; ZhongYe Ma; LinHao He; ShiLong Jiang; DongSheng Cao; Yan Cheng (Chemico-Biological Interactions, 2023)

Influence of GI configurations and wall thermal effects on flow structure and pollutant dispersion within urban street canyons - Peng-Yi Cui; Rong Ji; Lai He; Zhen Zhang; Yang Luo; Yong Yang; Yuan-Dong Huang (Building and Environment, 2023)

Nitidine chloride regulates cell function of bladder cancer in vitro through downregulating Lymphocyte antigen 75 - Shi-shuo Wang; Gao-qiang Zhai; Zhi-guang Huang; Jia-yuan Luo; Juan He; Jie-zhuang Huang; Ling Yang; Chu-nan Xiao; Su-li Li; Kai-rong Chen; Yan-yu Chen; Han-chu Ji; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)

One-step electrodeposition preparation of boron nitride and samarium co-modified Ti/PbO2 anode with ultra-long lifetime: highly efficient degradation of lincomycin wastewater - Maojie Zhao; Mengqi Yang; Peilin Yang; Rong Su; Feng Xiao; Ping He; Hongquan Deng; Tinghong Zhang; Bin Jia (Environmental Science and Pollution Research, 2023)

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

Novel_miR-1517 mediates CYP6CM1 to regulate imidacloprid resistance in Bemisia tabaci (Hemiptera: Gennadius) - Pei-Pan Gong; Xue-Gao Wei; Shao-Nan Liu; Jing Yang; Bu-Li Fu; Jin-Jin Liang; Ming-Jiao Huang; Tian-Hua Du; Cheng Yin; Yao Ji; Chao He; Jin-Yu Hu; et al. (Pesticide Biochemistry and Physiology, 2023)

Cytochrome P450 CYP6DB3 was involved in thiamethoxam and imidacloprid resistance in Bemisia tabaci Q (Hemiptera: Aleyrodidae) - Xuegao Wei; Jinyu Hu; Jing Yang; Cheng Yin; Tianhua Du; Mingjiao Huang; Buli Fu; Peipan Gong; Jinjin Liang; Shaonan Liu; Hu Xue; Chao He; et al. (Pesticide Biochemistry and Physiology, 2023)

Energy and exergy assessments of supercritical water oxidation of wet organic wastes under hydrothermal flames with a Y-shape reactor for power generation - Fengming Zhang; Yang He; Yuxin Qiu; Weiqing Rong (Fuel, 2023)

Cotransport of different electrically charged microplastics with PFOA in saturated porous media - Haifeng Rong; Jianmei Qin; Lei He; Meiping Tong (Environmental Pollution, 2023)

Interaction of metabolism-related pathway gene variants with bisphenol A exposure on serum lipid profiles - Heng He; Fuwei Zhang; Shuang Zhou; Shanshan Zhang; Lu Wang; Jiaoyuan Li; Qiang Zeng; Ying Zhu; Jianbo Tian; Jiang Chang; Liming Cheng; Qing Lu; et al. (Environmental Toxicology and Pharmacology, 2023)

Strong and continuous MXene/sodium alginate composite fibers prepared by immersion rotary jet spinning process with outstanding electromagnetic interference shielding performance - Guoxin Zhao; Chao Sui; Linlin Miao; Junjiao Li; Lei Wen; Gong Cheng; Chenxi Zhao; Weizhe Hao; Yuna Sang; Jiaxuan Li; Zhuochao Zhang; Yushun Zhao; et al. (Chemical Engineering Journal, 2023)

A 3D phytic acid cross-linked high-porous conductive hydrogel integrating g-C3N4 for electrochemical multiplex sensing of heavy metal ions - Lu Xiao; Yulan Zhao; Gang Chang; Huiling Yan; Rong Zou; Xiuhua Zhang; Shengfu Wang; Hanping He (Analytica Chimica Acta, 2023)

High-resolution forest age mapping based on forest height maps derived from GEDI and ICESat-2 space-borne lidar data - Xudong Lin; Rong Shang; Jing M. Chen; Guoshuai Zhao; Xiaoping Zhang; Yiping Huang; Guirui Yu; Nianpeng He; Li Xu; Wenzhe Jiao (Agricultural and Forest Meteorology, 2023)

Natural polymer Nicandra physaloides (L.) Gaertn seed gum mediated assembly of hydroxyapatite assembly as versatile sponge for water pollution control - Xudong Wu; Yazhou Wang; Li Zhou; Chengkun Cai; Mingfang Hu; Xiaofang Yu; Rong He; Wenkun Zhu (Journal of Cleaner Production, 2023)

Preparation and mechanism of carbon felt supported iron trioxide and zero-valent iron for enhancing anaerobic digestion performance - Zheng-Wei Wang; Chun-Hai WEI; Hua-Rong Yu; Fang-Shu Qu; Hong-Wei Rong; Jun-Guo He; Guang-Li Liu; Xia Huang; Huu Hao Ngo (Chemical Engineering Journal, 2023)

A hierarchical In2O3@ZIF-67 architecture with upgraded CO2 photoreduction performances - Ying-Jie Wang; Bing He; Dejun Ma; Rui Li; Yabo Xie; Jian-Rong Li (Chemical Engineering Journal, 2023)

Synergistic effect of elevated glucose levels with SARS-CoV-2 spike protein induced NOX-dependent ROS production in endothelial cells - Jiahao Zhang; Li He; Rong Huang; Juan Felipe Alvarez; David H. Yang; Qihao Sun; Fengqin Wang; Zhiyong Peng; Nanhui Jiang; Lianjiu Su (Molecular Biology Reports, 2023)

“Ship-port-country” multi-dimensional research on the fine analysis of China's LNG trade - Zhaojin Yan; Guanghao Yang; Rong He; Hui Yang; Hui Ci (Journal of Transport Geography, 2023)

Ag@Bi5O7I nanoparticles deposited on Bi(OH)3 nanosheets for boosting photocatalytic antibacterial activity under visible light irradiation - Qinghan Chen; Li Wang; Dehui He; Bo Xiao; Xia Ran; Rong Li; Hong Xu; Jian Feng (Journal of Environmental Chemical Engineering, 2023)

Multilayer Zn nanosheets promote electrochemical CO2 reduction to CO in KCl electrolyte - Chen Wang; Ao He; Na Wang; Hao Sun; Nianbo Zhang; Yunqian Ma; Guihuan Yan; Rong Xue (Journal of Environmental Chemical Engineering, 2023)

Variations in the motility and biofilm formation abilities of Escherichia coli O157:H7 during noodle processing - Xiaohua He; Heer Ding; Zenghui Gao; Xiaofeng Zhang; Rong Wu; Ke Li (Food Research International, 2023)

Construction of α-MnO2/g-C3N4 Z-scheme heterojunction for photothermal synergistic catalytic decomposition of formaldehyde - Nan Zhang; Weijiang He; Zeyi Cheng; Jingling Lu; Yu Zhou; Danni Ding; Shaopeng Rong (Chemical Engineering Journal, 2023)

Manganese oxide nanocrystals embedded porous Graphene-like network for electrosynthesis of H2O2 and construction of Self-powered aptasensor - Chuanpan Guo; Yiming Ruan; Shuai Zhang; Lun Kan; Heng Bian; Feilong Rong; Linghao He; Dongsheng Li; Miao Du; Zhihong Zhang (Chemical Engineering Journal, 2023)

Development of heterogenous electro-Fenton process with immobilized FeWO4 catalyst for the degradation of tetracycline and the treatment of crude oil tank cleaning wastewater in neutral medium - Yanyang Chu; Chang Liu; Rong Wang; He Chen (Chemical Engineering Journal, 2023)

Coaxial electrospun nanofibrous substrates with tunable wettability for constructing cucurbit[n]uril-embedded organic solvent nanofiltration membranes - Qian Wang; Qin-Yuan He; Liu-Lin Zhao; Yue Wang; Rong Fang; Cong Luo; Wei-Tong Lu; Hong-Ya Jiang; Shi-Peng Sun; Xue-Li Cao (Chemical Engineering Journal, 2023)

An endogenous neuropeptide hormone assists cancer cells in escaping from immune surveillance - Chang-Yu Yan; Yan-Ping Wu; Yi-Fang Li; Rong-Rong He (Science China Life Sciences, 2023)

Bacterial Inhibition Mechanism of Rhamnolipid-Modified β-Carotene/Rutinoside Complex Liposomes - Ying Ji; Rong He (Indian Journal of Microbiology, 2023)

Grass harvesting eliminates the beneficial effects of legume addition on soil nematode communities in a tall grass pasture - Jie Zhao; Wei Zhang; Xin Liu; Rong Yang; Dan Xiao; Xunyang He; Kelin Wang (Agriculture, Ecosystems & Environment, 2023)

Improving potato productivity and mitigating nitrogen losses using enhanced-efficiency fertilizers: A global meta-analysis - Zhaolong Pan; Daijia Fan; Rong Jiang; Naeem Abbasi; Daping Song; Guoyuan Zou; Dan Wei; Ping He; Wentian He (Agriculture, Ecosystems & Environment, 2023)

Corrigendum to “Promotional effects of calcination temperature and H2O on the catalytic activity of Al-substituted MnAlO catalysts for low-temperature acetone oxidation” [Chemosphere 301 (2022) 134722] - Wan-Peng Zhang; Kun Wu; Junyi Zhao; Jun He; Leiping Wang; Hang Xiao; Jian-Bing Guo; Jian-Rong Li (Chemosphere, 2023)

Quantum neuronal sensing of quantum many-body states on a 61-qubit programmable superconducting processor - Ming Gong; He-Liang Huang; Shiyu Wang; Chu Guo; Shaowei Li; Yulin Wu; Qingling Zhu; Youwei Zhao; Shaojun Guo; Haoran Qian; Yangsen Ye; Chen Zha; et al. (Science Bulletin, 2023)

Zinc efficiently extracted from zinc calcine by reduced wet grinding: ZnFe2O4 to ZnO and Fe3O4 - Shaoqin Chen; Xiangfei Zeng; Qian Liang; Ling Hu; Shuyuan Chen; Dejun He; Yunhui Han; Zhisheng Zhao; Rong Huang; Yin Huang; Songshan Zhou; Jiqin Wang; et al. (Journal of Cleaner Production, 2023)

QTL-seq and transcriptomic integrative analyses reveal two positively regulated genes that control the low-temperature germination ability of MTP–maize introgression lines - Ru-Yu He; Jun-Jun Zheng; Yu Chen; Ze-Yang Pan; Tao Yang; Yang Zhou; Xiao-Feng Li; Xinyi Nan; Ying-Zheng Li; Ming-Jun Cheng; Yan Li; Yang Li; et al. (Theoretical and Applied Genetics, 2023)

Plant succession and geo-topography determined forest soil P and nine fraction-Ps across a larch forest chronosequence in the northmost region of China - Xudong Cao; Qianru Ji; Chenhui Wei; Lu Xiao; Peng Zhang; Rong Mao; Xingyuan He; Wenjie Wang (Plant and Soil, 2023)

DNA damage and up-regulation of PARP-1 induced by columbin in vitro and in vivo - Yufen Liao; Xin Wang; Guangyun Ran; Shiyu Zhang; Chutian Wu; Rong Tan; Ying Liu; Yan He; Ting Liu; Zhongxiu Wu; Ying Peng; Weiwei Li; et al. (Toxicology Letters, 2023)

Generation of condensate bubble aphrons (CBA) by partially vaporized condensate to enhance oil removal from produced water - Ce Wang; Yuling Lü; Tianxu Ye; Feng Rong; Limin He (Process Safety and Environmental Protection, 2023)

Complete genome sequence of one novel marine Pseudomonas sp. BSw22131 growing with dimethylsulfoniopropionate (DMSP) as the sole carbon source - Ting Hu; Yin-Xin Zeng; Yi-He Zhang; Yu Du; Wei Han; Hui-Rong Li; Wei Luo (Marine Genomics, 2023)

Enhancement of acidic sites in layered MnO2 for the highly efficient selective catalytic oxidation of gaseous ammonia - Yu Zhou; Shaopeng Rong; Huifang Xie; Yanfang Feng; Danni Ding; Weijiang He; Nan Zhang; Jingling Lu (Journal of Environmental Chemical Engineering, 2023)

Hollow urchin-shaped NCM811 ternary-structure for high rate charge/discharge capability and efficient CO2 adsorption - Fan-Ming Yang; Xiao-Yao Zhou; Xi-Da Li; Zhi-Cheng Yi; Rong Feng; Guo-Wen He (Journal of Environmental Chemical Engineering, 2023)

Efficient removal of trace uranium from nuclear effluents using irradiation-functionalized fibrous adsorbents with very high salt tolerance - Yulong He; Liuhua Mu; Minglei Wang; Lijun Hu; Wanning Ren; Xuanzhi Mao; Xinxin Feng; Mingxing Zhang; Rong Li; Zhe Xing; Jiangtao Hu; Guozhong Wu (Chemical Engineering Journal, 2023)

Interaction Between the Glymphatic System and α-Synuclein in Parkinson’s Disease - Yu Zhang; Cui Zhang; Xu-Zhong He; Zhen-Hua Li; Jing-Cai Meng; Rui-Ting Mao; Xin Li; Rong Xue; Qian Gui; Guo-Xing Zhang; Lin-Hui Wang (Molecular Neurobiology, 2023)

Activating α7nAChR helps post-myocardial infarction healing by regulating macrophage polarization via the STAT3 signaling pathway - Xiao-Hui Niu; Rong-Hua Liu; Xiao Lv; Rui-Lin He; Fang-Zhou Lv; Shu-Jie Wu; Xu-Qing Li; Lei Li; Jia-Feng Lin (Inflammation Research, 2023)

Retraction Note: Emerging protective roles of shengmai injection in septic cardiomyopathy in mice by inducing myocardial mitochondrial autophagy via caspase-3/Beclin-1 axis - Yan Cao; Xiaotong Han; Hongwei Pan; Yu Jiang; Xiang Peng; Weiwei Xiao; Jingjing Rong; Fang Chen; Jin He; Lianhong Zou; Yi Tang; Yanfang Pei; et al. (Inflammation Research, 2023)

Assessing the consistency of crop leaf area index derived from seasonal Sentinel-2 and Landsat 8 imagery over Manitoba, Canada - Taifeng Dong; Jane Liu; Jiangui Liu; Liming He; Rong Wang; Budong Qian; Heather McNairn; Jarrett Powers; Yichao Shi; Jing M Chen; Jiali Shang (Agricultural and Forest Meteorology, 2023)

Real-time tracking and counting of grape clusters in the field based on channel pruning with YOLOv5s - Lei Shen; Jinya Su; Runtian He; Lijie Song; Rong Huang; Yulin Fang; Yuyang Song; Baofeng Su (Computers and Electronics in Agriculture, 2023)

Global photosynthetic capacity of C3 biomes retrieved from solar-induced chlorophyll fluorescence and leaf chlorophyll content - Yihong Liu; Jing M. Chen; Liming He; Rong Wang; Nicholas G. Smith; Trevor F. Keenan; Cheryl Rogers; Wenyu Li; Jiye Leng (Remote Sensing of Environment, 2023)

Spatiotemporal variation and driving factors of water quality in Yunnan-Guizhou plateau lakes, China - Jiao Ran; Rong Xiang; Jia He; Binghui Zheng (Journal of Contaminant Hydrology, 2023)

Shaking table tests and seismic assessment of a full-scale precast concrete sandwich wall panel structure with bolt connections - Jia-Xuan He; Zhao-Dong Xu; Lian-Yu Zhang; Zhi-Hua Lin; Zhong-Wei Hu; Qiang-Qiang Li; Yao-Rong Dong (Engineering Structures, 2023)

Self-oxidation cycle of oxidized red phosphorus for regeneration of binding sites enables efficient uranium extraction in tributylphosphate-kerosene system - Yingtong Lv; Ru Cheng; Guolin Yang; Wang Liu; Jingye Zhang; Xiaofang Yu; Wencai Bai; Rong He; Wenkun Zhu (Chemical Engineering Journal, 2023)

Dorsal root ganglia P2X4 and P2X7 receptors contribute to diabetes-induced hyperalgesia and the downregulation of electroacupuncture on P2X4 and P2X7 - Qun-qi Hu; Xiao-fen He; Yi-qi Ma; Li-qian Ma; Si-ying Qu; Han-zhi Wang; Yu-rong Kang; Lu-hang Chen; Xiang Li; Bo-yu Liu; Xiao-mei Shao; Jun-fan Fang; et al. (Purinergic Signalling, 2023)

Inhibition of phosphorylated calcium/calmodulin-dependent protein kinase IIα relieves streptozotocin-induced diabetic neuropathic pain through regulation of P2X3 receptor in dorsal root ganglia - Xiao-fen He; Yu-rong Kang; Xue-yu Fei; Lu-hang Chen; Xiang Li; Yi-qi Ma; Qun-qi Hu; Si-ying Qu; Han-zhi Wang; Xiao-mei Shao; Bo-yi Liu; Yi-Liang; et al. (Purinergic Signalling, 2023)
Diabetic neuropathic pain (DNP) is frequent among patients with diabetes. We previously showed that P2X3 upregulation in dorsal root ganglia (DRG) plays a role in streptozotocin (STZ)-induced DNP but the underlying mechanism is unclear. Here, a rat model of DNP was established by a single injection of STZ (65 mg/kg). Fasting blood glucose was significantly elevated from the 1 st to 3 rd week. Paw withdrawal thresholds (PWTs) and paw withdrawal latencies (PWLs) in diabetic rats significantly reduced from the 2 nd to 3 rd week. Western blot analysis revealed that elevated p-CaMKIIα levels in the DRG of DNP rats were accompanied by pain-associated behaviors while CaMKIIα levels were unchanged. Immunofluorescence revealed significant increase in the proportion of p-CaMKIIα immune positive DRG neurons (stained with NeuN) in the 2 nd and 3 rd week and p-CaMKIIα was co-expressed with P2X3 in DNP rats. KN93, a CaMKII antagonist, significantly reduce mechanical hyperalgesia and thermal hyperalgesia and these effects varied dose-dependently, and suppressed p-CaMKIIα and P2X3 upregulation in the DRGs of DNP rats. These results revealed that the p-CaMKIIα upregulation in DRG is involved in DNP, which possibly mediated P2X3 upregulation, indicating CaMKIIα may be an effective pharmacological target for DNP management.

Advances in post-operative prognostic models for hepatocellular carcinoma - Ziqin He; Xiaomin She; Ziyu Liu; Xing Gao; Lu Lu; Julu Huang; Cheng Lu; Yan Lin; Rong Liang; Jiazhou Ye (Journal of Zhejiang University-SCIENCE B, 2023)

Effect of super-absorbent polymer on swelling pressure of compacted bentonite infiltrated by alkaline solutions - Zhang-Rong Liu; Wei-Min Ye; He-Hua Zhu; Qiong Wang; Yong-Gui Chen (Applied Clay Science, 2023)

Pipeline positioning by the surface-to-borehole electromagnetic induction method in a clayey deposit - Guo-Wei Li; Zhi-Ming Ye; Yang Zhou; Guan-Jun He; Guang-Yu Liu; Xin-Rong He (Applied Geophysics, 2023)

Geographical distance, host evolutionary history and diet drive gut microbiome diversity of fish across the Yellow River - Baozhu Pan; Xu Han; Ke Yu; He Sun; Rong Mu; Chun‐Ang Lian (Molecular Ecology, 2023)
Fish represent a large part of the taxonomic diversity of vertebrates and are of high commercial value. However, the factors influencing the gut microbiota composition of freshwater fish over large spatial scales remain unclear. Therefore, this study explored gut microbiome diversity in 24 fish species from the Yellow River, which spans over 1500 km across China. The results showed that geographical distance, host phylogeny and diet significantly influenced gut microbial community diversity, whereas sex, body length and body weight had minimal influence. Geographical distance was the primary factor shaping gut microbiota, and dissimilarity in microbial community structure increased with an increase in geographical distance, which was mainly driven by dispersal limitation. The microbial communities were more homogeneous at higher host taxonomic resolutions due to the dominant role of homogeneous selection in community convergence. Phylosymbiosis was observed across all host species, with a stronger pattern in Cypriniformes, which harbour host‐specific microbial taxa. Host diet explained little variation in gut microbiome diversity, although it was significant for all diversity metrics tested. These findings collectively suggest that the geographical and host‐based patterns of fish gut microbiota tend to be shaped by different ecological forces across the Yellow River. The present work provides a robust assessment of multiple factors driving fish gut microbial community assembly and offers insight into the mechanisms underlying shifts in fish gut microbiota in rivers across large spatial scales.

Risk assessment and environmental determinants of urinary phthalate metabolites in pregnant women in Southwest China - Nian Wu; Lin Tao; Kunming Tian; Xia Wang; Caidie He; Songlin An; Yingkuan Tian; Xiang Liu; Wei Chen; Haonan Zhang; Pei Xu; Dengqing Liao; et al. (Environmental Science and Pollution Research, 2023)

Blasting dust diffuse characteristics of spiral tunnel and dust distribution model: similar experiment and numerical modeling - Rong Liu; Deyi Jiang; Jie Chen; Song Ren; Jinyang Fan; Yi He (Environmental Science and Pollution Research, 2023)

Ship Trajectory Clustering Based on Trajectory Resampling and Enhanced BIRCH Algorithm - Zhaojin Yan; Guanghao Yang; Rong He; Hui Yang; Hui Ci; Ran Wang (Journal of Marine Science and Engineering, 2023)
Automatic identification systems (AIS) provides massive ship trajectory data for maritime traffic management, route planning, and other research. In order to explore the valuable ship traffic characteristics contained implicitly in massive AIS data, a ship trajectory clustering method based on ship trajectory resampling and enhanced BIRCH (Balanced Iterative Reducing and Clustering using Hierarchies) algorithm is proposed. The method has been tested using 764,393 AIS trajectory points of 13,845 ships in the waters of the Taiwan Strait of China, and 832 ship trajectories have been generated and clustered to obtain 172 classes of ship trajectory line clusters among 40 port pairs. The experimental results show that the proposed method has exhibited a good clustering effect on ship trajectories. Compared with the existing ship trajectory clustering methods, the proposed method can more efficiently detect and identify differences between trajectories with largely similar spatial distribution characteristics, so as to obtain legitimate clustering results. In addition, this study has constructed the main ship navigation routes between ports based on the extracted ship trajectory line clusters, and the constructed main routes are directional, refined, and rich in content compared with the existing ship routes. This research provides theoretical and technical support for ship route planning and maritime traffic management.

A 40 % paddy surface soil organic carbon increase after 5-year no-tillage is linked with shifts in soil bacterial composition and functions - Jian-Ying Qi; Xiang-Bin Yao; Jian Lu; Long-Xin He; Jun-Li Cao; Zheng-Rong Kan; Xing Wang; Sheng-Gang Pan; Xiang-Ru Tang (Science of The Total Environment, 2023)

Overexpression of two CONSTANS-like 2 (MiCOL2) genes from mango delays flowering and enhances tolerance to abiotic stress in transgenic Arabidopsis - Rong-Zhen Liang; Cong Luo; Yuan Liu; Wan-Li Hu; Yi-Hang Guo; Hai-Xia Yu; Ting-Ting Lu; Shu-Quan Chen; Xiu-Juan Zhang; Xin-Hua He (Plant Science, 2023)

A novel method for real-time ATR system of AUV based on Attention-MobileNetV3 network and pixel correction algorithm - Xiaochao Huang; Rong Yang; Qi Wang; Fei Yu; Bo He (Ocean Engineering, 2023)

Selective recovery of rare earth elements and value-added chemicals from the Dicranopteris linearis bio-ore produced by agromining using green fractionation - Candie Xie; Ye Xiao; Chao He; Wen-Shen Liu; Ye-Tao Tang; Shizhong Wang; Antony van der Ent; Jean Louis Morel; Marie-Odile Simonnot; Rong-Liang Qiu (Journal of Hazardous Materials, 2023)

Carrier type affects anammox community assembly, species interactions and nitrogen conversion - Baoyong Zhang; Nianbo Zhang; Ao He; Chen Wang; Zhen Li; Guanjun Zhang; Rong Xue (Bioresource Technology, 2023)

Achieving robust mainstream nitritation by implementing light irradiation: long-term performance and microbial dynamics - Zhaorui Chu; Dandan Huang; Xiaoyu Huang; Jianfeng He; Lexin Chen; Jinyin Wang; Hongwei Rong (Bioresource Technology, 2023)

Elevated Levels of Naturally-Occurring Autoantibodies Against the Extracellular Domain of p75NTR Aggravate the Pathology of Alzheimer’s Disease - Chen-Yang He; Ding-Yuan Tian; Si-Han Chen; Wang-Sheng Jin; Yuan Cheng; Jia-Yan Xin; Wei-Wei Li; Gui-Hua Zeng; Cheng-Rong Tan; Jie-Ming Jian; Dong-Yu Fan; Jun-Rong Ren; et al. (Neuroscience Bulletin, 2023)

Associations of personal exposure to domestic heating and cooking fuel emissions and epidemiological effects on rural residents in the Fenwei Plain, China - Yunxuan Gu; Hongmei Xu; Rong Feng; Yue Cheng; Bei Han; Kin Fai Ho; Zexuan Wang; Yansu He; Linli Qu; Steven Sai Hang Ho; Jian Sun; Zhenxing Shen; et al. (Science of The Total Environment, 2023)

Short-term exposure to air pollution is an emerging but neglected risk factor for schizophrenia: A systematic review and meta-analysis - Rong Song; Li Liu; Ning Wei; Xuanxuan Li; Jintao Liu; Jiajun Yuan; Shuangshuang Yan; Xiaoni Sun; Lu Mei; Yunfeng Liang; Yuxuan Li; Xiaoyu Jin; et al. (Science of The Total Environment, 2023)

Moderate physical activity against effects of short-term PM2.5 exposure on BP via myokines-induced inflammation - Mengqi Wu; Yaxian Pang; Meiyu Chen; Lipeng Li; Lina Yan; Jie Ning; Qingping Liu; Yaling Zhang; Tao Jiang; Aijuan Kang; Xiaoyan Huang; Wentao Hu; et al. (Science of The Total Environment, 2023)

Transport of plastic particles in natural porous media under freeze–thaw treatment: Effects of porous media property - Meng Li; Lei He; Lichun Hsieh; Haifeng Rong; Meiping Tong (Journal of Hazardous Materials, 2023)

Modelling the impacts of inhibitors and fertilizer placement on maize yield and ammonia, nitrous oxide and nitrate leaching losses in southwestern Ontario, Canada - Rong Jiang; Jingyi Yang; Craig F. Drury; Brian B. Grant; Ward N. Smith; Wentian He; Daniel W. Reynolds; Ping He (Journal of Cleaner Production, 2023)

Modelling maize yield, soil nitrogen balance and organic carbon changes under long-term fertilization in Northeast China - Jingmin Yang; Rong Jiang; Hongwei Zhang; Wentian He; Jingyi Yang; Ping He (Journal of Environmental Management, 2023)

Mice kidney biometabolic process analysis after cantharidin exposure using widely-targeted metabolomics combined with network pharmacology - Tianmu He; Lijuan Xiong; Yixin Zhang; Rong Yan; Ming Yu; Meichen Liu; Liu Liu; Cancan Duan; Xiaofei Li; Jianyong Zhang (Food and Chemical Toxicology, 2023)

Boosting persulfate activation via paper mill sludge-based biochar for efficient degradation of bisphenol A: Inherent multiple active sites - Zhi-Juan Wang; Yang-Qian Lin; Hua-Jing Zhou; Zi-Lian Liu; Rong-Rong Miao; Xi-Meng Xu; Liang He; Qing-Qing Guan (Chemical Engineering Journal, 2023)

An improved model assessing variation characteristics of pore structure of sandy soil thawing from extremely low temperature using NMR technique - Bo Liu; Yanqing He; Yanhui Han; Ting Li; Dongyang Li; Rong Gao (Cold Regions Science and Technology, 2023)

Exposure–response relationship between temperature, relative humidity, and varicella: a multicity study in South China - Yihan Li; Jialing Li; Zhihua Zhu; Weilin Zeng; Qi Zhu; Zuhua Rong; Jianxiong Hu; Xing Li; Guanhao He; Jianguo Zhao; Lihua Yin; Yi Quan; et al. (Environmental Science and Pollution Research, 2023)

Acinetobacter faecalis Sp. Nov., Isolated from Elephant Faeces - Xue-Mei Chen; De-Feng An; Si-Rong He; Shao-Juan Yang; Zu-Zhen Yang; Lian-Shuang Xiong; Gui-Ding Li; Ming-Guo Jiang; Cheng-Lin Jiang; Yi Jiang (Current Microbiology, 2023)

A strategy for screening and identification of new amino acid-conjugated bile acids with high coverage by liquid chromatography-mass spectrometry - Yan-Zhen Wang; Peng-Cheng Mei; Pei-Rong Bai; Na An; Jin-Gang He; Jie Wang; Quan-Fei Zhu; Yu-Qi Feng (Analytica Chimica Acta, 2023)

Effects of Ran-GTP/importin β inhibition on the meiotic division of porcine oocytes - Yijing He; Jia Li; Lei Peng; Qiao Li; Yajie Chu; Qixin Lin; Jianjun Dai; Rong Rui; Shiqiang Ju (Histochemistry and Cell Biology, 2022)

Analysis of the effect of seasonal changes on sensitive parameters of LAI-based Penman–Monteith evapotranspiration model based on particle swarm algorithm - Hao Duan; Xin He; Hongli Zhao; Xiaohui Jin; Haowei Xu; Rong Wang (Acta Geophysica, 2022)

Homozygous missense mutation in CCDC155 disrupts the transmembrane distribution of CCDC155 and SUN1, resulting in non-obstructive azoospermia and premature ovarian insufficiency in humans - Huan Wu; Xin Zhang; Rong Hua; Yuqian Li; Li Cheng; Kuokuo Li; Yiyuan Liu; Yang Gao; Qunshan Shen; Guanxiong Wang; Mingrong Lv; Yuping Xu; et al. (Human Genetics, 2022)

Preparation of Pinocembrin-Loaded F127/MPEG-PDLLA Polymer Micelles and Anti-Osteoporotic Activity - Xia Cao; Qing He; Michael Adu-Frimpong; Xinyi Shen; Wanjing Rong; Xiaoxiao Li; Jian Zhang; Xiaoli Xia; Feng Shi; Hao Ji; Elmurat Toreniyazov; Qilong Wang; et al. (AAPS PharmSciTech, 2022)

Isolation and Analysis of Reverse Transcriptase of Ty1-copia-Like Retrotransposons in Sugarcane - Jun-Xian Liu; Jing Liu; Tai-Yi Yang; Li-Min Liu; Li-Hang Qiu; Yi-Jing Gao; Wei-Xing Duan; Jing-Chao Lei; Hong-Jian Liu; Rong-Hua Zhang; Wei-Zhong He; Song Li; et al. (Sugar Tech, 2022)

Plasma Lipidomic Subclasses and Risk of Hypertension in Middle-Aged and Elderly Chinese - Zhenhua Niu; Qingqing Wu; Yaogan Luo; Di Wang; He Zheng; Yanpu Wu; Xiaowei Yang; Rong Zeng; Liang Sun; Xu Lin (Phenomics, 2022)

Exposure characteristics of ultrafine particles on urban streets and its impact on pedestrians - Rong He; Zhaowen Qiu (Environmental Monitoring and Assessment, 2022)

Metabacillus rhizolycopersici sp. nov., Isolated from the Rhizosphere Soil of Tomato Plants - Rong Ma; Shan-Wen He; Xing Wang; Kyu Kyu Thin; Ji-Gang Han; Xiao-Xia Zhang (Current Microbiology, 2022)

Naturally-Occurring Antibodies Against Bim are Decreased in Alzheimer’s Disease and Attenuate AD-type Pathology in a Mouse Model - Jie-Ming Jian; Dong-Yu Fan; Ding-Yuan Tian; Yuan Cheng; Pu-Yang Sun; Cheng-Rong Tan; Gui-Hua Zeng; Chen-Yang He; Ye-Ran Wang; Jie Zhu; Xiu-Qing Yao; Yan-Jiang Wang; et al. (Neuroscience Bulletin, 2022)

MicroRNA alteration in cerebrospinal fluid from comatose patients with traumatic brain injury after right median nerve stimulation - Ying Jia; Yi-fan He; Ye Tian; Yuan-zhi Wang; Rui-ting Zhao; Xiao-chun Li; Jian Sun; Ying-sheng Wei; Shuo An; Heng-jie Yuan; Chun-xiao Wan; Rong-cai Jiang (Experimental Brain Research, 2022)

Spatiotemporal variation of the loose deposits in Baisha River Basin after the 2008 Wenchuan earthquake - Jiao-rong Lyu; Yu-hai Bao; Hang-yu Xie; Hong Li; Yun-hua Hu; Xiu-bin He (Journal of Mountain Science, 2022)

Fast forward modeling of muon transmission tomography based on model voxelization ray energy loss projection - Rong-Qing Zhang; Zhen-Zhu Xi; Wei Liu; He Wang; Zi-Yan Yang (Applied Geophysics, 2022)

Global evaluation of inhibitor impacts on ammonia and nitrous oxide emissions from agricultural soils: A meta‐analysis - Daijia Fan; Wentian He; Ward N. Smith; Craig F. Drury; Rong Jiang; Brian B. Grant; Yaoyao Shi; Daping Song; Yanhua Chen; Xuexia Wang; Ping He; Guoyuan Zou (Global Change Biology, 2022)
Inhibitors are widely considered an efficient tool for reducing nitrogen (N) loss and improving N use efficiency, but their effectiveness is highly variable across agroecosystems. In this study, we synthesized 182 studies (222 sites) worldwide to evaluate the impacts of inhibitors (urease inhibitors [UI], nitrification inhibitors [NI] and combined inhibitors) on crop yields and gaseous N loss (ammonia [NH 3 ] and nitrous oxide [N 2 O] emissions) and explored their responses to different management and environmental factors including inhibitor application timing, fertilization regime, cropping system, water management, soil properties and climatic conditions using subgroup meta‐analysis, meta‐regression and multivariate analyses. The UI were most effective in enhancing crop yields (by 5%) and reducing NH 3 volatilization (by 51%), whereas NI were most effective at reducing N 2 O emissions (by 49%). The application of UI mitigates NH 3 loss and increases crop yields especially in high NH 3 ‐N loss scenarios, whereas NI application would minimize the net N 2 O emissions and the resultant environmental impacts especially in low NH 3 ‐N loss scenarios. Alternatively, the combined application of UI and NI enables producers to balance crop production and environmental conservation goals without pollution tradeoffs. The inhibitor efficacy for decreasing gaseous N loss was dependent upon soil and climatic conditions and management practices. Notably, both meta‐regression and multivariate analyses suggest that inhibitors provide a greater opportunity for reducing fertilizer N inputs in high‐N‐surplus systems and presumably favor crop yield enhancement under soil N deficiency situations. The pursuit of an improved understanding of the interactions between plant‐soil‐climate‐management systems and different types of inhibitors should continue to optimize the effectiveness of inhibitors for reducing environmental losses while increasing productivity.

Complex impacts of hydraulic fracturing return fluids on soil microbial community respiration, structure and functional potentials - Cheng Zhong; Camilla L. Nesbø; Konstantin von Gunten; Yifeng Zhang; Xiaoqing Shao; Rong Jin; Kurt O. Konhauser; Greg G. Goss; Jonathan W. Martin; Yuhe He; Pei‐Yuan Qian; Brian D. Lanoil; et al. (Environmental Microbiology, 2022)
Summary The consequences of soils exposed to hydraulic fracturing (HF) return fluid, often collectively termed flowback and produced water (FPW), are poorly understood, even though soils are a common receptor of FPW spills. Here, we investigate the impacts on soil microbiota exposed to FPW collected from the Montney Formation of western Canada. We measured soil respiration, microbial community structure and functional potentials under FPW exposure across a range of concentrations, exposure time and soil types (luvisol and chernozem). We find that soil type governs microbial community response upon FPW exposure. Within each soil, FPW exposure led to reduced biotic soil respiration, and shifted microbial community structure and functional potentials. We detect substantially higher species richness and more unique functional genes in FPW‐exposed soils than in FPW‐unexposed soils, with metagenome‐assembled genomes (e.g. Marinobacter persicus ) from luvisol soil exposed to concentrated FPW being most similar to genomes from HF/FPW sites. Our data demonstrate the complex impacts of microbial communities following FPW exposure and highlight the site‐specific effects in evaluation of spills and agricultural reuse of FPW on the normal soil functions.

Cuproptosis: copper-induced regulated cell death - Wen-Jun Duan; Rong-Rong He (Science China Life Sciences, 2022)

Synthesis and biological evaluation of prodrugs for nitroreductase based 4-β-amino-4′-Demethylepipodophyllotoxin as potential anticancer agents - Zheng-Rong Wu; Wei Deng; Dian He (Medicinal Chemistry Research, 2022)

Asymmetric changes of photosynthetically active radiation and light utilization efficiency during the maize growing season in North China - Huayun He; Qi Hu; Jing Wang; Mengyuan Xing; Yuanyuan Liu; Xiaochen Wang; Rong Li; Xuebiao Pan; Zhihua Pan; Binxiang Huang; Qijin He (Theoretical and Applied Climatology, 2022)

Analysis of Grain Yield Formation Components of Extra Heavy-Panicle-Type Mid-Season Indica Hybrid Rice - Xiaolong Zhong; Hafiz Athar Hussain; Bingbing Zhao; Manyu Huang; Saddam Hussain; Rong Xie; Linjun Cai; Han Yun; Guanghua He; Changwei Zhang (Journal of Plant Growth Regulation, 2022)

Composition, Demographic History, and Population Structures of Trichiurus - Kui-Ching Hsu; Mu-Rong Yi; Sui Gu; Xiong-Bo He; Zhi-Sen Luo; Bin Kang; Hung-Du Lin; Yun-Rong Yan (Frontiers in Marine Science, 2022)
Sequences of the complete mitochondrial cytochrome oxidase subunit I gene were used to identify Trichiurus species and examine their population genetic structure and demographic history along the coast of China. Three Trichiurus species were found. Trichiurus japonicus lives in colder waters along the continental shelves in the China Seas, while Trichiurus nanhaiensis lives warmer waters along continental slopes in the South China Sea, and Trichiurus brevis lives in shallow and warmer waters in the South China Sea. The migrations of these species were mainly associated with feeding and spawning preferences. Two major wintering and spawning grounds in the East China Sea and South China Sea were found. All species showed a lack of population genetic structure resulting from their oceanodromous life cycle (the degree of population substructure index N ST = 0.000–0.149), but the results of approximate Bayesian computational approaches suggested population declines or stabilization and differentiation. The results of the T MRCA (time to the most recent common ancestor) showed that during glaciations, the Yellow Sea and the East China Sea were completely exposed, and the South China Sea acted as a refugium. Thus, the populations of these three species experienced differentiation during glaciations. This study also examined the limitations of Bayesian skyline plot analysis.

The solar wind plasma upstream of Mars observed by Tianwen-1: Comparison with Mars Express and MAVEN - Kai Fan; Limei Yan; Yong Wei; Aibing Zhang; Linggao Kong; Markus Fränz; Fei He; Lihui Chai; Chongjing Yuan; Yuqi Wang; Jun Zhong; Zhaojin Rong; et al. (Science China Earth Sciences, 2022)

Cassiterite oxygen isotopes in magmatic-hydrothermal systems: in situ microanalysis, fractionation factor, and applications - Yang Li; Sheng He; Rong-Qing Zhang; Xian-Wu Bi; Lian-Jun Feng; Guo-Qiang Tang; Wen-Zhong Wang; Fang Huang; Xian-Hua Li (Mineralium Deposita, 2022)

Monitoring the behavior of subway tunnels during early operation in saturated soft strata - Ben-Guo He; Rong-Li Zhen; Tian-Yu Chen; Hong-Pu Li (Bulletin of Engineering Geology and the Environment, 2022)

Effects of Dietary Rhodobacter sphaeroides Protein Substitution of Fishmeal and Coenzyme Q10 Supplementation on Growth Performance, Intestinal Microbiota and Stress Tolerance of Litopenaeus vannamei in Acute Low Salinity - Zhihong Liao; Yangyang Gong; Ziqiao Wang; Yingjie Wang; Rong Yao; Mengdie Chen; Dan Wei; Wei Zhao; Xuanshu He; Jin Niu (Frontiers in Marine Science, 2022)
A 56-day culture experiment followed by an acute low salinity challenge was conducted to evaluate the effects of Rhodobacter sphaeroides protein (RSP) substitution of fishmeal and Coenzyme Q10 (CoQ10) supplementation on growth performance, intestinal microbiota and compressive capacity of Litopenaeus vannamei ( L. vanname i). Four experimental diets were formulated: FM diet (20% fishmeal), RSP diet (20% RSP instead of 20% fishmeal), CoQ10 diet (20% fishmeal supplemented with CoQ10 at 0.08 g kg –1 ), RSP + CoQ10 diet (20% RSP supplemented with CoQ10 at 0.08 g kg –1 ). The obtained results were denoted that L. vannamei fed CoQ10 diet could improve growth performance (weigh gain and specific growth rate), condition factor and crude lipid, and decrease hepatosomatic index, but no differences were found in survival rates. High throughput sequencing on intestinal microbiota indicated that intestinal microbiota of L. vannamei consisted mainly of Proteobacteria and Firmicutes . The species richness of the RSP diet was remarkably higher than that of the other diets. Moreover, the presence of RSP and CoQ10 may improve intestinal homeostasis by inhibiting the propagation of Vibrio . Compared to FM diet and RSP diet, supplementation of CoQ10 significantly improved the compressive capacity of L. vannamei against the acute low salinity challenge, as indicated by higher survival rates as well as higher activities of T-AOC and higher transcript levels of SOD , HSP70 , and Relish gene. Our findings demonstrated that RSP could serve as a novel FM and CoQ10 could serve as a prospective feed additive to help L. vannamei to overcome environmental stresses.

Polysaccharide Krestin Prevents Alzheimer’s Disease-type Pathology and Cognitive Deficits by Enhancing Monocyte Amyloid-β Processing - Si-Han Chen; Chen-Yang He; Ying-Ying Shen; Gui-Hua Zeng; Ding-Yuan Tian; Yuan Cheng; Man-Yu Xu; Dong-Yu Fan; Cheng-Rong Tan; An-Yu Shi; Xian-Le Bu; Yan-Jiang Wang (Neuroscience Bulletin, 2022)

Pulsed exsolution of magmatic ore-forming fluids in tin-tungsten systems: a SIMS cassiterite oxygen isotope record - Yang Li; Rong-Qing Zhang; Sheng He; Massimo Chiaradia; Xian-Hua Li (Mineralium Deposita, 2022)

The adsorption mechanism of CF4 on the surface of activated carbon made from peat and modified by Cu - Rong Pan; Wei Dong; Yanni Guo; Yining Tang; Jun Shang; Lei Zhou; Deliang He (Environmental Science and Pollution Research, 2022)

Circ_0002711 knockdown suppresses cell growth and aerobic glycolysis by modulating miR-1244/ROCK1 axis in ovarian cancer - Weiquan Xie; Lu Liu; Chuanyong He; Min Zhao; Rong Ni; Zixiong Zhang; Chengyu Shui (Journal of Biosciences, 2021)

Use of historical and contemporary distribution of mammals in China to inform conservation - Kang Huang; He Zhang; Chengliang Wang; Rong Hou; Pei Zhang; Gang He; Songtao Guo; Shiyi Tang; Baoguo Li; Charles Oxnard; Ruliang Pan (Conservation Biology, 2021)
A systematic understanding of dynamic animal extinction trajectories for different regions in a nation like China is critically important to developing practical conservation strategies. We explored historical and contemporary changes in terrestrial mammalian diversity to determine how diversity in each of the 5 regions in China has changed over time and to examine the conservation potential of these regions. We used records from databases on Pleistocene mammalian fossils and historical distribution records (1175–2020) for Primates (as a case study) to reconstruct evolutionary and historical distribution trajectories of the 11 orders of terrestrial mammals and to predict their prospective survival based on the national conservation strategy applied. The results indicated that since the Pleistocene, 4–5 mammalian orders have been lost in the northeast, 3 in central China, 2 along the coast, and 1 in the northwest. In the southwest, all 11 orders were maintained. Contemporarily, the coast and southwest had the highest and second‐highest species densities. The southwest region and southeastern sections of the northwest region were the most historically and contemporarily diverse areas, which suggests that they should be the first priority for protected area (PA) designation. The central and coastal areas should be secondarily prioritized. In these 2 regions, conservation should focus on human coexistence with nature. Less attention should be paid to the PA in the northeast and western northwest because in these areas ecosystems are depauperate and the climate is harsh. Conservation in these areas should focus principally on avoiding further human encroachment on natural areas. Article impact statement : Historical and contemporary patterns of extinction can be a basis for mammalian conservation strategies.

The chemical profile and biological activity of different extracts of Sapindus mukorossi Gaertn. against Cutibacterium acnes - Min-Ping Wei; Jin-Dan Qiu; Lu Li; Yun-Fei Xie; Ya-Hui Guo; Hang Yu; Yu-Liang Cheng; He Qian; Wei-Rong Yao (Natural Product Research, 2021)

Isolation of two sesquiterpene glycosides from Sapindus mukorossi Gaertn. with cytotoxic properties and analysis of their mechanism based on network pharmacology - Min-ping Wei; Xiao-wen Zhu; Hang Yu; Yun-fei Xie; Ya-hui Guo; Yu-liang Cheng; He Qian; Wei-rong Yao (Natural Product Research, 2021)

Differential metabolism-associated gene expression of duck pancreatic cells in response to two strains of duck hepatitis A virus type 1 - Zhen Chen; Shao-hua Shi; Yu Huang; Cui-qin Huang; Rong-chang Liu; Long-fei Cheng; Guang-hua Fu; Hong-mei Chen; Chun-he Wan; Qiu-ling Fu (Archives of Virology, 2021)
Several outbreaks of duck hepatitis A virus type 1 (DHAV-1), which were characterized by yellow coloration and hemorrhage in pancreatic tissues, have occurred in China. The causative agent is called pancreatitis-associated DHAV-1. The mechanisms involved in pancreatitis-associated DHAV-1 infection are still unclear. Transcriptome analysis of duck pancreas infected with classical-type DHAV-1 and pancreatitis-associated DHAV-1 was carried out. Deep sequencing with Illumina-Solexa resulted in a total of 53.9 Gb of clean data from the cDNA library of the pancreas, and a total of 29,597 unigenes with an average length of 993.43 bp were generated by de novo sequence assembly. The expression levels of D-3-phosphoglycerate dehydrogenase, phosphoserine aminotransferase, and phosphoserine phosphatase, which are involved in glycine, serine, and threonine metabolism pathways, were significantly downregulated in ducks infected with pancreatitis-associated DHAV-1 compared with those infected with classical-type DHAV-1. These findings provide information regarding differences in expression levels of metabolism-associated genes between ducks infected with pancreatitis-associated DHAV-1 and those infected with classical-type DHAV-1, indicating that intensive metabolism disorders may contribute to the different phenotypes of DHAV-1-infection.

Development and application of the Faba_bean_130K targeted next-generation sequencing SNP genotyping platform based on transcriptome sequencing - Chenyu Wang; Rong Liu; Yujiao Liu; Wanwei Hou; Xuejun Wang; Yamei Miao; Yuhua He; Yu Ma; Guan Li; Dong Wang; Yishan Ji; Hongyan Zhang; et al. (Theoretical and Applied Genetics, 2021)

Activation of the Hippocampal LXRβ Improves Sleep-Deprived Cognitive Impairment by Inhibiting Neuroinflammation - Chen Qiu; Min Wang; Wen Yu; Zheng Rong; He-Sheng Zheng; Ting Sun; Shui-Bing Liu; Ming-Gao Zhao; Yu-Mei Wu (Molecular Neurobiology, 2021)

Interaction of magnolia bark extracts with Staphylococcus aureus DNA and evaluation of the stability of their antibacterial activities - Shu-Mei Cui; Hai-yun Liang; Ting Li; Ke-Ke He; Yu-Mei Zheng; Meng Tang; Chong-rong Ke; Li-Ya Song (Archives of Microbiology, 2021)

Phenomic and metabolomic responses of roots to cadmium reveal contrasting resistance strategies in two rice cultivars (Oryza sativa L.) - Chong Liu; Mo-ming Lan; Er-kai He; Ai-jun Yao; Guo-bao Wang; Ye-tao Tang; Rong-liang Qiu (Soil Ecology Letters, 2021)

Enhanced Biodegradation of Hexachlorocyclohexane in Soil by Application of Exogenous Amendments - Xutong Liu; He Huang; Dan Huang; Kai Zhong; Qun Rong; Xingzi Qin; Chaolan Zhang; Xue Li (Water, Air, & Soil Pollution, 2021)

Effects of Mn2+ on neutral lipid content, C4 pathway, and related gene expression in Phaeodactylum tricornutum - Rong-Shi Chen; Li Zhang; Feng-Juan Wei; Lan-Ying Yuan; Pu Zhao; He-Yu Wang; Yi-Fu Gong (Journal of Applied Phycology, 2021)

Improvement on the Effectiveness of Marine Stock Enhancement in the Artificial Reef Area by a New Cage-Based Release Technique - Junbo Zhang; Yufeng He; Zhixing Guo; Shuheng Ji; Shuo Zhang; Yanli Tang; Huaxiang Sheng; Rong Wan; Daisuke Kitazawa (Journal of Ocean University of China, 2021)

Dissipation, residue, dietary, and ecological risk assessment of atrazine in apples, grapes, tea, and their soil - Longfei Yuan; Yida Chai; Congdi Li; Rong Liu; Zenglong Chen; Li Li; Wei Li; Yujian He (Environmental Science and Pollution Research, 2021)

Remediation of Soil in a Deserted Arsenic Plant Site Using Synthesised MgAlFe-LDHs - Kai Zhong; Chaolan Zhang; Siwei Ren; He Huang; Qun Rong; Yongxin Zhou (Bulletin of Environmental Contamination and Toxicology, 2021)

Retrospective surveillance of porcine circovirus 4 in pigs in Inner Mongolia, China, from 2016 to 2018 - Zhuo Ha; Chengdong Yu; Changzhan Xie; Guanyu Wang; Ying Zhang; Pengfei Hao; Jinfeng Li; Zhuoxin Li; Yanwei Li; Fulong Rong; Fulong Nan; He Zhang; et al. (Archives of Virology, 2021)

Genotypic variation in nitrogen utilization efficiency in oilseed rape is related to the coordination of leaf senescence and root N uptake during reproductive stage - Huiying He; Yuyu Xie; Anyu Zhao; Wencong Hu; Xiao Guo; Anthony J. Miller; Xiaoming Wu; Biyun Chen; Rong Zhang; Hui Tian; Yajun Gao (Plant and Soil, 2021)

Transcutaneous Auricular Vagus Nerve Stimulation: From Concept to Application - Yu Wang; Shao-Yuan Li; Dan Wang; Mo-Zheng Wu; Jia-Kai He; Jin-Ling Zhang; Bin Zhao; Li-Wei Hou; Jun-Ying Wang; Lei Wang; Yi-Fei Wang; Yue Zhang; et al. (Neuroscience Bulletin, 2021)

Correction to: Synthetic antimicrobial agents inhibit aflatoxin production - Jing Li; Qing-Qing Zhi; Jie Zhang; Xiao-Yu Yuan; Li-Hong Jia; Yu-Lin Wan; Qiu-Yun Liu; Jian-Rong Shi; Zhu-Mei He (Brazilian Journal of Microbiology, 2021)

Synthetic antimicrobial agents inhibit aflatoxin production - Jing Li; Qing-Qing Zhi; Jie Zhang; Xiao-Yu Yuan; Li-Hong Jia; Yu-Lin Wan; Qiu-Yun Liu; Jian-Rong Shi; Zhu-Mei He (Brazilian Journal of Microbiology, 2021)

Small-sized extracellular vesicles (EVs) derived from acute myeloid leukemia bone marrow mesenchymal stem cells transfer miR-26a-5p to promote acute myeloid leukemia cell proliferation, migration, and invasion - Dexiang Ji; Yue He; Wei Lu; Yanyan Rong; Fei Li; Xianbao Huang; Ruibin Huang; Yanxia Jiang; Guoan Chen (Human Cell, 2021)

Genome sequencing and functional annotation of Bacillus sp. strain BS-Z15 isolated from cotton rhizosphere soil having antagonistic activity against Verticillium dahliae - Zhong-Yi Chen; Xieerwanimu Abuduaini; Nuramina Mamat; Qi-Lin Yang; Meng-Jun Wu; Xin-Rui Lin; Ru Wang; Rong-Rong Lin; Wei-Jun Zeng; Huan-Chen Ning; He-Ping Zhao; Jin-Yu Li; et al. (Archives of Microbiology, 2021)

Effect of fermentation bed on bacterial growth in the fermentation mattress material and cecum of ducks - Jian- mei Wang; Xin- meng Gan; Fa-jun Pu; Wan- xia Wang; Min Ma; Ling-li Sun; Ji-wei Hu; Bo Hu; Rong-ping Zhang; Li-li Bai; Liang Li; He-he Liu (Archives of Microbiology, 2021)

Identification of genetic variants in m6A modification genes associated with pancreatic cancer risk in the Chinese population - Pingting Ying; Yao Li; Nan Yang; Xiaoyang Wang; Haoxue Wang; Heng He; Bin Li; Xiating Peng; Danyi Zou; Ying Zhu; Rong Zhong; Xiaoping Miao; et al. (Archives of Toxicology, 2021)

Discovery of new small-molecule cyclin-dependent kinase 6 inhibitors through computational approaches - Xiaojiao Luo; Yu Zhao; Pan Tang; Xingkai Du; Feng Li; Qingying Wang; Rong Li; Jun He (Molecular Diversity, 2021)

Rhizobium rhizolycopersici sp. nov., Isolated from the Rhizosphere Soil of Tomato Plants in China - Kyu Kyu Thin; Shan-Wen He; Xing Wang; Yao Wang; Ma Rong; Ji-Gang Han; Xiaoxia Zhang (Current Microbiology, 2021)

Geochemical characteristics and geological significance of chert nodules in Qixia formation, Pingding Mountain, lower Yangtze Plate - Jun Li; Lu-wang Chen; Chun-ming Hao; Jie Zhang; Song Chen; He-rong Gui (Journal of Mountain Science, 2021)

A stochastic epidemic model coupled with seasonal air pollution: analysis and data fitting - Sha He; Sanyi Tang; Yongli Cai; Weiming Wang; Libin Rong (Stochastic Environmental Research and Risk Assessment, 2020)

Quantitative Determination of Glymphatic Flow Using Spectrophotofluorometry - Yu Zhang; Jian Song; Xu-Zhong He; Jian Xiong; Rong Xue; Jia-Hao Ge; Shi-Yu Lu; Die Hu; Guo-Xing Zhang; Guang-Yin Xu; Lin-Hui Wang (Neuroscience Bulletin, 2020)

Numerical simulations of incompressible fluid flow in synthetic fractures using lattice Boltzmann method - Guan Rong; Long Cheng; Junsong Quan; Yaosheng Tan; Renhui He; Jie Tan (Arabian Journal of Geosciences, 2020)

An Innovative Method to Evaluate Hydraulic Conductivity of a Single Rock Fracture Based on Geometric Characteristics - Jie Tan; Guan Rong; Hongbin Zhan; Renhui He; Song Sha; Bowen Li (Rock Mechanics and Rock Engineering, 2020)

Purinergic signaling as a basis of acupuncture-induced analgesia - Jin-Rong He; Shu-Guang Yu; Yong Tang; Peter Illes (Purinergic Signalling, 2020)
This review summarizes experimental evidence indicating that purinergic mechanisms are causally involved in acupuncture (AP)-induced analgesia. Electroacupuncture (EAP) and manual AP release at pain-relevant acupoints ATP which may activate purinergic P2X receptors (Rs) especially of the P2X3 type situated at local sensory nerve endings (peripheral terminals of dorsal root ganglion [DRG] neurons); the central processes of these neurons are thought to inhibit via collaterals of ascending dorsal horn spinal cord neurons, pain-relevant pathways projecting to higher centers of the brain. In addition, during AP/EAP non-neuronal P2X4 and/or P2X7Rs localized at microglial cells of the CNS become activated at the spinal or supraspinal levels. In consequence, these microglia secrete bioactive compounds such as growth factors, cytokines, chemokines, reactive oxygen, and nitrogen species, which modulate the ascending neuronal pathways conducting painful stimuli. Alternatively, ATP released at acupoints by AP/EAP may be enzymatically degraded to adenosine, stimulating in loco presynaptic A1Rs exerting an inhibitory influence on the primary afferent fibers (the above mentioned pain-sensing peripheral terminals of DRG neurons) which thereby fail to conduct action potentials to the spinal cord dorsal horn. The net effect of the stimulation of P2X3, P2X4, P2X7, and A1Rs by the AP/EAP-induced release of ATP/adenosine at certain acupoints will be analgesia.

Numerical investigation of heat transfer effect on flow behavior in a single fracture - Jie Tan; Guan Rong; Renhui He; Jie Yang; Jun Peng (Arabian Journal of Geosciences, 2020)

Rapid identification and analysis of the major chemical constituents from the fruits of Sapindus mukorossi by HPLC-ESI-QTOF-MS/MS - Yun Ling; Qing Zhang; Wenjuan Zhong; Mengping Chen; Haonan Gong; Shasha He; Rong Liang; Jiao Lv; Liyuan Song (Natural Product Research, 2020)

Habitat fragmentation changes top‐down and bottom‐up controls of food webs - Rong Wang; Xin Zhang; Yi‐Su Shi; Yuan‐Yuan Li; Jianguo Wu; Fangliang He; Xiao‐Yong Chen (Ecology, 2020)
Top‐down and bottom‐up controls regulate the structure and stability of ecosystems, but their relative roles in terrestrial systems have been debated. Here we studied a hydro‐inundated land‐bridge system in subtropical China and tested the relative importance of these two controls in determining the rodent‐mediated regeneration of a locally dominant tree species. Our results showed that both controls operated in terrestrial habitats and that their relative importance switched as habitat size changed. Habitat loss initially removed predators of rodents that released rodent populations and triggered massive seed predation (top‐down control), leading to reduced seedling establishment. A further reduction in habitat size led to decrease in rodent population that was supposed to increase seedling survival of the tree species, but the decline in habitat size deteriorated the abiotic environments (bottom‐up control) that severely prevented seedling recruitment. As the ongoing global land use change is creating increasing number of small‐sized forest fragments, our findings provide novel insights into the restoration of seriously fragmented forests.

CuO Nanoparticle Exposure Impairs the Root Tip Cell Walls of Arabidopsis thaliana Seedlings - Guangli Nie; Jian Zhao; Rong He; Yulin Tang (Water, Air, & Soil Pollution, 2020)

GaHD1, a candidate gene for the Gossypium arboreum SMA-4 mutant, promotes trichome and fiber initiation by cellular H2O2 and Ca2+ signals - Mingquan Ding; Yuefen Cao; Shae He; Jian Sun; Huaqin Dai; Hua Zhang; Chendong Sun; Yurong Jiang; Andrew H. Paterson; Junkang Rong (Plant Molecular Biology, 2020)

A Novel Eyes Topical Drug Delivery System: CsA-LNC for the Treatment of DED - Anan Zhang; Rong Sun; Meixin Ran; Yaxin Deng; Ying Ge; Yunjing Zhu; Xiumei Tao; Lixia Shang; Jingxin Gou; Haibing He; Tian Yin; Yanjiao Wang; et al. (Pharmaceutical Research, 2020)

Tensile strength and brittleness of sandstone and granite after high-temperature treatment: a review - Song Sha; Guan Rong; Jie Tan; Renhui He; Bowen Li (Arabian Journal of Geosciences, 2020)

Transcriptome analysis reveals genes associated with leaf color mutants in Cymbidium longibracteatum - Jiang Yu; Wang Qiang; Shen Qin-Qin; Zhuo Bi-Ping; He Jun-Rong (Tree Genetics & Genomes, 2020)

The isolation and culture of giant panda (Ailuropoda melanoleuca) breast milk cells - Chen Yijiao; Wang Donghui; Liu Yuliang; Li Feiping; He Ping; Cai Zhigang; Zhang Hao; Chen Min; Hou Rong; An Junhui (In Vitro Cellular & Developmental Biology - Animal, 2020)

Simulation of the landform change process on a purple soil slope due to tillage erosion and water erosion using UAV technology - Chao Yang; Zheng-an Su; Jian-rong Fan; Hai-dong Fang; Liang-tao Shi; Jian-hui Zhang; Zhou-yao He; Tao Zhou; Xiao-yi Wang (Journal of Mountain Science, 2020)

Influence of Aphis gossypii feeding on defense strategy of native and introduced populations of Ageratina adenophora - Ying Lin; Shu-Qi He; Zhi-Hui Lu; Yu-Lin Gao; Yan-Ru Duan; Zheng-Yue Li; Bin Chen; Fu-Rong Gui (Arthropod-Plant Interactions, 2020)

MiR-145 alleviates Hcy-induced VSMC proliferation, migration, and phenotypic switch through repression of the PI3K/Akt/mTOR pathway - Minghao Zhang; Fan Li; Xiuyu Wang; Jian Gong; Yushan Xian; Guan Wang; Zihan Zheng; Chenxu Shang; Bo Wang; Yanhao He; Weirong Wang; Rong Lin (Histochemistry and Cell Biology, 2020)

Fate of 2,4,6-Tribromophenol in Soil Under Different Redox Conditions - Xiong Jia; Wenji Wang; Yao Yao; Yujie He; Philippe F.-X. Corvini; Rong Ji (Bulletin of Environmental Contamination and Toxicology, 2020)

The effects of mesoscale oceanographic structures and ambient conditions on the catch of albacore tuna in the South Pacific longline fishery - Cheng Zhou; Pingguo He; Liuxiong Xu; Pascal Bach; Xuefang Wang; Rong Wan; Hao Tang; Yu Zhang (Fisheries Oceanography, 2020)
Albacore tuna ( Thunnus alalunga ) exhibit patchy concentrations associated with biological process at a wide range of spatial scales, resulting in variations in their catchability by fishing gears. Here, we investigated the association of catch variation for pelagic longlines in the South Pacific Ocean with oceanographic mesoscale structures (in horizontal dimension) and ambient conditions (in vertical dimension). The distribution of albacore tuna as indicated by catch per unit effort (CPUE) of longlines was significantly related to the presence of mesoscale structures, with higher CPUE found at locations closer to thermal fronts and with greater gradient magnitudes, as well as areas marked by peripheral contour line of the anticyclone indicated by Sea Surface Height Anomalies ~0.05 m. Surface mesoscale current velocity had the negative effect on the catch, probably as a result of decreased catchability by shoaling the hook depth. Vertical distribution of albacore in the survey region of South Pacific Ocean was hardly restricted by ambient temperature and oxygen concentration, though effect of ambient temperature was relevant and showed a negatively linear correlation with CPUE at the range of 20–24°C. On the contrary, albacore distribution was evidently dominated by the water depth and showed strong preference on water depth of 200 m, which was likely a representative feeding layer. The presence of prey resources and their accessibility by albacore revealed by mesoscale structures in the biological and physical processes, and catchability determined by the location of the baited hooks comprehensively contribute to the variability of catch.

Immunogenicity noninferiority study of 2 doses and 3 doses of an Escherichia coli-produced HPV bivalent vaccine in girls vs. 3 doses in young women - Yue-Mei Hu; Meng Guo; Chang-Gui Li; Kai Chu; Wen-Gang He; Jing Zhang; Jian-Xiang Gu; Juan Li; Hui Zhao; Xiang-Hong Wu; BiZhen Lin; Zhi-Jie Lin; et al. (Science China Life Sciences, 2020)

Serum Uric Acid Levels and Risk of Intracranial Atherosclerotic Stenosis: A Cross-Sectional Study - Lin Li; Jun-Xia Zhu; Xiao-He Hou; Ya-Hui Ma; Wei Xu; Chen-Chen Tan; Fu-Rong Sun; Hong-Qi Li; Qiang Dong; Lan Tan; Jin-Tai Yu (Neurotoxicity Research, 2020)

Reduced mineral fertilization coupled with straw return in field mesocosm vegetable cultivation helps to coordinate greenhouse gas emissions and vegetable production - Rong Huang; Jiang Liu; Xinhua He; Deti Xie; Jiupai Ni; Chang Xu; Yarong Zhang; En Ci; Zifang Wang; Ming Gao (Journal of Soils and Sediments, 2020)

Triterpene-Enriched Olive Extract as an Immunopotentiator in Black Sea Bream (Acanthopagrus schlegelii) - Jiahuan Rong; Yu Han; Shanjie Zha; Yu Tang; Wei Shi; Xiaofan Guan; Xueying Du; Maolong He; Guangxu Liu (Journal of Ocean University of China, 2020)

Evidence of compliance with and effectiveness of guidelines for noninvasive prenatal testing in China: a retrospective study of 189,809 cases - Chan Tian; Tao Deng; Xiuhuang Zhu; Chen Gong; Yangyu Zhao; Yuan Wei; Rong Li; Xiufeng Xu; Miaonan He; Zhiwei Zhang; Jing Cheng; Mol BenWillem; et al. (Science China Life Sciences, 2020)

Elevated Hs-CRP Levels Are Associated with Higher Risk of Intracranial Arterial Stenosis - Bing-Jie Su; Yi Dong; Chen-Chen Tan; Xiao-He Hou; Wei Xu; Fu-Rong Sun; Mei Cui; Qiang Dong; Lan Tan; Jin-Tai Yu (Neurotoxicity Research, 2020)

Development of Climate and Earth System Models in China: Past Achievements and New CMIP6 Results - Tianjun Zhou; Ziming Chen; Liwei Zou; Xiaolong Chen; Yongqiang Yu; Bin Wang; Qing Bao; Ying Bao; Jian Cao; Bian He; Shuai Hu; Lijuan Li; et al. (Journal of Meteorological Research, 2020)

RETRACTED ARTICLE: Emerging protective roles of shengmai injection in septic cardiomyopathy in mice by inducing myocardial mitochondrial autophagy via caspase-3/Beclin-1 axis - Yan Cao; Xiaotong Han; Hongwei Pan; Yu Jiang; Xiang Peng; Weiwei Xiao; Jingjing Rong; Fang Chen; Jin He; Lianhong Zou; Yi Tang; Yanfang Pei; et al. (Inflammation Research, 2020)

Effect of FIGF overexpression on liver cells transforming to insulin-producing cells - Yaqin He; Xiaoliang Xie; Xiaoyan Li; Shikuo Rong; Yukui Li; Zhenhui Lu (Journal of Biosciences, 2019)

Pedobacter changchengzhani sp. nov., isolated from soil of Antarctica - Rui-Han He; Zhen-Wei Liu; Yong Yu; Hui-Rong Li; Zong-Jun Du (Antonie van Leeuwenhoek, 2019)

Identifying the Design Alternatives and Flow Interference of Tuna Purse Seine by the Numerical Modelling Approach - Cheng Zhou; Liuxiong Xu; Hao Tang; Fuxiang Hu; Pingguo He; Taisei Kumazawa; Xuefang Wang; Rong Wan; Shuchuang Dong (Journal of Marine Science and Engineering, 2019)
Dynamic responses of tuna purse seine to currents were numerically studied with regard to the vertical subsidence and global load distribution, and determinant attributes were identified. We rebuilt the submerged geometry of a purse seine net using the lumped mass method with hydrodynamic coefficients obtained from measurements of the prototype material, as well as a mesh grouping method, which corrects the twine diameter and netting material density for the equivalent net by introducing the compensation coefficient. Uneven tension distribution showed that it was vulnerable to high loads in the bunt area at shooting and along the lead line at pursing. High loads were present at the convex sections of net circles in the direction of the current. Higher shooting speeds resulted in well-balanced sinking, while a reduced hanging ratio of netting panels was beneficial to faster sinking. While large mesh sizes reduce water resistance and increase sinking velocity, extensive use should be cautioned in terms of the sensibility to stress. Comparing two options of different proportions of large-mesh panels, mesh sizes doubled for 15 strips versus 5 strips, suggesting that the 15 strip option would pose a higher risk of strand vulnerability, while the 5 strip option may be a more balanced alternative with a lower mesh density and a lower mesh stress.

Two highly oxygenated Ergosterols from cultures of the Basidiomycete Conocybe siliginea - Chao-Jun Pu; Yue-Ling Peng; Zheng-Hui Li; Juan He; Rong Huang; Tao Feng; Ji-Kai Liu (Natural Product Research, 2019)

Two new benzophenones from endohydric moss Polytrichum Commune - Xu-Hong Duan; Jian-Cheng Zhao; Lin Li; Lin Pei; Pei He; Rong Wang (Natural Product Research, 2019)

Ecological Risk Assessment of Neodymium and Yttrium on Rare Earth Element Mine Sites in Ganzhou, China - Chun-Mei Zhao; Xing Shi; Si-Qi Xie; Wen-Shen Liu; Er-Kai He; Ye-Tao Tang; Rong-Liang Qiu (Bulletin of Environmental Contamination and Toxicology, 2019)

Nitrogen use-inefficient oilseed rape genotypes exhibit stronger growth potency during the vegetative growth stage - Xiao Guo; Huiying He; Rong An; Yuying Zhang; Rui Yang; Lanqin Cao; Xiaoming Wu; Biyun Chen; Hui Tian; Yajun Gao (Acta Physiologiae Plantarum, 2019)

Interseismic Coupling in the Central Nepalese Himalaya: Spatial Correlation with the 2015 Mw 7.9 Gorkha Earthquake - Shuiping Li; Qi Wang; Gang Chen; Ping He; Kaihua Ding; Yunguo Chen; Rong Zou (Pure and Applied Geophysics, 2019)

Skin test of tuberculin purified protein derivatives with a dissolving microneedle-array patch - Wei Wang; Hou Ming Liu; Jing Zhou; Yu Guang Wang; Xi Feng; Hao Tang; Qinying Yan; Rong Sheng Zhu; Yu Wei Wu; Xing Guo Wang; Dan He; Fan Chen (Drug Delivery and Translational Research, 2019)

Non-monotonic Relaxation and Memory Effect of Rock Salt - Yi He; Deyi Jiang; Jie Chen; Rong Liu; Jinyang Fan; Xiang Jiang (Rock Mechanics and Rock Engineering, 2019)

Identifying the Pollution Characteristics of Atmospheric Polycyclic Aromatic Hydrocarbons Associated with Functional Districts in Ningbo, China - Lei Tong; Cheng-Hui Peng; Zhong-Wen Huang; Jing-Jing Zhang; Xiao-Rong Dai; Hang Xiao; Neng-Bin Xu; Jun He (Bulletin of Environmental Contamination and Toxicology, 2019)

Arbuscular mycorrhizal fungi abundance was sensitive to nitrogen addition but diversity was sensitive to phosphorus addition in karst ecosystems - Dan Xiao; Rongxiao Che; Xin Liu; Yongjun Tan; Rong Yang; Wei Zhang; Xunyang He; Zhihong Xu; Kelin Wang (Biology and Fertility of Soils, 2019)

A facile extraction of keratin from pig hair and its properties - Quan-Fang Li; Yufeng He; Rong-Min Wang (Biologia, 2019)

Evaluating giant panda as a surrogate species for conservation co-occurring species in the Baishuijiang National Nature Reserve - Zhanlei Rong; Xingming Liu; Chuanyan Zhao; Liwen He; Junjie Liu; Yunfei Gao; Fei Zang; Haojie Xu; Zhaoxia Guo; Yahua Mao (Environmental Science and Pollution Research, 2019)

Underestimated ecosystem carbon turnover time and sequestration under the steady state assumption: A perspective from long‐term data assimilation - Rong Ge; Honglin He; Xiaoli Ren; Li Zhang; Guirui Yu; T. Luke Smallman; Tao Zhou; Shi‐Yong Yu; Yiqi Luo; Zongqiang Xie; Silong Wang; Huimin Wang; et al. (Global Change Biology, 2019)
It is critical to accurately estimate carbon (C) turnover time as it dominates the uncertainty in ecosystem C sinks and their response to future climate change. In the absence of direct observations of ecosystem C losses, C turnover times are commonly estimated under the steady state assumption ( SSA ), which has been applied across a large range of temporal and spatial scales including many at which the validity of the assumption is likely to be violated. However, the errors associated with improperly applying SSA to estimate C turnover time and its covariance with climate as well as ecosystem C sequestrations have yet to be fully quantified. Here, we developed a novel model‐data fusion framework and systematically analyzed the SSA ‐induced biases using time‐series data collected from 10 permanent forest plots in the eastern China monsoon region. The results showed that (a) the SSA significantly underestimated mean turnover times ( MTT s) by 29%, thereby leading to a 4.83‐fold underestimation of the net ecosystem productivity ( NEP ) in these forest ecosystems, a major C sink globally; (b) the SSA ‐induced bias in MTT and NEP correlates negatively with forest age, which provides a significant caveat for applying the SSA to young‐aged ecosystems; and (c) the sensitivity of MTT to temperature and precipitation was 22% and 42% lower, respectively, under the SSA . Thus, under the expected climate change, spatiotemporal changes in MTT are likely to be underestimated, thereby resulting in large errors in the variability of predicted global NEP . With the development of observation technology and the accumulation of spatiotemporal data, we suggest estimating MTT s at the disequilibrium state via long‐term data assimilation, thereby effectively reducing the uncertainty in ecosystem C sequestration estimations and providing a better understanding of regional or global C cycle dynamics and C‐climate feedback.

Transcriptome analysis of Panax zingiberensis identifies genes encoding oleanolic acid glucuronosyltransferase involved in the biosynthesis of oleanane-type ginsenosides - Qing-Yan Tang; Geng Chen; Wan-Ling Song; Wei Fan; Kun-Hua Wei; Si-Mei He; Guang-Hui Zhang; Jun-Rong Tang; Ying Li; Yuan Lin; Sheng-Chao Yang (Planta, 2019)

Angiogenesis in pancreatic cancer: current research status and clinical implications - Shuo Li; Hua-Xiang Xu; Chun-Tao Wu; Wen-Quan Wang; Wei Jin; He-Li Gao; Hao Li; Shi-Rong Zhang; Jin-Zhi Xu; Zi-Hao Qi; Quan-Xing Ni; Xian-Jun Yu; et al. (Angiogenesis, 2019)

Deep sequencing of small RNAs from 11 tissues of grass carp Ctenopharyngodon idella and discovery of sex‐related microRNAs - Liangming Chen; Rong Huang; Denghui Zhu; Cheng Yang; Libo He; Yongming Li; Lanjie Liao; Zuoyan Zhu; Yaping Wang (Journal of Fish Biology, 2019)
This research identified 169 known microRNAs (miRNAs), 380 novel miRNAs, and 30,538 targets in 11 tissues (blood, brain, derma, gill, heart, intestine, kidney, liver, muscle, pronephros, and spleen) from grass carp Ctenopharyngodon idella with high‐throughput sequencing (HTS). Transcripts per million (TPM) expression analysis detected 41 brain‐enriched miRNAs (accounting for 61.19% of all tissue‐enriched miRNAs). Real‐time quantitative PCR (RT‐qPCR) confirmed that 21 of 24 randomly selected tissue‐enriched miRNAs from the TPM analysis were indeed tissue‐enriched ( P dmrt ) involved in sex differentiation. RT‐qPCR revealed that cid‐miR ‐138 was more highly expressed in testis than in ovary ( P dmrt4a ( P cid‐miR ‐138– dmrt4a in neuroendocrine mechanisms related to brain‐pituitary networks during sex development. The discovery of miRNAs from 11 C. idella tissues expands the available fish mi R NA database, and enhances our understanding of the role of sex‐related miRNAs in tissue differentiation and maintenance of specific tissue functions in fishes.

A Longitudinal Functional Magnetic Resonance Imaging Study of Working Memory in Patients Following a Transient Ischemic Attack: A Preliminary Study - Wei Su; Jian Guo; Yun Zhang; Jie Zhou; Ning Chen; Muke Zhou; Rong Li; Huafu Chen; Li He (Neuroscience Bulletin, 2018)

Comparative proteomic analysis of Nostoc flagelliforme reveals the difference in adaptive mechanism in response to different ultraviolet-B radiation treatments - Shi-gang Shen; Rong-jun Guo; Rong-rong Yan; Yi-kai Wu; Dong-xue Zhao; Ya-hui Lin; He-xin Lv; Shi-ru Jia; Pei-pei Han (Molecular Biology Reports, 2018)

Changes in gene and genotype frequencies during the development of the grass carp Ctenopharyngodon idella - LiB. He; Lv Xiong; AiD. Zhang; YongM. Li; Rong Huang; LanJ. Liao; ZuoY. Zhu; YaP. Wang (Journal of Fish Biology, 2018)
In this study, a full‐sib population of Ctenopharyngodon idella was constructed and approximately 500 C. idella individuals were sampled at four early developmental stages (hatching, first feeding, juvenile fish and young fish). Four DNA pools were constructed and subjected to next‐generation sequencing. On the basis of the identification of single nucleotide polymorphisms (SNP), changes in gene and genotype frequencies during the developmental progress of C. idella were revealed, which indicates that death during the early developmental stage is not a random process. These findings will establish the basis for further studies performed for identifying superior alleles or genotypes as target markers for molecular breeding.

Association between serum somatostatin levels and glucose-lipid metabolism in the Jino ethnic minority and Han Chinese population - Shiyun Wang; Rong Zhang; Xuhong Hou; Fusong Jiang; Jie Wang; Zhen He; Feng Jiang; Cheng Hu; Weiping Jia (Science China Life Sciences, 2018)

Frond transformation system mediated by Agrobacterium tumefaciens for Lemna minor - Gui-Li Yang; Yang Fang; Ya-Liang Xu; Li Tan; Qi Li; Yang Liu; Fan Lai; Yan-Ling Jin; An-Ping Du; Kai-Ze He; Xin-Rong Ma; Hai Zhao (Plant Molecular Biology, 2018)

Diversity of herbaceous plants and bacterial communities regulates soil resistome across forest biomes - Hang‐Wei Hu; Jun‐Tao Wang; Brajesh K. Singh; Yu‐Rong Liu; Yong‐Liang Chen; Yu‐Jing Zhang; Ji‐Zheng He (Environmental Microbiology, 2018)
Summary Antibiotic resistance is ancient and prevalent in natural ecosystems and evolved long before the utilization of synthetic antibiotics started, but factors influencing the large‐scale distribution patterns of natural antibiotic resistance genes (ARGs) remain largely unknown. Here, a large‐scale investigation over 4000 km was performed to profile soil ARGs, plant communities and bacterial communities from 300 quadrats across five forest biomes with minimal human impact. We detected diverse and abundant ARGs in forests, including over 160 genes conferring resistance to eight major categories of antibiotics. The diversity of ARGs was strongly and positively correlated with the diversity of bacteria, herbaceous plants and mobile genetic elements (MGEs). The ARG composition was strongly correlated with the taxonomic structure of bacteria and herbs. Consistent with this strong correlation, structural equation modelling demonstrated that the positive effects of bacterial and herb communities on ARG patterns were maintained even when simultaneously accounting for multiple drivers (climate, spatial predictors and edaphic factors). These findings suggest a paradigm that the interactions between aboveground and belowground communities shape the large‐scale distribution of soil resistomes, providing new knowledge for tackling the emerging environmental antibiotic resistance.

Selection of growth-related genes and dominant genotypes in transgenic Yellow River carp Cyprinus carpio L. - Lifei Luo; Rong Huang; Aidi Zhang; Cheng Yang; Liangming Chen; Denghui Zhu; Yongming Li; Libo He; Lanjie Liao; Zuoyan Zhu; Yaping Wang (Functional & Integrative Genomics, 2018)

Soil nutrients in relation to vertical roots distribution in the riparian zone of Three Gorges Reservoir, China - Rong-hua Zhong; Jin-ming Hu; Yu-hai Bao; Fei Wang; Xiu-bin He (Journal of Mountain Science, 2018)

Mixed Cadzow filtering method in fractional Fourier domain - Zhong-Lin Cao; Jun-Xing Cao; Fu-Rong Wu; Guang-Ming He; Qiang Zhou; Yu-Lin Wu (Applied Geophysics, 2018)

Nutrient Decomposition Rate and Sugarcane Yield as Influenced by Mung Bean Intercropping and Crop Residue Recycling - Tie-Guang He; Li-Rong Su; Yang-Rui Li; Tian-Ming Su; Fang Qin; Qin Li (Sugar Tech, 2018)

Design, synthesis and biological evaluation of novel furoxan-based coumarin derivatives as antitumor agents - Zhuo Zhang; Zhi-Wei Bai; Yong Ling; Li-Qin He; Peng Huang; Hong-Xia Gu; Rong-Feng Hu (Medicinal Chemistry Research, 2018)

Anomalous gray matter structural networks in recent onset post-traumatic stress disorder - Shun Qi; Yun-Feng Mu; Long-Biao Cui; Jian Zhang; Fan Guo; Qing-Rong Tan; Mei Shi; Kang Liu; Yi-Bin Xi; Nan-Yin Zhang; Xiao-Liang Zhang; Yong He; et al. (Brain Imaging and Behavior, 2018)

Discovery of a novel multifunctional carbazole–aminoquinoline dimer for Alzheimer's disease: copper selective chelation, anti-amyloid aggregation, and neuroprotection - Xiao Zhang; Ying Wang; Sheng-nan Wang; Qiu-he Chen; Ya-lin Tu; Xiao-hong Yang; Jing-kao Chen; Jin-wu Yan; Rong-biao Pi; Yan Wang (Medicinal Chemistry Research, 2018)

Superabsorbent polymers influence soil physical properties and increase potato tuber yield in a dry-farming region - Xianqing Hou; Rong Li; Wenshou He; Xiaohua Dai; Kun Ma; Yi Liang (Journal of Soils and Sediments, 2018)

Schinzel–Giedion syndrome: a novel case, review and revised diagnostic criteria - Wei-Liang Liu; Zhi-Xu He; Fang Li; Rong Ai; Hong-Wei Ma (Journal of Genetics, 2018)

Cyclooxygenase-2 (COX-2) polymorphism rs689466 may contribute to the increased susceptibility to post-traumatic osteomyelitis in Chinese population - Lei Wang; Nan Jiang; Qing-rong Lin; Cheng-he Qin; Yan-jun Hu; Bin Yu (Infectious Diseases, 2017)

Lipid accumulation and anti-rotifer robustness of microalgal strains isolated from Eastern China - Cheng Yuan; Yan-Lin Zheng; Wan-Lu Zhang; Ru He; Yong Fan; Guang-Rong Hu; Fu-Li Li (Journal of Applied Phycology, 2017)

Injectable Sustained-Release Depots of PLGA Microspheres for Insoluble Drugs Prepared by hot-Melt Extrusion - Yuting Guo; Yunning Yang; Luying He; Rong Sun; Chenguang Pu; Bin Xie; Haibing He; Yu Zhang; Tian Yin; Yanjiao Wang; Xing Tang (Pharmaceutical Research, 2017)

Two new Anti-TMV active chalconoid analogues from the root of Phyllanthus emblica - He Yan; Li Rong Han; Xing Zhang; Jun Tao Feng (Natural Product Research, 2017)

Dissipation behavior and risk assessment of butralin in soybean and soil under field conditions - Congdi Li; Rong Liu; Li Li; Wei Li; Yujian He; Longfei Yuan (Environmental Monitoring and Assessment, 2017)

Responses of soil nitrous oxide production and abundances and composition of associated microbial communities to nitrogen and water amendment - Qing Wang; Yu-Rong Liu; Cui-Jing Zhang; Li-Mei Zhang; Li-Li Han; Ju-Pei Shen; Ji-Zheng He (Biology and Fertility of Soils, 2017)

UPregulated single-stranded DNA-binding protein 1 induces cell chemoresistance to cisplatin in lung cancer cell lines - Xiang Zhao; Rong He; Yu Liu; Yongkai Wu; Leitao Kang (Molecular and Cellular Biochemistry, 2017)

Involvement of the miR-462/731 cluster in hypoxia response in Megalobrama amblycephala - Cui-Hong Huang; Nan Chen; Chun-Xiao Huang; Bao Zhang; Meng Wu; Lei He; Hong Liu; Rong Tang; Wei-Min Wang; Huan-Ling Wang (Fish Physiology and Biochemistry, 2017)

Fruit and vegetable consumption and risk of cardiovascular disease: A meta-analysis of prospective cohort studies - Jian Zhan; Yu-Jian Liu; Long-Biao Cai; Fang-Rong Xu; Tao Xie; Qi-Qiang He (Critical Reviews in Food Science and Nutrition, 2017)

Diversity of Eukaryotic Algae in Propylene Oxide Saponification Wastewater Activated Sludge - Rong He; Xiangyu Fan; Pengfei Gu; Yan Ji; Junyu Shen; Ruirui Li; Yumei Li; Qiang Li (Water Conservation Science and Engineering, 2017)

NaCl stress induces CsSAMs gene expression in Cucumis sativus by mediating the binding of CsGT-3b to the GT-1 element within the CsSAMs promoter - Li-Wei Wang; Mei-Wen He; Shi-Rong Guo; Min Zhong; Sheng Shu; Jin Sun (Planta, 2017)

Bispectral index-guided sedation in transfemoral transcatheter aortic valve implantation: a retrospective control study - Wei He; Rong-rong Huang; Qing-yu Shi; Xian-bao Liu; Jian-an Wang; Min Yan (Journal of Zhejiang University-SCIENCE B, 2017)

Synthesis and evaluation of multifunctional ferulic and caffeic acid dimers for Alzheimer’s disease - Xi-xin He; Xiao-hong Yang; Rui-ying Ou; Ying Ouyang; Sheng-nan Wang; Zi-wei Chen; Shi-jun Wen; Rong-biao Pi (Natural Product Research, 2017)

Quinone/hydroquinone meroterpenoids with antitubercular and cytotoxic activities produced by the sponge-derived fungus Gliomastix sp. ZSDS1-F7 - Wei-Jun He; Xiao-Jiang Zhou; Xiao-Chu Qin; Yong-Xin Mai; Xiu-Ping Lin; Sheng-Rong Liao; Bin Yang; Tianyu Zhang; Zheng-Chao Tu; Jun-Feng Wang; Yonghong Liu (Natural Product Research, 2017)

Use of electroacupuncture and transcutaneous electrical acupoint stimulation in reproductive medicine: a group consensus - Fan Qu; Rong Li; Wei Sun; Ge Lin; Rong Zhang; Jing Yang; Li Tian; Guo-gang Xing; Hui Jiang; Fei Gong; Xiao-yan Liang; Yan Meng; et al. (Journal of Zhejiang University-SCIENCE B, 2017)

The dynamics of landscape-scale ecological connectivity based on least-cost model in Dongshan Island, China - Li-yun Wu; Dong-jin He; Wei-bin You; Zhi-rong Ji; Yong Tan; Li-li Zhao (Journal of Mountain Science, 2017)

Abnormal O-GlcNAcylation of Pax3 Occurring from Hyperglycemia-Induced Neural Tube Defects Is Ameliorated by Carnosine But Not Folic Acid in Chicken Embryos - Rui-Rong Tan; Yi-Fang Li; Shi-Jie Zhang; Wen-Shan Huang; Bun Tsoi; Dan Hu; Xin Wan; Xuesong Yang; Qi Wang; Hiroshi Kurihara; Rong-Rong He (Molecular Neurobiology, 2017)

Hepatic expression of transcription factors affecting developmental regulation of UGT1A1 in the Han Chinese population - Ya-li Nie; Hang He; Jiang-feng Li; Xiang-guang Meng; Liang Yan; Pei Wang; Shu-jie Wang; Hong-zheng Bi; Li-rong Zhang; Quan-cheng Kan (European Journal of Clinical Pharmacology, 2017)

Three-Dimensional Tricuspid Annular Motion Analysis from Cardiac Magnetic Resonance Feature-Tracking - Shuang Leng; Meng Jiang; Xiao-Dan Zhao; John Carson Allen; Ghassan S. Kassab; Rong-Zhen Ouyang; Ju-Le Tan; Ben He; Ru-San Tan; Liang Zhong (Annals of Biomedical Engineering, 2016)

Brain natriuretic peptide for prevention of contrast-inducednephropathy: a meta-analysis of randomized controlled trials - Xue-biao Wei; Lei Jiang; Xin-rong Liu; Dan-qing Yu; Ning Tan; Ji-yan Chen; Ying-ling Zhou; Peng-cheng He; Yuan-hui Liu (European Journal of Clinical Pharmacology, 2016)

Cloning and characterization of Bax1 and Bax2 genes of Ctenopharyngodon idellus and evaluation of transcript expression in response to grass carp reovirus infection - Hao Wang; Libo He; Yongyan Pei; Pengfei Chu; Rong Huang; Yongming Li; Lanjie Liao; Zuoyan Zhu; Yaping Wang (Fish Physiology and Biochemistry, 2016)

Pseudomonas syringae pv. Actinidiae isolated from non-kiwifruit plant species in China - Pu Liu; Shizhou Xue; Rong He; Jiayong Hu; Xiaojie Wang; Bing Jia; Lorenzo Gallipoli; Angelo Mazzaglia; Giorgio M. Balestra; Liwu Zhu (European Journal of Plant Pathology, 2016)

To perceive a perfect Dora Maar in peripheral vision - Rong-Ding He; Tao Su; Yang Yang; Ying Liu; Yan Wei; Rong-Qiao He (Science China Life Sciences, 2016)

Chromosome elimination of hexaploid common wheat mediated by interaction between Chinese Spring cytoplasm and a genetic factor(s) on chromosome arm 1BL of wild emmer - Y. R. Jiang; M. D. He; M. Q. Ding; J. K. Rong (Euphytica, 2016)

Chitooligosaccharide Inhibits Scar Formation and Enhances Functional Recovery in a Mouse Model of Sciatic Nerve Injury - Hongping Hou; Lihai Zhang; Zuguang Ye; Jianrong Li; Zijian Lian; Chao Chen; Rong He; Bo Peng; Qihua Xu; Guangping Zhang; Wenbiao Gan; Peifu Tang (Molecular Neurobiology, 2016)

Characterization of the life cycle of the tick Haemaphysalis tibetensis under field conditions in Qinghai-Tibet plateau - Ming Liu; Tuo Li; Zhi-Jun Yu; Xiao-He Gao; Chun-Wei Zuo; Rong-Rong Wang; Ning-Xin Li; Hui Wang; Jing-Ze Liu (Experimental and Applied Acarology, 2016)

Erratum to: An Up-regulation of IRF-1 After a Spinal Cord Injury: Implications for Neuronal Apoptosis - Jian Zhao; Chen Chen; Jian-Ru Xiao; Hai-Feng Wei; Xu-hui Zhou; Xing-Xing Mao; Wei-dong Zhang; Rong Qian; Xin-lei Chen; Ming-qing He; Xiao-Wei Yu; Jian Zhao (Journal of Molecular Neuroscience, 2016)

Hydrochemical characteristics and quality assessment of deep groundwater from the coal-bearing aquifer of the Linhuan coal-mining district, Northern Anhui Province, China - Man-li Lin; Wei-hua Peng; He-rong Gui (Environmental Monitoring and Assessment, 2016)

The Inhibition Effect and Excessive Carbon Flux Resulting from Blocking Anthocyanin Biosynthesis Under Darkness in Begonia semperflorens - Kai Ming Zhang; Mei Li Guo; Dan He; Rong Hua Wu; Yong Hua Li (Journal of Plant Growth Regulation, 2016)

Estimation of soil reinforcement by the roots of four post-dam prevailing grass species in the riparian zone of Three Gorges Reservoir, China - Rong-hua Zhong; Xiu-bin He; Yu-hai Bao; Qiang Tang; Jin-zhang Gao; Dan-dan Yan; Ming-feng Wang; Yu Li (Journal of Mountain Science, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Downregulation of ubiquitin-specific protease 14 (USP14) inhibits breast cancer cell proliferation and metastasis, but promotes apoptosis - Lianxin Zhu; Shuyun Yang; Song He; Fulin Qiang; Jing Cai; Rong Liu; Changjiang Gu; Zengya Guo; Chen Wang; Wei Zhang; Chunhui Zhang; Yingying Wang (Journal of Molecular Histology, 2016)

Spy1 participates in the proliferation and apoptosis of epithelial ovarian cancer - Shumin Lu; Rong Liu; Min Su; Yingze Wei; Shuyun Yang; Song He; Xia Wang; Fulin Qiang; Chen Chen; Shuyang Zhao; Weiwei Zhang; Pan Xu; et al. (Journal of Molecular Histology, 2016)

Erratum to: First molecular detection of porcine circovirus type 2 in bovids in China - Shao-Lun Zhai; Rui-Ai Chen; Sheng-Nan Chen; Xiao-Hui Wen; Dian-Hong Lv; Da-Cheng Wu; Jie Yuan; Zhong Huang; Xiu-Rong Zhou; Man-Lin Luo; Dong-Sheng He; Wen-Kang Wei (Virus Genes, 2016)

Lentibacillus amyloliquefaciens sp. nov., a halophilic bacterium isolated from saline sediment sample - Jing-Li Wang; Ke-Dong Ma; Yan-Wei Wang; Hui-Min Wang; Yan-Bin Li; Shan Zhou; Xiao-Rong Chen; De-Long Kong; Xiang Guo; Ming-Xiong He; Zhi-Yong Ruan (Antonie van Leeuwenhoek, 2016)

Genetic fine mapping and candidate gene analysis of the Gossypium hirsutum Ligon lintless-1 (Li1) mutant on chromosome 22(D) - Yurong Jiang; Mingquan Ding; Yuefen Cao; Fen Yang; Hua Zhang; Shae He; Huaqin Dai; Huanfeng Hao; Junkang Rong (Molecular Genetics and Genomics, 2015)

An Up-regulation of IRF-1 After a Spinal Cord Injury: Implications for Neuronal Apoptosis - Jian Zhao; Chen Chen; Jian-Ru Xiao; Hai-Feng Wei; Xu-hui Zhou; Xing-Xing Mao; Wei-dong Zhang; Rong Qian; Xin-lei Chen; Ming-qing He; Xiao-Wei Yu; Jian Zhao (Journal of Molecular Neuroscience, 2015)
IRF-1, a kind of transcription factor, is expressed in many cell types, except in early embryonal cells. IRF-1 has played an essential role in various physiological and pathological processes, including tumor immune surveillance, viral infection, development of immunity system and pro-inflammatory injury. However, the expression and function of IRF-1 in spinal cord injury (SCI) are still unknown. In this study, we have performed an acute SCI model in adult rats and investigated the dynamic changes of IRF-1 expression in the spinal cord. Western blot have shown that IRF-1 protein levels gradually increased, reaching a peak at day 3 and then gradually declined to a normal level at day 14 after SCI. Double immunofluorescence staining showed that IRF-1 immunoreactivity was found in neurons, but not in astrocytes and microglia. Additionally, colocalization of IRF-1/active caspase-3 was detected in neurons. In vitro, IRF-1 depletion, by short interfering RNA, obviously decreases neuronal apoptosis. In conclusion, this is the first description of IRF-1 expression in spinal cord injury. Our results suggested that IRF-1 might play crucial roles in CNS pathophysiology after SCI.

Characteristics of gravity anomalies and prediction of volcanosedimentary boron deposit distribution in the Xiongba area, Tibet - Li-Rong Song; Chang-Qing Yu; Gui-Hua Li; Yang-Yang Feng; Jun-Jie He (Applied Geophysics, 2015)

New cytotoxic and anti-inflammatory compounds isolated from Morus alba L. - Jing Qin; Min Fan; Juan He; Xing-De Wu; Li-Yan Peng; Jia Su; Xiao Cheng; Yan Li; Ling-Mei Kong; Rong-Tao Li; Qin-Shi Zhao (Natural Product Research, 2015)

Determination and Method Validation of the New Sulfone Fungicide 2-(4-Fluorophenyl)-5-Methylsulfonyl-1,3,4-Oxadiazole in Tomato and Soil by UPLC in Field Trial Samples from Guizhou Province, China - Rong Linghu; Mingjiao Jin; Sizhu Pan; Jing Zhang; Mingming Tang; Jin He; Kankan Zhang; Deyu Hu (Bulletin of Environmental Contamination and Toxicology, 2015)

Modified method for estimating organic carbon density in discontinuous Karst soil using ground-penetrating radar and geostatistics - Lei Li; Yin-hang Xia; Shu-juan Liu; Wei Zhang; Xiang-bi Chen; Hua Zheng; Hu-sen Qiu; Xun-yang He; Yi-rong Su (Journal of Mountain Science, 2015)

A Real-time monitoring and early warning system for landslides in Southwest China - Neng-pan Ju; Jian Huang; Run-qiu Huang; Chao-yang He; Yan-rong Li (Journal of Mountain Science, 2015)

The involvement of c-Myc in the DNA double-strand break repair via regulating radiation-induced phosphorylation of ATM and DNA-PKcs activity - Fengmei Cui; Rong Fan; Qiu Chen; Yongming He; Man Song; Zengfu Shang; Shimeng Zhang; Wei Zhu; Jianping Cao; Hua Guan; Ping-Kun Zhou (Molecular and Cellular Biochemistry, 2015)

Schwann cells induce Proliferation and Migration of Oligodendrocyte Precursor Cells Through Secretion of PDGF-AA and FGF-2 - Yue-Juan Chen; Jing-Xing Zhang; Lin Shen; Qi Qi; Xiao-Xin Cheng; Zheng-Rong Zhong; Zhi-Quan Jiang; Rui Wang; He-Zuo Lü; Jian-Guo Hu (Journal of Molecular Neuroscience, 2015)

The bioavailability and adverse impacts of lead and decabromodiphenyl ether on soil microbial activities - Lei Chen; Wei Zhang; Rong Zhang; Kuangfei Lin; Lei He; Liqun Wu (Environmental Science and Pollution Research, 2015)

Construction of cDNA library from Prunus campanulata leaves and preliminary expressed sequence tag (EST) analysis during cold stress - Ying-Hui Zhang; Jun-Dong Rong; Li-Guang Chen; Ling-Yan Chen; Tian-You He; Yu-Shan Zheng (Biologia, 2015)

Genetic diversity revealed by morphological traits and ISSR markers in 48 Okras (Abelmoschus escullentus L.) - Cong-Ying Yuan; Ping Wang; Pang-Pang Chen; Wen-Jun Xiao; Cheng Zhang; Shuai Hu; Ping Zhou; Hong-Ping Chang; Zhuang He; Rong Hu; Xiu-Tao Lu; Jia-Zhuo Ye; et al. (Physiology and Molecular Biology of Plants, 2015)

Long-term nickel exposure altered the bacterial community composition but not diversity in two contrasting agricultural soils - Jing Li; Hang-Wei Hu; Yi-Bing Ma; Jun-Tao Wang; Yu-Rong Liu; Ji-Zheng He (Environmental Science and Pollution Research, 2015)

Molecular characterization of a transcriptionally active Ty1/copia-like retrotransposon in Gossypium - Yuefen Cao; Yurong Jiang; Mingquan Ding; Shae He; Hua Zhang; Lifeng Lin; Junkang Rong (Plant Cell Reports, 2015)

Protective effect of adiponectin on paraquat-induced pulmonary fibrosis in mice - Rong Yao; Yarong He; Zhi Zeng; Zongan Liang; Yu Cao (Molecular & Cellular Toxicology, 2015)

Establishment and characterization of a novel cell line from midgut tissue of Helicoverpa armigera (Lepidoptera: Noctuidae) - Jianghuai Li; Fei He; Yongbo Yang; Yutao Xiao; Rong Peng; Hanchao Yao; Xianchun Li; Jianxin Peng; Huazhu Hong; Kaiyu Liu (In Vitro Cellular & Developmental Biology - Animal, 2015)

Different influences of field aging on nickel toxicity to Folsomia candida in two types of soil - Yu-Rong Liu; Jing Li; Ji-Zheng He; Yi-Bing Ma; Yuan-Ming Zheng (Environmental Science and Pollution Research, 2015)

Isolation and characterization of 18 microsatellites for Aconitum vilmorinianum Kom. (Ranunculaceae) using next-generation sequencing technology - Jun He; Zhi-Rong Zhang; Jun-Bo Yang; Hong Wang; Jing Meng (Conservation Genetics Resources, 2015)

Paenibacillus vini sp. nov., isolated from alcohol fermentation pit mud in Sichuan Province, China - Xiao-Rong Chen; Cheng-Bin Shao; Yan-Wei Wang; Ming-Xiong He; Ke-Dong Ma; Hui-Min Wang; De-Long Kong; Xiang Guo; Yi-Qing Zhou; Zhi-Yong Ruan (Antonie van Leeuwenhoek, 2015)

Isolation and the interaction between a mineral-weathering Rhizobium tropici Q34 and silicate minerals - Rong Rong Wang; Qi Wang; Lin Yan He; Gang Qiu; Xia Fang Sheng (World Journal of Microbiology and Biotechnology, 2015)

Communities of gamasid mites on Eothenomys miletus in southwest China - Pei-Ying Peng; Xian-Guo Guo; Wen-Yu Song; Peng Hou; Yun-Ji Zou; Rong Fan; Xue-Song He (Biologia, 2015)

Anti-herpes simplex virus activity of polysaccharides from Eucheuma gelatinae - Fujun Jin; Cuiqin Zhuo; Zhe He; Huailin Wang; Wei Liu; Rong Zhang; Yifei Wang (World Journal of Microbiology and Biotechnology, 2015)

Protective effects of hydroxysafflor yellow A (HSYA) on alcohol-induced liver injury in rats - Yanhao He; Qiang Liu; Yanxiang Li; Xiaofeng Yang; Weirong Wang; Tingting Li; Wei Zhang; Yuexin Cui; Chaoyun Wang; Rong Lin (Journal of Physiology and Biochemistry, 2015)

Biological Roles of Olfactory Ensheathing Cells in Facilitating Neural Regeneration: A Systematic Review - Hao Yang; Bao-Rong He; Ding-Jun Hao (Molecular Neurobiology, 2015)

Impacts of shape and height of upstream roof on airflow and pollutant dispersion inside an urban street canyon - Yuan-dong Huang; Wen-rong He; Chang-Nyung Kim (Environmental Science and Pollution Research, 2015)

Removal of antibiotics and antibiotic resistance genes in rural wastewater by an integrated constructed wetland - Jun Chen; You-Sheng Liu; Hao-Chang Su; Guang-Guo Ying; Feng Liu; Shuang-Shuang Liu; Liang-Ying He; Zhi-Feng Chen; Yong-Qiang Yang; Fan-Rong Chen (Environmental Science and Pollution Research, 2015)

Fibroblast Growth Factor 4 Is Required but not Sufficient for the Astrocyte Dedifferentiation - Guo-Dong Feng; Bao-Rong He; Fan Lu; Lin-Hong Liu; Lingling Zhang; Bo Chen; Zu-Ping He; Ding-Jun Hao; Hao Yang (Molecular Neurobiology, 2014)

First molecular detection of porcine circovirus type 2 in bovids in China - Shao-Lun Zhai; Rui-Ai Chen; Sheng-Nan Chen; Xiao-Hui Wen; Dian-Hong Lv; Da-Cheng Wu; Jie Yuan; Zhong Huang; Xiu-Rong Zhou; Man-Lin Luo; Dong-Sheng He; Wen-Kang Wei (Virus Genes, 2014)

Characterization of the biological properties and complete genome sequence analysis of a cattle-derived rabies virus isolate from the Guangxi province of southern China - Hai-Bo Tang; Zhuan-Ling Lu; Yi-Zhi Zhong; Xiao-Xia He; Tao-Zhen Zhong; Yan Pan; Xian-Kai Wei; Yang Luo; Su-Huan Liao; Nobuyuki Minamoto; Ting Rong Luo (Virus Genes, 2014)

Three dimensional reconstruction of bone-cartilage transitional structures based on semi-automatic registration and automatic segmentation of serial sections - Hua Guo; Zheng-Wei Xu; Bao-Rong He; Ding-Jun Hao; Wei-Guo Bian (Tissue Engineering and Regenerative Medicine, 2014)

Changes in weathering effectiveness and community of culturable mineral-weathering bacteria along a soil profile - Qi Wang; Rong Rong Wang; Lin Yan He; Jia Jia Lu; Zhi Huang; Xia Fang Sheng (Biology and Fertility of Soils, 2014)

Fungus Exposed Solenopsis invicta Ants Benefit from Grooming - Hua-long Qiu; Li-hua Lu; Qing-xing Shi; Yu-rong He (Journal of Insect Behavior, 2014)

Response of bacterial pdo1, nah, and C12O genes to aged soil PAH pollution in a coke factory area - Xue-Mei Han; Yu-Rong Liu; Yuan-Ming Zheng; Xiao-Xia Zhang; Ji-Zheng He (Environmental Science and Pollution Research, 2014)

Response of ammonia-oxidizing archaea and bacteria to long-term industrial effluent-polluted soils, Gujarat, Western India - Gangavarapu Subrahmanyam; Ju-Pei Shen; Yu-Rong Liu; Gattupalli Archana; Ji-Zheng He (Environmental Monitoring and Assessment, 2014)

A novel method for the rapid detection of benzo(a)pyrene in liquid milk by dimethyl sulfoxide selectively enhanced synchronous fluorescence spectrometry - Li-Rong Lin; He-Dong Luo; Xiu-Ying Li; Na Li; Na Zhou; Yu-Zhu Jia; Yi-Hong Liu; Yao-Qun Li (Food Additives & Contaminants: Part A, 2014)

Phagocytic Removal of Neuronal Debris by Olfactory Ensheathing Cells Enhances Neuronal Survival and Neurite Outgrowth via p38MAPK Activity - Bao-Rong He; Song-Tao Xie; Ming-Mei Wu; Ding-Jun Hao; Hao Yang (Molecular Neurobiology, 2014)

Interval Q inversion based on zero-offset VSP data and applications - Gu-Lan Zhang; Xi-Ming Wang; Zhen-Hua He; Jun-Xing Cao; Ke-En Li; Jiao-Jun Rong (Applied Geophysics, 2014)

Effects of land cover on soil organic carbon stock in a karst landscape with discontinuous soil distribution - Xiang-bi Chen; Hua Zheng; Wei Zhang; Xun-yang He; Lei Li; Jin-shui Wu; Dao-you Huang; Yi-rong Su (Journal of Mountain Science, 2014)

MiR-200a is involved in proliferation and apoptosis in the human endometrial adenocarcinoma cell line HEC-1B by targeting the tumor suppressor PTEN - Rong Li; Jun-lin He; Xue-mei Chen; Chun-Lan Long; De-Hui Yang; Yu-Bin Ding; Hong-Bo Qi; Xue-Qing Liu (Molecular Biology Reports, 2014)

Molecular characterisation and expression profiling of the ENO1 gene in the ovarian follicle of the Sichuan white goose - Bo Kang; Dong Mei Jiang; Lin Bai; Hui He; Rong Ma (Molecular Biology Reports, 2014)

Seismic attenuation relationship with homogeneous and heterogeneous prediction-error variance models - He-Qing Mu; Rong-Rong Xu; Ka-Veng Yuen (Earthquake Engineering and Engineering Vibration, 2014)

Effect of Suaeda salsa on Soil Aggregate-Associated Organic Carbon and Nitrogen in Tidal Salt Marshes in the Liaohe Delta, China - Rong Mao; Xin-Hou Zhang; He-Nan Meng (Wetlands, 2014)

Environmental Investigations and Molecular Typing of Aspergillus in a Chinese Hospital - Jun-hong Ao; Zhen-feng Hao; He Zhu; liang Wen; Rong-ya Yang (Mycopathologia, 2014)

Isolation from Proteus mirabilis of a novel class I 5-enopyruvylshikimate-3-phosphate synthase with glyphosate tolerance in transgenic Arabidopsis thaliana - Yong-Sheng Tian; Xiao-Fen Jin; Jing Xu; Jing Han; Wei Zhao; Xiao-Yan Fu; Ri-He Peng; Rong-Tan Wang; Quan-Hong Yao (Acta Physiologiae Plantarum, 2014)

Silencing Pax3 by shRNA inhibits the proliferation and differentiation of duck (Anas platyrhynchos) myoblasts - Rong-Ping Zhang; He-He Liu; Hao-Han Wang; Yan Wang; Chun-Chun Han; Liang Li; Hua He; Heng-Yong Xu; Feng Xu; Ji-Wen Wang (Molecular and Cellular Biochemistry, 2014)

Enhanced Oxidation Stability of Quasi Core-Shell Alloyed CdSeS Quantum Dots Prepared Through Aqueous Microwave Synthesis Technique - Hong-Ju Zhan; Pei-Jiang Zhou; Rong Ma; Xi-Jing Liu; Yu-Ning He; Chuan-Yun Zhou (Journal of Fluorescence, 2014)

Linkage between community diversity of sulfate-reducing microorganisms and methylmercury concentration in paddy soil - Yu-Rong Liu; Yuan-Ming Zheng; Li-Mei Zhang; Ji-Zheng He (Environmental Science and Pollution Research, 2014)

Application of Endobronchial Ultrasound-Guided Transbronchial Needle Aspiration in the Management of Mediastinal and Hilar Lymphadenopathy Without Intrapulmonary Mass: Experience from the Largest Cancer Center of Southern China - Guang-yu Luo; Pei-qiang Cai; Jie-hua He; Jian-jun Li; Yin Li; Hong-bo Shan; Rong Zhang; Xiao-yan Gao; Xiang-ming Lao; Guo-liang Xu (Cell Biochemistry and Biophysics, 2013)

Association of single-nucleotide polymorphisms in the STAT3 gene with autoimmune thyroid disease in Chinese individuals - Ling Xiao; Fatuma-Said Muhali; Tian-tian Cai; Rong-hua Song; Renming Hu; Xiao-hong Shi; Wen-juan Jiang; Dan-Feng Li; Shuang-tao He; Jian Xu; Jin-an Zhang (Functional & Integrative Genomics, 2013)

Down-regulation of human cytomegalovirus UL138, a novel latency-associated determinant, by hcmv-miR-UL36 - Yujing Huang; Ying Qi; Yanping Ma; Rong He; Yaohua Ji; Zhengrong Sun; Qiang Ruan (Journal of Biosciences, 2013)

Differences in oxidative stress, antioxidant systems, and microscopic analysis between regenerating callus-derived protoplasts and recalcitrant leaf mesophyll-derived protoplasts of Citrus reticulata Blanco - Xiaoyong Xu; Gaisheng Xie; Li He; Jiaojiao Zhang; Xiaoling Xu; Rong Qian; Guohua Liang; Ji-Hong Liu (Plant Cell, Tissue and Organ Culture (PCTOC), 2013)

QTL mapping and correlation analysis for 1000-grain weight and percentage of grains with chalkiness in rice - JIAN-MIN BIAN; HUAN SHI; CUI-JUAN LI; CHANG-LAN ZHU; QIU-YING YU; XIAO-SONG PENG; JUN-RU FU; XIAO-PENG HE; XIAO-RONG CHEN; LI-FANG HU; LIN-JUAN OUYANG; HAO-HUA HE (Journal of Genetics, 2013)

Bacterioplankton community structure in the Arctic waters as revealed by pyrosequencing of 16S rRNA genes - Yin-Xin Zeng; Fang Zhang; Jian-Feng He; Sang H. Lee; Zong-Yun Qiao; Yong Yu; Hui-Rong Li (Antonie van Leeuwenhoek, 2013)

Persistence and intergenerational transmission of differentially expressed genes in the testes of intracytoplasmic sperm injection conceived mice - Li-ya Wang; Ning Wang; Fang Le; Lei Li; Le-jun Li; Xiao-zhen Liu; Ying-ming Zheng; Hang-ying Lou; Xiang-rong Xu; Xiao-ming Zhu; Yi-min Zhu; He-feng Huang; et al. (Journal of Zhejiang University-SCIENCE B, 2013)

Influence of ORM1 polymorphisms on the maintenance stable warfarin dosage - Lian Sheng Wang; Jing Jing Shang; Shu Ya Shi; Yan Qing Zhang; Jian Lin; Zhi Hua Guo; Yi Chen Wang; Jie Tang; Jie Liu; Ying Zi Liu; Zhi Li; Zhi Rong Tan; et al. (European Journal of Clinical Pharmacology, 2013)

Diversity of bacteria in surface ice of Austre Lovénbreen glacier, Svalbard - Yin-Xin Zeng; Ming Yan; Yong Yu; Hui-Rong Li; Jian-Feng He; Kun Sun; Fang Zhang (Archives of Microbiology, 2013)

Effects of super absorbent polymers on soil microbial properties and Chinese cabbage (Brassica chinensis) growth - Xi Li; Ji-Zheng He; Yu-Rong Liu; Yuan-Ming Zheng (Journal of Soils and Sediments, 2013)

Molecular epidemiology of PRRSV from China’s Guangxi Province between 2007 and 2009 - Hong-Yun Zhang; Jing-Jing Liang; Xian-Ming Meng; Hui Li; Jian Yang; Li-Juan Su; Hong-Pu Zhang; Lin-Juan Xie; Xiao-Xia He; Yan-Sheng Li; Shan Yin; Xiao-Quan Li; et al. (Virus Genes, 2013)

Tectonic mechanism of the Suining (Ms5.0) earthquake, center of Sichuan Basin, China - Rong-jun Zhou; Yong Li; Laurence Svirchev; Yong-jiu Zhang; Deng-fa He; Yu-lin He; Pei-lin Zhao; Zan-jun Wang; Feng Long; Jin-rong Su; Shi-yuan Wang; Ming-jian Liang; et al. (Journal of Mountain Science, 2013)

Gene cloning and functional analysis of yellow green leaf3 (ygl3) gene during the whole-plant growth stage in rice - Xiaoqing Tian; Yinghua Ling; Likui Fang; Peng Du; Xianchun Sang; Fangming Zhao; Yunfeng Li; Rong Xie; Guanghua He (Genes & Genomics, 2013)

Survival and development of Liaodong oak stump sprouts in the Huanglong Mountains of China six years after three partial harvests - Li Rong; Zhang Wenhui; He Jingfeng; Zhou Jianyun (New Forests, 2013)

Epstein-Barr virus interactions with the Bcl-2 protein family and apoptosis in human tumor cells - Qin Fu; Chen He; Zheng-rong Mao (Journal of Zhejiang University-SCIENCE B, 2013)

Characterization of a Novel Pollen-Specific Promoter from Wheat (Triticum Aestivum L.) - Ling Chen; Yingjie Miao; Cheng Wang; Peipei Su; Tianheng Li; Rong Wang; Xinglong Hao; Guangxiao Yang; Guangyuan He; Chunbao Gao (Plant Molecular Biology Reporter, 2012)

The role of leptin in lipid metabolism in fatty degenerated hepatocytes of the grass carp Ctenopharyngodon idellus - Rong-Hua Lu; Xu-Fang Liang; Min Wang; Yi Zhou; Xiao-Li Bai; Yan He (Fish Physiology and Biochemistry, 2012)

Oxidative Parameters in the Rat Brain of Chronic Mild Stress Model for Depression: Relation to Anhedonia-Like Responses - Chao Wang; He-ming Wu; Xiao-rong Jing; Qiang Meng; Bei Liu; Hua Zhang; Guo-dong Gao (The Journal of Membrane Biology, 2012)

Antioxidant system of tea (Camellia sinensis) leaves in response to phosphorus supply - Zheng-He Lin; Li-Song Chen; Rong-Bing Chen; Fang-Zhou Zhang (Acta Physiologiae Plantarum, 2012)

Soil oxidases recovered faster than hydrolases in a 50-year chronosequence of desert revegetation - Zhi-Shan Zhang; Xue-Jun Dong; Yu-Bin Liu; Xin-Rong Li; Rong-Liang Jia; Yi-Gang Hu; Ming-Zhu He; Lei Huang (Plant and Soil, 2012)

A molecular mechanism underlying ovarian dysfunction of polycystic ovary syndrome: hyperandrogenism induces epigenetic alterations in the granulosa cells - Fan Qu; Fang-Fang Wang; Rong Yin; Guo-Lian Ding; Mohamed El-prince; Qian Gao; Bi-Wei Shi; Hui-Hui Pan; Yi-Ting Huang; Min Jin; Peter C. K. Leung; Jian-Zhong Sheng; et al. (Journal of Molecular Medicine, 2012)

Erratum to: Genetic variation in the carbonyl reductase 3 gene confers risk of type 2 diabetes and insulin resistance: a potential regulator of adipogenesis - Yi-Cheng Chang; Pi-Hua Liu; Yun-Chih Tsai; Yen-Feng Chiu; Shyang-Rong Shih; Low-Tone Ho; Wen-Jane Lee; Chieh-Hua Lu; Thomas Quertermous; J. David Curb; Wei-Jei Lee; Po-Chu Lee; et al. (Journal of Molecular Medicine, 2012)

Genetic variation in the carbonyl reductase 3 gene confers risk of type 2 diabetes and insulin resistance: a potential regulator of adipogenesis - Yi-Cheng Chang; Pi-Hua Liu; Yun-Chih Tsai; Yen-Feng Chiu; Shyang-Rong Shih; Low-Tone Ho; Wen-Jane Lee; Chieh-Hua Lu; Thomas Quertermous; J. David Curb; Wei-Jei Lee; Po-Chu Lee; et al. (Journal of Molecular Medicine, 2012)

Spontaneous retroperitoneal hemorrhage after hemodialysis involving anticoagulant agents - Wen-xing Fan; Zheng-xu Deng; Fang Liu; Rong-bo Liu; Ling He; Bogati Amrit; Li Zang; Jing-wen Li; Xian-rong Liu; Song-min Huang; Ping Fu (Journal of Zhejiang University-SCIENCE B, 2012)

Toxicity of profenofos to the springtail, Folsomia candida, and ammonia-oxidizers in two agricultural soils - Yu-Rong Liu; Yuan-Ming Zheng; Ji-Zheng He (Ecotoxicology, 2012)

Characterization of Prototheca zopfii Associated with Outbreak of Bovine Clinical Mastitis in Herd of Beijing, China - Jian Gao; Han-qi Zhang; Jian-zhong He; Yang-hua He; Shu-mei Li; Rong-guang Hou; Qiao-xing Wu; Yang Gao; Bo Han (Mycopathologia, 2012)

Association between ATM 5557G>A polymorphism and breast cancer risk: a meta-analysis - Chen Mao; Vincent C. H. Chung; Ben-Fu He; Rong-Cheng Luo; Jin-Ling Tang (Molecular Biology Reports, 2012)

Downregulation of OsPK1, a cytosolic pyruvate kinase, by T-DNA insertion causes dwarfism and panicle enclosure in rice - Yan Zhang; Wenkai Xiao; Lijuan Luo; Jinhuan Pang; Wei Rong; Chaozu He (Planta, 2012)

Effects of Schisandra sphenanthera extract on the blood concentration of tacrolimus in renal transplant recipients - Hua-Wen Xin; Qing Li; Xiao-Chun Wu; Yan He; Ai-Rong Yu; Lei Xiong; Ying Xiong (European Journal of Clinical Pharmacology, 2011)

Human cytomegalovirus RL13 gene transcripts in a clinical strain - Mali Li; Yanping Ma; Yaohua Ji; Rong He; Ying Qi; Zhengrong Sun; Ning Wang; Shuang Gao; Qiang Ruan (Virus Genes, 2011)

Erratum to: Olfactory responses of Neoseiulus cucumeris (Acari: Phytoseiidae) to odors of host plants and Frankliniella occidentalis (Thysanoptera: Thripidae)–plant complexes - Feng Zhong; Yu-Rong He; Yan Gao; Guo-Jun Qi; Chen-Yin Zhao; Li-Hua Lu (Arthropod-Plant Interactions, 2011)

Olfactory responses of Neoseiulus cucumeris (Acari: Phytoseiidae) to odors of host plants and Frankliniella occidentalis (Thysanoptera: Thripidae)–plant complexes - Feng Zhong; Yu-Rong He; Yan Gao; Guo-Jun Qi; Chen-Yin Zhao; Li-Hua Lu (Arthropod-Plant Interactions, 2011)

Synthesis of novel 6-triazologlycolipids via click chemistry and their preliminary cytotoxicity assessments - Hai-Lin Zhang; Xiao-Peng He; Li Sheng; Yuan Yao; Wei Zhang; Xiao-Xin Shi; Jia Li; Guo-Rong Chen (Molecular Diversity, 2011)

Production of conjugated linoleic acids by Lactobacillus plantarum strains isolated from naturally fermented Chinese pickles - Pei Liu; Sheng-rong Shen; Hui Ruan; Qian Zhou; Liu-liu Ma; Guo-qing He (Journal of Zhejiang University-SCIENCE B, 2011)

Normal epigenetic inheritance in mice conceived by in vitro fertilization and embryo transfer - Lei Li; Fang Le; Li-ya Wang; Xiang-rong Xu; Hang-ying Lou; Ying-ming Zheng; Jiang-zhong Sheng; He-feng Huang; Fan Jin (Journal of Zhejiang University-SCIENCE B, 2011)

Discovering the distinct inhibitory effects between C4-epimeric glycosyl amino acids: new insight into the development of protein tyrosine phosphatase inhibitors - Xiao-Peng He; Cui Li; Zhi-Zhou Wang; Li-Xin Gao; Xiao-Xin Shi; Yun Tang; Juan Xie; Jia Li; Guo-Rong Chen; Kaixian Chen (Glycoconjugate Journal, 2011)

Trigonella arcuata-associated rhizobia—an Ensifer (Sinorhizobium) meliloti population adapted to a desert environment - Yu Rong He; Jing Yu Wang; En Tao Wang; Gu Feng; Yue Li Chang; Xin Hua Sui; Wen Xin Chen (Plant and Soil, 2011)

G1 cell cycle arrest signaling in hepatic injury after intraperitoneal sepsis in rats - Quan-hui Yang; Da-wei Liu; Xiao-ting Wang; Rong-li Yang; Yan Shi; Yun Long; Hong-zhong Liu; Huai-wu He; Xiang Zhou; Bo Tang (Inflammation Research, 2011)

Monitoring of flow field based on stable isotope geochemical characteristics in deep groundwater - Lu-wang Chen; He-rong Gui; Xiao-xi Yin (Environmental Monitoring and Assessment, 2011)

A new bioorganic fertilizer can effectively control banana wilt by strong colonization with Bacillus subtilis N11 - Nan Zhang; Kai Wu; Xin He; Shu-qing Li; Zhen-hua Zhang; Biao Shen; Xing-ming Yang; Rui-fu Zhang; Qi-wei Huang; Qi-rong Shen (Plant and Soil, 2011)

Earthquake characteristics and building damage in high-intensity areas of Wenchuan earthquake I: Yingxiu town - Chang-Rong He; Ru Zhang; Qun Chen; Sheng-Li Han (Natural Hazards, 2011)

Earthquake characteristics and building damage in high-intensity areas of Wenchuan earthquake II: Dujiangyan and Pengzhou City - Chang-Rong He; Qun Chen; Sheng-Li Han; Ru Zhang (Natural Hazards, 2011)

Genistein alters caffeine exposure in healthy female volunteers - Yao Chen; Chang-Qiong Xiao; Yi-Jing He; Bi-Lian Chen; Guo Wang; Gan Zhou; Wei Zhang; Zhi-Rong Tan; Shan Cao; Li-Ping Wang; Hong-Hao Zhou (European Journal of Clinical Pharmacology, 2011)

Knockdown of ribonuclease inhibitor expression with siRNA in non-invasive bladder cancer cell line BIU-87 promotes growth and metastasis potentials - Junxia Chen; Xi Ou-Yang; Juan Gao; Jun Zhu; Xiaoyan He; Jiang Rong (Molecular and Cellular Biochemistry, 2011)

Methylobacterium soli sp. nov. a methanol-utilizing bacterium isolated from the forest soil - Yan-Ru Cao; Qian Wang; Rong-Xian Jin; Shu-Kun Tang; Yi Jiang; Wen-Xiang He; Hang-Xian Lai; Li-Hua Xu; Cheng-Lin Jiang (Antonie van Leeuwenhoek, 2011)

Antigenically dominant proteins within the human liver mitochondrial proteome identified by monoclonal antibodies - YanFang Ju; JinJu Yang; Rong Liu; XiaoLan Liu; XueMei Du; Li Liu; ZhiCheng Chen; Jun Chi; ShuEr Liu; Yuan Gao; JianEn Gao; ShunChang Jiao; et al. (Science China Life Sciences, 2011)

Methotrexate ameliorates pristane-induced arthritis by decreasing IFN-γ and IL-17A expressions - Wei-kun Hou; Lie-su Meng; Fang Zheng; Yu-rong Wen; Wen-hua Zhu; Cong-shan Jiang; Xiao-jing He; Yan Zhou; She-min Lu (Journal of Zhejiang University-SCIENCE B, 2011)

Quantitative estimation of the shrub canopy LAI from atmosphere-corrected HJ-1 CCD data in Mu Us Sandland - Wei Chen; ChunXiang Cao; QiSheng He; HuaDong Guo; Hao Zhang; RenQiang Li; Sheng Zheng; Min Xu; MengXu Gao; Jian Zhao; Sha Li; XiLiang Ni; et al. (Science China Earth Sciences, 2010)

Colorectal cancer cell growth inhibition by linoleic acid is related to fatty acid composition changes - Xiao-feng Lu; Guo-qing He; Hai-ning Yu; Qi Ma; Sheng-rong Shen; Undurti N. Das (Journal of Zhejiang University-SCIENCE B, 2010)

A mini review of MAR-binding proteins - Tian-Yun Wang; Zhong-Min Han; Yu-Rong Chai; Jun-He Zhang (Molecular Biology Reports, 2010)

Transcription pattern of UL131A-128 mRNA in clinical strains of human cytomegalovirus - Zhengrong Sun; Gaowei Ren; Yanping Ma; Ning Wang; Yaohua Ji; Ying Qi; Mali Li; Rong He; Qiang Ruan (Journal of Biosciences, 2010)

Effect of glycyrrhizin on the activity of CYP3A enzyme in humans - Jiang-Hua Tu; Yi-Jing He; Yao Chen; Lan Fan; Wei Zhang; Zhi-Rong Tan; Yuan-Fei Huang; Dong Guo; Dong-Li Hu; Dan Wang; Hong-Hao Zhou (European Journal of Clinical Pharmacology, 2010)

Effects of mercury on the activity and community composition of soil ammonia oxidizers - Yu-Rong Liu; Yuan-Ming Zheng; Ju-Pei Shen; Li-Mei Zhang; Ji-Zheng He (Environmental Science and Pollution Research, 2010)

Over-expression of ThpI from Choristoneura fumiferana enhances tolerance to cold in Arabidopsis - Bo Zhu; Ai-Sheng Xiong; Ri-He Peng; Jing Xu; Xiao-Fen Jin; Xiu-Rong Meng; Quan-Hong Yao (Molecular Biology Reports, 2010)

Identification and characterization of a novel ∆6-fatty acid desaturase gene from Rhizopus nigricans - He Lu; Jia-Na Li; You-Rong Chai; Xue-Kun Zhang (Molecular Biology Reports, 2009)

Curcumin prevents liver fibrosis by inducing apoptosis and suppressing activation of hepatic stellate cells - Jian-Chang Shu; Ya-Jun He; Xia Lv; Guo-Rong Ye; Le-Xin Wang (Journal of Natural Medicines, 2009)

Detection of survivin-expressing circulating cancer cells in the peripheral blood of patients with esophageal squamous cell carcinoma and its clinical significance - Mei Cao; Shang-Mian Yie; Sheng-Min Wu; Shu Chen; Be Lou; Xu He; Shang-Rong Ye; Ke Xie; Lin Rao; En Gao; Nai-Yao Ye (Clinical & Experimental Metastasis, 2009)

PEG-conjugated PAMAM Dendrimers Mediate Efficient Intramuscular Gene Expression - Rong Qi; Yu Gao; Yin Tang; Rui-Rui He; Tao-Le Liu; Yun He; Sheng Sun; Bo-Yu Li; Yang-Bing Li; George Liu (The AAPS Journal, 2009)

Suppression of neuronal excitability by the secretion of the lamprey (Lampetra japonica) provides a mechanism for its evolutionary stability - Shaopeng Chi; Rong Xiao; Qingwei Li; Liwei Zhou; Rongqiao He; Zhi Qi (Pflügers Archiv - European Journal of Physiology, 2009)

Increased expression of Toll-like receptors 4 and 9 in human lung cancer - Yan-Bei Zhang; Feng-Lian He; Ming Fang; Tian-Feng Hua; Bi-Dan Hu; Zhi-Hong Zhang; Qi Cao; Rong-Yu Liu (Molecular Biology Reports, 2009)

Relationship between transmembrane signal transduction pathway and DNA repair and the mechanism after global cerebral ischemia-reperfusion in rats - Rong-Liang Xue; Jia-Xuan He; Ning Wang; Feng-Zhen Yao; Jian-Rui Lv; Gang Wu (Neuroscience Bulletin, 2009)

Epigallocatechin-3-gallate affects the growth of LNCaP cells via membrane fluidity and distribution of cellular zinc - Jun-guo Yang; Hai-ning Yu; Shi-li Sun; Lan-cui Zhang; Guo-qing He; Undurti N. Das; Hui Ruan; Sheng-rong Shen (Journal of Zhejiang University-SCIENCE B, 2009)

Diagnostic value of HCMV pp65 antigen detection by FCA for symptomatic and asymptomatic infection: compared to quantification of HCMV DNA and detection of IgM antibody in infants - Zhengrong Sun; Xiangshi Ceng; Zhiqin Mao; Jidong Wang; Qing Liu; Yaohua Ji; Yanping Ma; Ying Qi; Rong He; Qiang Ruan (Medical Microbiology and Immunology, 2009)

Induction of cytochrome P450 2B6 activity by the herbal medicine baicalin as measured by bupropion hydroxylation - Lan Fan; Jin-Chao Wang; Feng Jiang; Zhi-Rong Tan; Yao Chen; Qing Li; Wei Zhang; Guo Wang; He-Ping Lei; Dong-Li Hu; Dan Wang; Hong-Hao Zhou (European Journal of Clinical Pharmacology, 2009)

Gene mapping related to yellow green leaf in a mutant line in rice (Oryza sativa L.) - Peng Du; Ying-Hua Ling; Xian-Chun Sang; Fang-Ming Zhao; Rong Xie; Zheng-Lin Yang; Guang-Hua He (Genes & Genomics, 2009)

The CYP2C19 ultra-rapid metabolizer genotype influences the pharmacokinetics of voriconazole in healthy male volunteers - Guo Wang; He-Ping Lei; Zhi Li; Zhi-Rong Tan; Dong Guo; Lan Fan; Yao Chen; Dong-Li Hu; Dan Wang; Hong-Hao Zhou (European Journal of Clinical Pharmacology, 2009)

Microsatellite variability reveals the necessity for genetic input from wild giant pandas ( Ailuropoda melanoleuca ) into the captive population - FUJUN SHEN; ZHIHE ZHANG; WEI. HE; BISONG YUE; ANJU. ZHANG; LIANG ZHANG; RONG. HOU; CHENGDONG WANG; TOSHI WATANABE (Molecular Ecology, 2009)
Recent success in breeding giant pandas in captivity has encouraged panda conservationists to believe that the ex situ population is ready to serve as a source for supporting the wild population. In this study, we used 11 microsatellite DNA markers to assess the amount and distribution of genetic variability present in the two largest captive populations (Chengdu Research Base of Giant Panda Breeding, Sichuan Province and the China Research and Conservation Center for the Giant Panda at Wolong, Sichuan Province). The data were compared with those samples from wild pandas living in two key giant panda nature reserves (Baoxing Nature Reserve and Wanglang Nature Reserve). The results show that the captive populations have retained lower levels of allelic diversity and heterozygosity compared to isolated wild populations. However, low inbreeding coefficients indicate that captive populations are under careful genetic management. Excessive heterozygosity suggests that the two captive populations have experienced a genetic bottleneck, presumably caused by founder effects. Moreover, evidence of increased genetic divergence demonstrates restricted breeding options within facilities. Based on these results, we conclude that the genetic diversity in the captive populations is not optimal. Introduction of genetic materials from wild pandas and improved exchange of genetic materials among institutions will be necessary for the captive pandas to be representative of the wild populations.

Effects of ginkgolide B on neuronal discharges in paraventricular nucleus of rat hypothalamic slices - Yue Lin; Ru Wang; Xin Wang; Rui-Rong He; Yu-Ming Wu (Neuroscience Bulletin, 2008)

Four trace elements contents of water environment of mining subsidence in the Huainan diggings, China - En-qin Yao; He-rong Gui (Environmental Monitoring and Assessment, 2008)

Microbial composition and diversity of an upland red soil under long-term fertilization treatments as revealed by culture-dependent and culture-independent approaches - Ji-Zheng He; Yong Zheng; Cheng-Rong Chen; Yuan-Qiu He; Li-Mei Zhang (Journal of Soils and Sediments, 2008)

A preliminary study on the teratogenesis of dexamethasone and the preventive effect of vitamin B12 on murine embryonic palatal shelf fusion in vitro - Sheng-jun Lu; Wei He; Bing Shi; Tian Meng; Xiao-yu Li; Yu-rong Liu (Journal of Zhejiang University-SCIENCE B, 2008)

PCR-CTPP: a rapid and reliable genotyping technique based on ZFX/ZFY alleles for sex identification of tiger (Panthera tigris) and four other endangered felids - Kun Wei; Zhihe Zhang; Wenping Zhang; Xiao Xu; Xu Liang; Guangxin He; Fujun Shen; Liang Zhang; Rong Hou; Bisong Yue (Conservation Genetics, 2008)

Evaluation of FORS-D Analysis: A Comparison with the Statistically Significant Stem-loop Potential - Chi-Yu Zhang; Ji-Fu Wei; Jian-Sheng Wu; Wen-Rong Xu; Xiao Sun; Shao-Heng He (Biochemical Genetics, 2008)

Heregulin protects mesenchymal stem cells from serum deprivation and hypoxia-induced apoptosis - Chun Gui; Jian An Wang; Ai Na He; Tie Long Chen; Rong Hua Luo; Jun Jiang; Xin Yang Hu; Xiao Jie Xie (Molecular and Cellular Biochemistry, 2007)

Human cytomegalovirus UL145 gene is highly conserved among clinical strains - Zhengrong Sun; Ying Lu; Qiang Ruan; Yaohua Ji; Rong He; Ying Qi; Yanping Ma; Yujing Huang (Journal of Biosciences, 2007)

Intergeneration CAG expansion in a Wuhan juvenile-onset Huntington disease family - Yuan Liu; Yan Shen; He Li; Hui Wang; Zhen-Rong Yang; Yan Chen; Yan-Ping Tang (Neuroscience Bulletin, 2007)

Unexpected effect of concomitantly administered curcumin on the pharmacokinetics of talinolol in healthy Chinese volunteers - He Juan; Bernd Terhaag; Zang Cong; Zhang Bi-Kui; Zhu Rong-Hua; Wang Feng; Su Fen-Li; Song Juan; Tang Jing; Peng Wen-Xing (European Journal of Clinical Pharmacology, 2007)

Silver nanoparticles: partial oxidation and antibacterial activities - Chun-Nam Lok; Chi-Ming Ho; Rong Chen; Qing-Yu He; Wing-Yiu Yu; Hongzhe Sun; Paul Kwong-Hang Tam; Jen-Fu Chiu; Chi-Ming Che (JBIC Journal of Biological Inorganic Chemistry, 2007)

Nematicidal Resorcylides from the Aquatic Fungus Caryospora callicarpa YMF1.01026 - Jinyan Dong; Yanhui Zhu; Hongchuan Song; Ru Li; Hongping He; Haiyang Liu; Rong Huang; Yongping Zhou; Le Wang; Yi Cao; Keqin Zhang (Journal of Chemical Ecology, 2007)

Dynamics in microbial immobilization and transformations of phosphorus in highly weathered subtropical soil following organic amendments - Jinshui Wu; Min Huang; He-Ai Xiao; Yi-Rong Su; Cheng-Li Tong; Dao-You Huang; J. Keith Syers (Plant and Soil, 2007)

BRD2 is one of BRD7-interacting proteins and its over-expression could initiate apoptosis - Ming Zhou; Xiao-Jie Xu; Hou-De Zhou; Hua-Ying Liu; Jia-Jin He; Xiao-Ling Li; Cong Peng; Wei Xiong; Song-Qing Fan; Jian-Hong Lu; Jue Ouyang; Shou-Rong Shen; et al. (Molecular and Cellular Biochemistry, 2006)

Genetic spatial clustering: significant implications for conservation of wild soybean (Glycine soja: Fabaceae) - Yan Jin; Tianhua He; Bao-Rong Lu (Genetica, 2006)

Bone marrow mesenchymal stem cell transplantation combined with perindopril treatment attenuates infarction remodelling in a rat model of acute myocardial infarction - Jian-an Wang; Rong-hua Luo; Xing Zhang; Xiao-jie Xie; Xin-yang Hu; Ai-na He; Jie Chen; Jia-hui Li (Journal of Zhejiang University-SCIENCE B, 2006)

The A and B Loci in Tobacco Regulate a Network of Stress Response Genes, Few of which are Associated with Nicotine Biosynthesis - Sarah K. Kidd; Amanda A. Melillo; Rong-He Lu; Deborah G. Reed; Norihito Kuno; Kenko Uchida; Masaki Furuya; John G. Jelesko (Plant Molecular Biology, 2006)

Tissue distribution of the secretory protein, SPLUNC1, in the human fetus - Hou-De Zhou; Song-Qin Fan; Jin Zhao; Dong-Hai Huang; Ming Zhou; Hua-Ying Liu; Zhao-Yang Zeng; Yi-Xing Yang; He Huang; Xiao-Ling Li; Shou-Rong Shen; Gui-Yuan Li (Histochemistry and Cell Biology, 2006)

OsGLU1, A Putative Membrane-bound Endo-1,4-ß-D-glucanase from Rice, Affects Plant Internode Elongation - Hua-Lin Zhou; Si-Jie He; Yang-Rong Cao; Tao Chen; Bao-Xing Du; Cheng-Cai Chu; Jin-Song Zhang; Shou-Yi Chen (Plant Molecular Biology, 2006)

Environmental evolution of ordos desert in china since 1.1Ma B.P. as indicated by Yulin stratigraphical section and its grain-size analysis results - Bao-sheng Li; Shang-yu Gao; Guang-rong Dong; He-ling Jin (Chinese Geographical Science, 2005)

Thermal effects of building’s external surfaces in city - Yi-ping Zhang; Yun-ling He; Yu-hong Liu; You-xin Ma; You-rong Li; Jun-xia Dou (Chinese Geographical Science, 2004)

The role of CYP2C19 in amitriptyline N-demethylation in Chinese subjects - Zhi-Ping Jiang; Yan Shu; Xiao-Ping Chen; Song-Lin Huang; Rong-Hua Zhu; Wei Wang; Nan He; Hong-Hao Zhou (European Journal of Clinical Pharmacology, 2002)